Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
previousShortDOI: 10/ghgnfn previousShortDOI: 10/ghgnfn previousDOI: 10.5281/zenodo.4779020 previousDOI: 10.5281/zenodo.4768577 previousDOI: 10.5281/zenodo.3594489 previousShortDOI: 10/ghgnfn EdTechHub.Copy: 2129771:USWMWK73 previousShortDOI: 10/ghgnfn KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523943 10.5281/zenodo.3594489 10.5281/zenodo.4768577 10.5281/zenodo.4779020 10.53832/edtechhub.0015 10/ghgnfn 2129771:K852X3EV 2129771:T7BUZI5N 2129771:USWMWK73 2339240:5KS58AH6 2339240:NZDE37HY 2405685:NM6CPLE9 2405685:SSWKT2MV 2405685:TDVP3W34
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology; EdTech; low-income countries; literature review

Research publication strategy and proposed publications - Haßler, Björn; McIntyre, Nora; Hollow, David; Jordan, Katy; Hennessy, Sara; Brugha, Meaghan; Mitchell, Joel (EdTech Hub, 2019)
EdTechHub.Copy: 2129771:SNH4JG9L EdTechHub.Source: 2339240:94ZP3EK4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3624978 2129771:SNH4JG9L 2339240:94ZP3EK4 2339240:VMNDUZSF 2405685:2GLWRD86
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Reviewing the research literature in educational technology for development: Balancing rigour and inclusivity - Jordan, Katy (EdTech Hub, 2019)
shortDOI: 10/ghgnf5 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3581041 10/ghgnf5 2405685:YXIGT4W9
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _zenodoETH

Hello, I’m Björn, Director of Research – The EdTech Hub - Haßler, Björn (EdTech Hub, 2019)
I’m Dr Björn Haßler, one of the three Directors of Research for the programme. Research, and particularly at-scale research, is a core focus for the #EdTechHub and that’s why we have three Directors of Research, who will also introduce themselves. I am — we all are — extremely happy that we have been awarded the programme. We, like all our competitors, worked hard for around 1.5 years until the final submission. However, this work paid off! It means we can get going on the important mission.
EdTechHub.Copy: 2129771:NPLNWHCZ shortDOI: 10/ghgnfd KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906829 10/ghgnfd 2129771:NPLNWHCZ 2129771:XKQV2EDS 2405685:3IM8DBXI
Keywords: _DOILIVE; _EdTechHub_Output; _yl:r; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Five starting points on innovation for the EdTech Hub – The EdTech Hub - Simpson, Lea (EdTech Hub, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:XCJNWSVR XCJNWSVR
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Introducing the EdTech Hub’s programme for research in low-income countries – The EdTech Hub - Hennessy, Sara (EdTech Hub, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:A7H9CPGD A7H9CPGD
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech Hub Research and Innovation to fulfill the potential of EdTech - Nicolai, Susan (EdTech Hub, 2019)
EdTechHub.ItemAlsoKnownAs: 2405685:3547DQJS
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

The EdTech Hub’s approach to amplifying impact through engagement – The EdTech Hub - Jamieson Eberhardt, Molly (EdTech Hub, 2019)
If you have spent time working in the education sector, you’ll know that even marginal gains are worthy of celebration. Those of us involved in launching the EdTech Hub know this well — from our experience as teachers, researchers, advisers, programme implementers, and civil servants. Nevertheless, we have the ambition to help accelerate progress toward quality education at an unprecedented rate. We of course know that sustainable change often takes time, and we respect hard-earned marginal gains. But what we’re really after is improvement in education outcomes at a pace that matches the urgency of the problem — think millions of children receiving quality education within a decade, not in decades.
shortDOI: 10/ghgngr KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906791 10/ghgngr 2405685:AGB565DF 2405685:MUPWVYW6
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
previousshortDOI: 10/ghgk6v previousDOI: 10.5281/zenodo.3346903 EdTechHub.Source: 2405685:3BG5X7VG EdTechHub.Source: <this> shortDOI: 10/ghgk6v KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3346903 10.53832/edtechhub.0017 10/ghgk6v 2129771:FLGEYF22 2339240:SZ4GSDD6 2405685:3BG5X7VG
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Methodology for literature reviews undertaken by the EdTech Hub - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Sara Hennessy; David Hollow; Katy Jordan; Kevin Martin; Mary Murphy; Hannah Walker (EdTech Hub, 2019)
An output of the EdTEch Hub
EdTechHub.Copy: 2129771:3GKL5PCI EdTechHub.Copy: 2129771:L2EAYWTN shortDOI: 10/ghgnfq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3352101 10.5281/zenodo.3595594 10/ghgnfq 2129771:3GKL5PCI 2129771:K4IV67YV 2129771:L2EAYWTN 2317526:NRY5DISC 2339240:LY57CR53 2339240:XNCNITQP 2405685:BMM3Z3CM 2405685:CEJDF5XI
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _dont_post_PDF; _yl:h; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Systemic Mixed-Methods Research — A conceptual framework for EdTech research along the IDIA scale - Haßler, Björn; Hennessy, Sara; Hollow, David; Simpson, Lea; Carter, Alice; Damani, Kalifa; Francis, Gill; Jordan, Katy; McIntyre, Nora; Mitchell, Joel (EdTech Hub, 2019)
EdTechHub.Copy: 2129771:SLHSYDRF PreviousDOI: 10.5281/zenodo.3377829 PreviousShortDOI: 10/ghgngc KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3377828 10.5281/zenodo.3377829 10.5281/zenodo.3595482 10/ghgngc 2129771:84AIHEAJ 2129771:Q74CFTXR 2129771:SLHSYDRF 2339240:2DHE9CQC 2339240:BF96YT5K 2339240:FJZA9NPX 2339240:NLMLQD75 2405685:6YT2AIMC 2405685:7S8Z2IUF 2405685:RUSE8WYV
Keywords: LP: English; R:Mixed methods; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF; _yl:f; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Complexity and Considerations in Delivering Adaptive Learning Digital Services - Proctor, Jamie (EdTech Hub, 2019)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4561896 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4561896 2339240:M4PBAXK6 2405685:XU7B7DHZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Mobile learning policy and practice in Africa: Towards inclusive and equitable access to higher education - Kaliisa, Rogers; Picard, Michelle (Australasian Journal of Educational Technology, 2019)
This article presents the results of a review of practice and policy in relation to mobile learning and its potential to enhance inclusive and equitable access to higher education in Africa. We reviewed academic literature on potential barriers. Then, we explored the current state of the mobile learning policy environment in 10 African countries through an analysis of how these policies have tried to address the prominent challenges in the adoption of mobile learning as identified in the literature. The findings reveal that significant resourcing inequalities and epistemological, sociocultural, and institutional barriers remain and affect mobile learning adoption. The analysis also reveals that there is still a policy vacuum in relation to mobile learning specific policies within African higher education institutional and governmental policies. Thus, the formal integration of mobile learning in higher education to facilitate equitable access is very much in its infancy. This article suggests a strong need for institutional, cross-institutional, national and African-wide mobile learning specific policies to ensure better implementation of mobile learning. As interest in mobile learning continues to grow, this review will provide insights into policy and strategic planning for the adoption of mobile learning to achieve inclusive and equitable access to higher education.
Number: 6 KerkoCite.ItemAlsoKnownAs: 10.14742/ajet.5562 2405685:HRGWJESX 4042040:2SL6HJAA
Keywords: Africa; Mobile learning; equity; higher education; inclusive; policy

Sierra Leone designs online portal to take long wait out of teacher recruitment - Directorate of Science, Technology & Innovation (Sierra Leone) (2019)
A new teacher recruitment portal developed at the Directorate of Science, Technology, and Innovation (DSTI) will make it easier and faster for education administrators to hire teachers, and allocate teachersRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2405685:UWP4N7FT

Teacher Professional Development in Tanzania: Challenges and Opportunities - Komba, Sotco Claudius; Mwakabenga, Rehema Japhet (Educational Leadership, 2019)
This chapter is about teacher professional development in Tanzania. The authors have examined the current status of teacher professional development in Tanzania, focusing on predominant perspectives on the concept and provision modalities. In addition, the authors have identified challenges facing teacher professional development in Tanzania, most of which seem to be systemic. The challenges include lack of explicit policy and guidelines for teacher professional development, limited knowledge on teacher professional development among teacher professional development stakeholders, predominance of traditional approach to teacher professional development, and ineffective organization of teacher professional development activities. It is, thus, concluded that a number of opportunities are available for effective teacher professional development in Tanzania. These include strengthening the available institutions responsible for teacher professional development, making use of different teacher professional development providers available in the country to promote professional development activities for teachers through a harmonized scheme and capitalizing on the use of different communication networks and the national optic fiber to promote self-directed teacher professional development.
Publisher: IntechOpen KerkoCite.ItemAlsoKnownAs: 10.5772/intechopen.90564 2339240:9MJFKUCS 2405685:632GMNKZ
Keywords: _Tanzania; _final_bib

A systematic review on literature-based discovery: General overview, methodology, & statistical analysis - Thilakaratne, Menasha; Falkner, Katrina; Atapattu, Thushari (ACM Computing Surveys, 2019)
The vast nature of scientific publications brings out the importance of Literature-Based Discovery (LBD) research that is highly beneficial to accelerate knowledge acquisition and the research development process. LBD is a knowledge discovery workflow that automatically detects significant, implicit knowledge associations hidden in fragmented knowledge areas by analysing existing scientific literature. Therefore, the LBD output not only assists in formulating scientifically sensible, novel research hypotheses but also encourages the development of cross-disciplinary research. In this systematic review, we provide an in-depth analysis of the computational techniques used in the LBD process using a novel, up-to-date, and detailed classification. Moreover, we also summarise the key milestones of the discipline through a timeline of topics. To provide a general overview of the discipline, the review outlines LBD validation checks, major LBD tools, application areas, domains, and generalisability of LBD methodologies. We also outline the insights gathered through our statistical analysis that capture the trends in LBD literature. To conclude, we discuss the prevailing research deficiencies in the discipline by highlighting the challenges and opportunities of future LBD research.
KerkoCite.ItemAlsoKnownAs: 10.1145/3365756 2405685:VSAB6MHU 2486141:7P3SZUP3 2486141:FKA6GEWK
Keywords: LBD; Literature-based discovery; hypotheses generation; knowledge discovery; literature mining; systematic review; text mining

Human Development Report 2019 - Viet Nam briefing note - United Nations Development Programme (UNDP, 2019)
Beyond income, beyond averages, beyond today: Inequalities in human development in the 21st century
KerkoCite.ItemAlsoKnownAs: 2339240:6JH8NRWS 2405685:Q5AS8C6J

Prize Lecture: Michael Kremer, Prize in Economic Sciences 2019 - Nobel Prize (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:UADJ9JZR

Integration of Technology in the Training of Basic Education Teachers in Nigeria: Issues, Challenges and Prospects - Egede, Bernadette Amukahara Joy; Asabor, Mary (2019)
Book Title: ADECT 2019 Proceedings Publisher: Oklahoma State University Libraries KerkoCite.ItemAlsoKnownAs: 2339240:M42RYQLB 2405685:NUQNAI3Z

Supporting refugee distance education: A review of the literature - Taftaf, Randa; Williams, Christy (American Journal of Distance Education, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1080/08923647.2020.1691411 2339240:KT5K3HND 2405685:9RV8LDXF

Data governance: A conceptual framework, structured review, and research agenda - Abraham, Rene; Schneider, Johannes; vom Brocke, Jan (International Journal of Information Management, 2019)
Data governance refers to the exercise of authority and control over the management of data. The purpose of data governance is to increase the value of data and minimize data-related cost and risk. Despite data governance gaining in importance in recent years, a holistic view on data governance, which could guide both practitioners and researchers, is missing. In this review paper, we aim to close this gap and develop a conceptual framework for data governance, synthesize the literature, and provide a research agenda. We base our work on a structured literature review including 145 research papers and practitioner publications published during 2001-2019. We identify the major building blocks of data governance and decompose them along six dimensions. The paper supports future research on data governance by identifying five research areas and displaying a total of 15 research questions. Furthermore, the conceptual framework provides an overview of antecedents, scoping parameters, and governance mechanisms to assist practitioners in approaching data governance in a structured manner.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijinfomgt.2019.07.008 2339240:PBSJC28X 2339240:QNUP8K53 2405685:I6GXD6TV 2405685:IHNENRTG
Keywords: Conceptual framework; Data governance; Information governance; Literature review; Research agenda

Possibilities of using Mobile Technology to improve Early Grade Reading in Bangladesh: Towards a Practical Framework - Ahsan, Sumera; Hossain, Md; Sarwar, Sheikh (2019)
Using mobile phones can enhance literacy skills such as reading. However, the success in terms of gain in reading skill using mobile phones depends on manifold conditions and factors which are context dependent. Therefore, the process of implementation of initiative that used mobile phones for boosting literacy is worth exploring in different contexts. The aim of this research project was to capture the first impression of the stakeholders related to the mBoost project, a project that used voices and text to help teachers and parents use activities to enhance children's reading skills, immediately after its piloting. Data was collected through qualitative interview, observation, and FGDs with parents, teachers, students, and relevant Save the Children Staff. This research found that three types of factors, technical, socio-cultural, and individual end user characteristics affected the implementation process in four phases (sending, receiving, comprehending, and implementing text and voice message activities) narrowing down the targeted benefits.
KerkoCite.ItemAlsoKnownAs: 2339240:5YUYY2RL 2405685:KSGSB638

Global South teacher educators in digital landscape: implications on professional learning - Impedovo, Maria Antonietta; Malik, Sufiana Khatoon; Kinley, Kinley (Research on Education and Media, 2019)
Abstract This article explores Pakistani and Bhutanese teacher educators’ digital competences about the use of social media, digital resources and professional online communities and implications of this on professional learning. The two countries, less discussed in international educational literature, are facing a growing use of the Internet in teaching and learning. Data include a survey completed by 67 teacher educators from Pakistan and 37 teachers from Bhutan, as well as semi-structured interviews from both countries. This study provides evidence of how teachers’ interaction on social networks and the use of digital resources play a central role in the introduction of innovative pedagogical practices of teacher educators, and teacher educators remain interested in knowledge sharing through social media for their professional learning.
Publisher: Sciendo Section: Research on Education and Media KerkoCite.ItemAlsoKnownAs: 10.2478/rem-2019-0018 2339240:Z3R2S3E6 2405685:9SU5FW7M
Keywords: ⚠️ Invalid DOI

Support for children and young people with vision impairment in educational settings (Welsh Government, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BVB4T4PT 2405685:PE87BSH7

A Study of the Association between Self-Directed Learning Readiness and Academic Achievement of Student-Teachers in Pakistan - Hussain, Tariq; Sabar, Ajia; Jabeen, Rafia (Bulletin of Education and Research, 2019)
Education at every level is typically future-oriented; it is imperative for the learners to keep pace with the unpredictable and fast changing world. The field of teacher-education is no exception. Student-centered approaches have started gaining popularity in today's day and age. Self-directed learning is becoming one of the most prominent phenomena for the 21st century learners. This study investigated whether any relationship exists between Self-Directed Learning readiness (SDLR) and academic achievement of student-teachers. For this purpose, quantitative approach was adopted and correlation research design was used. The population comprised all the master level students of the Institute of Education and Research, enrolled in the session 2017-2019. The total number was 510. The researchers used multistage sampling to draw a sample. A total of 300 students were included in the research. To determine the SDLR of student-teachers, a modified SDLI questionnaire, developed by Su-Fen Cheng, Chien-Lin Kuo, Kuan-Chia Lin, and Jane LeeHsieh in 2009, was used. The analysis of the data concluded that student-teachers' self-directed learning readiness is high. It was determined that a significant difference does not exist among the population on the basis of gender or marital status.
Publisher: Institute of Education and Research KerkoCite.ItemAlsoKnownAs: 2339240:Q4MNT3WE 2405685:Q32HJ6XQ
Keywords: Academic Achievement; Correlation; Foreign Countries; Gender Differences; Graduate Students; Independent Study; Learning Readiness; Marital Status; Masters Programs; Student Centered Learning; Student Teacher Attitudes; Student Teachers; Teacher Education; ⛔ No DOI found

Assemblage Theory: Coping with Complexity in Technology Enhanced Language Learning - Matthews, Blair (Research-publishing, 2019)
Language classrooms are complex systems, but theory often simplifies these processes making researching effectiveness difficult. Assemblage theory – a theory of complexity in the social sciences – allows us to examine complexity in the language classroom. In this paper, I present an account of the language classroom that captures the complexity, subjectivity, and temporality of technology enhanced language learning. [For the complete proceedings, see ED600837.]
Publication Title: Research-publishing.net KerkoCite.ItemAlsoKnownAs: 2339240:N5SJAE74 2339240:X2DH2PJB 2405685:23WUVGJ7 2405685:CJQA4TZT
Keywords: Computer Assisted Instruction; Influence of Technology; Learning Motivation; Learning Processes; Learning Theories; Second Language Learning; Social Systems; Systems Approach; Teaching Methods

Beyond Short-Term Learning Gains: The Impact of Outsourcing Schools in Liberia after Three Years [short report] - Romero, Mauricio; Sandefur, Justin (Instituto Tecnológico Autónomo de México; Center for Global Development, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:N2C8L4D6

The new generation of interactive whiteboards: How students perceive and conceptualize? - Saltan, Fatih (Participatory Educational Research, 2019)
The aim of the study was to investigate high school students' perceptions of the new generation of Interactive white board (IWB). At the same time, the question whether there were differences in perceptions with regard to certain variables such as gender and frequency of IWB use by teachers and students was examined. To achieve this aim, a parallel mixed method design was used. A total of 877 high school students participated in the study, comprising 410 female and 467 male students. The data were collected through an "Interactive Whiteboard Student Survey" and by open-ended questions. The quantitative data were analyzed using SPSS 20.0 for descriptive statistics and multivariate analysis of variance. Nvivo8 qualitative data analysis software was utilized for coding. Appropriate themes were developed from the related codes. The qualitative analysis revealed that about half of the students thought that IWBs were useful and effective tools for learning. There were seven themes and sub-themes which explained the contribution of IWBs to students' learning. The results of the MANOVA revealed no significant effect of gender and frequency of IWB use by teacher on high school students' perception of IWBs. On the other hand, there was a statistically significant difference in students' perception of IWBs based on frequency of IWB use by himself/herself, F (6, 1662) = 3.11, p<0.5.
Publisher: Participatory Education Research ERIC Number: EJ1236334 KerkoCite.ItemAlsoKnownAs: 2339240:RFHM9GEI 2405685:H5FRRLE3 6018420:MSVZENM9
Keywords: Adolescents; Computer Peripherals; Educational Equipment; Foreign Countries; Gender Differences; High School Students; Incidence; Instructional Effectiveness; Interaction; Preferences; Projection Equipment; Public Schools; Student Attitudes; Technology Integration; Urban Schools; Usability

Prottoy: A smart phone based mobile application to detect autism of children in bangladesh - Satu, Md. Shahriare; Azad, Md. Saikat; Haque, Md. Fardin; Imtiaz, Syed Khalid; Akter, Tania; Barua, Lipika; Rashid, Mamunur; Soron, Tanjir Rashid; Al Mamun, Khondaker Abdullah (2019 4th International Conference on Electrical Information and Communication Technology (EICT), 2019)
In developing countries, autism is needed to detect at early ages that helps us to improve the conditions of children. The diagnosis of autism is a challenging issue in the low and middle income countries due to lack of trained professionals, low cost available tools and infrastructure. In this paper, we proposed a mobile interactive automated application named prottoy to screen autism between 3 to 11 years children using Bengali version of Childhood Autism Spectrum Test. It was translated into Bengali by following cross cultural validation schemes. Pictorial representation of each question was placed into this apps. So, parents can easily check autism of their children by understanding the scenarios of each question. After screening, this app is automatically manipulated user response and detected the possibility of autism of their children. We expect that this app will promote screening that help us to detect autism early of the children in Bangladesh.
KerkoCite.ItemAlsoKnownAs: 10.1109/EICT48899.2019.9068815 2339240:37SAYW3L 2405685:54F3DEIP
Keywords: Autism; CAST; Cloud computing; Cultural differences; Pediatrics; Three-dimensional displays; Tools; Visualization; autism; detection; mobile apps; screening

Top Marks for Rising in Final Year Liberia Evaluation - Skidmore, Paul (Center for Global Development; Innovations for Poverty Action, 2019)
The final report of a randomised controlled trial of Liberia’s flagship education reform has praised Rising Academies for producing “a consistently positive pattern of results across learning, access, and safety dimensions.” The three year ‘gold standard’ evaluation of the Liberia Education Adv
EdTechHub.ItemAlsoKnownAs: 2405685:FMWA647M

From OLPC XO to Positivo: Rwanda Sets the Bar Higher - Sabiiti, Daniel (KT PRESS, 2019)
Rwanda is set to distribute a new model computers that will change the ways in which primary school children learn and practice information communication and technology (ICT) lessons under the one laptop per child (OLPC) program. This move comes ahead of the review of the four year-ICT in educati
Section: National KerkoCite.ItemAlsoKnownAs: 2339240:3Z6DZUAX 2405685:UUK9XLDP

Private engagement in refugee education and the promise of digital humanitarianism - Menashy, Francine; Zakharia, Zeena (Oxford Review of Education, 2019)
This paper examines the prevalence of technological interventions in education in emergencies through a case study of private participation in Syrian refugee education in Jordan, Lebanon, and Turkey. This research is conceptually situated within critiques of ‘digital humanitarianism’, simultaneously interrogating the role of technology in humanitarian responses and the roles of private actors who promote this technology. Our study demonstrates that a pervasive optimism concerning education technology in emergencies accompanies a surge in private actor engagement in Syrian refugee education. Findings indicate that while access to technology in educational settings is important to the Syrian refugee populations, private actors’ disproportionate focus on technology is problematic, particularly when technological interventions are viewed as panaceas for refugee education; designed free from coordination; driven by proﬁt motivations; and developed in a manner decontextualised from the learning context. This study attends to the necessity of countering the overwhelming optimism about technology as a panacea for refugee education, which fails to problematise the implications of interventions developed in the Global North for a distant ‘other’ in the Global South.
KerkoCite.ItemAlsoKnownAs: 10.1080/03054985.2019.1682536 2339240:NDC5PX8G 2405685:DV2P5KPW

Rumie Management Center (RMC): Product Documentation - Janzen, Tiffany; Chugh, Manav (Rumie, 2019)
EdTechHub.ItemAlsoKnownAs: 2405685:B6MZUYHT

Communications for Development - Fink, Günther; Karlan, Dean; Udry, Christopher; Osei, Robert (Harvard Dataverse, 2019)
In 2012, Ghana Health Services (GHS), with funding from the United Nations Children’s Fund (UNICEF), launched a Communication for Development (C4D)...
KerkoCite.ItemAlsoKnownAs: 10.7910/DVN/CQRNC7 2405685:GVUSAT6F
Keywords: Health and Life Sciences; Medicine; Social Sciences

Number of pay TV households in Ghana 2014-2023 - Watson, Amy (Statista, 2019)
The timeline presents the number of pay TV households in Ghana from 2014 to 2018, and a forecast thereof until 2023.
EdTechHub.ItemAlsoKnownAs: 2405685:WYGSUTLX

The Data Protection Act (No. 24 of 2019) - Republic of Kenya (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:VXRC7SDS 2405685:K8JBSFIZ

Abracadabra (ABRA) - Coventry University (Education Endowment Foundation, 2019)
Project: Abracadabra (ABRA), An online reading programme to improve early literacy
EdTechHub.ItemAlsoKnownAs: 2405685:VUPTIFAH

Quantitizing Affective Data as Project Evaluation on the Use of a Mathematics Mobile Game and Intelligent Tutoring System - Nygren, Eeva; Blignaut, Seugnet; Leendertz, Verona; Sutinen, Erkki (Informatics in Education, 2019)
Technology-enhanced learning generally focuses on the cognitive rather than the affective domain of learning. This multi-method evaluation of the INBECOM project (Integrating Behaviourism and Constructivism in Mathematics) was conducted from the point of view of affective learning levels of Krathwohl et al. (1964). The research questions of the study were: (i) to explore the affective learning experiences of the three groups of participants (researchers, teachers and students) during the use of a mobile game UFractions and an intelligent tutoring system ActiveMath to enhance the learning of fractions in mathematics; and (ii) to determine the significance of the relationships among the affective learning experiences of the three groups of participants (researchers, teachers and students) in the INBECOM project. This research followed a sequential, equal status, multi-mode research design and methodology where the qualitative data were derived from the interviews with researchers, teachers and students, as well as from learning diaries, feelings blogs, and observations (311 documents) across three contexts (South Africa, Finland, and Mozambique). The qualitative data was quantitized (Saldaña, 2009), i.e. analysed deductively in an objective and quantifiable way as instances on an ExcelT spreadsheet for statistical analyses. All the data was explored from the affective perspective by labelling the feelings participants experienced according to the affective levels of the Krathwohl et al. (1964) framework. The researchers concluded that: (i) the research participants not only received information, but actively participated in the learning process; responded to what they learned; associated value to their acquired knowledge; organised their values; elaborated on their learning; built abstract knowledge; and adopted a belief system and a personal worldview; and (ii) affirmation of affective learning at all five levels was recognised among the three groups of participants. The study raised a number of issues which could be addressed in future, like how affective levels of learning are intertwined with cognitive levels of learning while learning mathematics in a technology-enhanced learning environment; and how pedagogical models which take into account both cognitive and affective aspects of learning support deep learning.
KerkoCite.ItemAlsoKnownAs: 10.15388/infedu.2019.18 2339240:R2M5YK7G 2405685:3SUJ8RED

A PRACTICAL AND EFFECTIVE PROGRAMME TO BUILD FOUNDATIONAL READING SKILLS FOR PRIMARY GRADE STRUGGLING LEARNERS IN INDIA - Misquitta, Radhika; Ghosh, Aditi (2019)
Curriculum-based measurement (CBM) has emerged as a valid, reliable and economic measure to assess and monitor reading skills. Unfortunately, CBMs have not been developed for the Indian context. Further, CBMs can be cumbersome to administer manually, especially given the high teacher- student ratio in India. The challenge also then remains about what teachers actually do with the reading data. Most teachers in India are unable to interpret reading scores or use them to tailor an intervention plan. This paper describes the work Gateway has begun to develop a digital curriculum- based measurement tool that is contextually relevant. This paper outlines the procedures used to select passages, including equating passages using readability formulae, as well as field testing passages. The tool will support teachers with collecting data, interpreting the scores, and most importantly, developing an intervention plan to support struggling learners. It will also outline future directions for the project.
Pages: 6381 KerkoCite.ItemAlsoKnownAs: 10.21125/iceri.2019.1535 2405685:QD674Y6P 2486141:B42E2QAP

E-learning implementation using user experience questionnaire - Pandu; Fajar, Ahmad Nurul (Journal of Physics: Conference Series, 2019)
Abstract Online learning system or commonly called e-Learning which is commonly applied to the world of education, is now increasingly used in companies with diverse business fields. The concept of e-Learning is a transformation of conventional learning into digital form. The concept of e-Learning is now widely known and can be accepted in the community as evidenced by the many applications in the world of education and business. The aim to be achieved in this study is to implement e-Learning to PT MRK Diagnostics and find out whether or not there are inhibiting factors in implementing e-Learning to PT MRK Diagnostics. The method used to obtain recommendations after using e-Learning uses the User Experience Questionnaire (UEQ) method to find out the impression of using e-Learning that affects employee performance. Edmodo e-Learning has positive impression values in the Attractiveness (1,950), Perspicuity (2,100), Efficiency (1,775), Dependability (1,575), Stimulation (1,125), and Novelty (0.875) groups.
KerkoCite.ItemAlsoKnownAs: 10.1088/1742-6596/1367/1/012015 2339240:W7KSGTM3 2405685:2SWLY8TB

The private schooling phenomenon in India: A review - Kingdon, Geeta Gandhi (2019)
This paper examines the size, growth, salaries, fee levels and per-pupil-costs of private schools, and compares these with the government school sector. Official data show a steep growth of private schooling and a corresponding rapid shrinkage in the size of the government school sector in India, suggesting parental abandonment of government schools. Data show that a very large majority of private schools in most states are ‘low-fee’ when judged in relation to: state per capita income, perpupil expenditure in the government schools, and the officially-stipulated rural minimum wage rate for daily-wage-labour. This suggests that affordability is an important factor behind the migration towards and growth of private schools. The main reason for the very low fee levels in private schools is their lower teacher salaries, which the data show to be a small fraction of the salaries paid in government schools; this is possible because private schools pay the market-clearing wage, which is depressed by a large supply of unemployed graduates in the country, whereas government schools pay bureaucratically determined minimum-wages. The paper shows how education policies can be harmful when formulated without seeking the evidence.
KerkoCite.ItemAlsoKnownAs: 2339240:Q358PXQL 2405685:BBJ3G7H2
Keywords: ⛔ No DOI found

2019 Annual Schools Census Report And Statistical Abstract - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:MJH7EBNP 2405685:VM4EWGLU

National Information, Communications and Technology (ICT) Policy - Ministry of Information, Communications and Technology, Kenya (Government of Kenya, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:P4P4HDNQ 2405685:DZ2QSTVI

Bangladesh Demographic and Health Survey 2017-2018: key indicators - NIPORT; ICF (National Institute of Population Research and Training (NIPORT) and ICF, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:77QXWVJP 2405685:2IGTN5VN

UNESCO schools give hope to Syrian refugees in Lebanon - UNESCO (2019)
“Enrolling in this school gave me hope,” says Asma Al Ahmad who fled the conflict in the Syrian Arab Republic and found refuge in the Bekaa region of Lebanon. The 16-year-old girl was deprived of education for two years, living in a refugee camp in Saadnayel. Last year, she was offered the opportunity to resume her education at a middle school established by UNESCO to provide educational complementary support programmes for young displaced Syrians. "I hope I will have a future and succeed in life, she says.
KerkoCite.ItemAlsoKnownAs: 2339240:HNS7B2C2 2405685:FLTIDLD3

Process for iterative and adaptive implementation of government policy in order to utilise educational technology - Haßler, Björn; Khalayleh, Abdullah (Open Development & Education, 2019)
An output of Activating EdTech Jordan. Information about the Activating EdTech Jordan and our outputs can be found at http://tiny.cc/ActivatingEdTech. Our outputs are archived here https://zenodo.org/communities/aet/.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3372141 2405685:E29PL7BW

Sierra Leone invests $1.5 million to bring education innovation to schools for better learning outcomes - DSTI Media (Directorate of Science, Technology and Innovation, 2019)
A national education dashboard released last month by Sierra Leone’s agency for technology and innovation and the Ministry of Basic and Senior Secondary Education (MBSSE) showed that schools and studentsRead More
KerkoCite.ItemAlsoKnownAs: 2405685:B6TMDRUY

OU partners with Ministry of Education in Ghana to launch OpenSTEM Africa - Grimmette, Hannah (OU News, 2019)
The Open University and the Ministry of Education (Ghana) have launched a programme to promote the effective teaching of practical science in Senior High Schools. Open STEM Africa: Ghana, is aimed at improving practical teaching and learning of science and in particular providing support for under-qualified or inexperienced science teachers, in line with the government of Ghana’s education policy.
Library Catalog: ounews.co Section: Education KerkoCite.ItemAlsoKnownAs: 2405685:GB3T6EY7

Rwandan ed-tech startup BAG Innovation raises $150k seed round - Disrupt Africa - Jackson, Tom (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:UTY2JHU3 2405685:WAIGHFRK

Synthesis of Reviews on Teacher Professional Development in Sub-Saharan Africa - Haßler, Björn; D’Angelo, Sophia; Walker, Hannah; Marsden, Melissa (Open Development & Education, 2019)
EdTechHub.Source: 2129771:SC8FTPC4 KerkoCite.ItemAlsoKnownAs: 2129771:SC8FTPC4 2339240:GJ83JMQA 2405685:T7DTBWJB
Keywords: _yl:i; dode_eth-src-dode; dode_eth-trf2-dode

Why we started R4D’s evaluation & adaptive learning practice - Arkedis, Jean (Results for Development, 2019)
R4D's Evaluation & Adaptive Learning practice lead, shares a new explainer video, which offers a framework for how we design, test and evaluate for impact.
KerkoCite.ItemAlsoKnownAs: 2339240:IWF249BR 2405685:ACUDTN33

‘Digital welfare state’: big tech allowed to target and surveil the poor, UN is warned - Pilkington, Ed (the Guardian, 2019)
UN’s rapporteur on extreme poverty says in devastating account big tech companies are being allowed to go unregulated in ‘human rights free-zones’
Section: Technology KerkoCite.ItemAlsoKnownAs: 2339240:8GAAFX6C 2405685:F8TY9WN2

Learning poverty - World Bank (2019)
This indicator brings together schooling and learning indicators.
KerkoCite.ItemAlsoKnownAs: 2339240:N8466Y2D 2405685:4PIXX9F9

Rwanda's education U-turn sparks debate on mother tongue instruction - Edwards, Sophie (Devex, 2019)
Amid growing consensus that teaching in a student's mother tongue can improve learning outcomes, why are some countries switching back to European languages that most teachers and children don’t understand?
EdTechHub.ItemAlsoKnownAs: 2405685:4PRWXPW4

Exploring transition toward independent learning student experiences in the first year of architecture school - Al Maani, Duaa (Welsh School of Architecture, Cardiff University, 2019)
Constructivism within the design studio capitalises on the richness embodied by the differences in learners, and strongly opposes the notion of students as empty vessels. Although this perspective suggests that learners are individual and unique, yet it emphasises on their need for outside influences to learn as well. This thesis explores the learning experiences of students in the architectural design studio, specifically looking at learning issues associated with the transition from dependence to independence and analysing students’ accounts of their learning processes during their first year. The findings suggest that the design studio is a suitable environment for facilitating learning independence in higher education. Most of the students appreciated the learning environment within the school and expressed a feeling of belonging to the community, stating that it had helped them to become more independent. More importantly, an analysis of the narratives revealed that the respondents perceived themselves as becoming more independent as they progressed through the year. However, many of the participants felt uncertain about aspects of independent learning and wanted more guidance and support, remaining attached to the practice of tutor centred learning.
KerkoCite.ItemAlsoKnownAs: 2339240:T7YPWQA5 2405685:IZS7VHYQ

Female teachers in Tanzania: An analysis of gender, poverty and constrained capabilities - Tao, Sharon (Gender and Education, 2019)
Tanzania has made great strides in improving access to education; however, concerns about the quality of this education persist due to reports of teacher absenteeism, distraction and lack of preparation. Given this situation, this study aimed to investigate teachers’ values and contexts to provide nuanced understandings of teacher practice and behaviour, particularly with regard to how gender intersects with these. Ethnographic case studies were conducted at three Tanzanian schools and findings demonstrated that although men and women experienced similar material conditions, there were marked differences between their opportunities and constraints, which female teachers could readily relate to instances of absenteeism and distraction. A feminist interpretation of the capability approach was used to reflect on female teachers’ capabilities, constraints and agency; and socialist feminist theory was used to further elaborate on why male and female teachers differ in their valued capabilities, their levels of constraint and their actions resulting from negotiating constraint.
KerkoCite.ItemAlsoKnownAs: 10.1080/09540253.2017.1336203 2339240:JC2UHY96 2405685:KMVD4QX8

Using design-based research to bring partnership between researchers and practitioners - Getenet, Seyum (Educational Research, 2019)
Background: A key aim of educational research is for findings to inform practice, thereby bringing about improvements in teaching and learning. However, the relationship between research and practice is complex, and there is often no clear link between changes in practice and research findings. One of the challenges for research and practice is breaking down barriers and finding effective and sustainable ways to translate research findings into practical solutions in the classroom.Purpose: This discursive paper focuses on describing the nature of the partnership working involved when a design-based research (DBR) approach was employed to bring researchers and practitioners together. The researchers and practitioners worked in collaboration to design a professional development (PD) programme, in order to solve classroom problems and enhance practitioners’ research engagement.Sources of evidence: This paper describes the author’s experience of using DBR to co-design a PD programme that was responsive to a particular context and practitioners’ needs. It illustrates and exemplifies the ways in which the researcher–practitioner collaboration itself sits at the heart of the design process and enabled solutions to be found. The paper also considers the epistemological positions of the practitioners and researchers in the different stages of DBR. The context for the description is a mixed-methods intervention study conducted in two colleges of teacher education, which documented the design and refinement of a PD programme to facilitate teachers’ effective use of technology to teach mathematics.Discussion and conclusions: The examples presented and discussed here suggest how a DBR process is able to facilitate fruitful collaborations between researchers and practitioners and increase engagement in research. By working with practitioners to design interventions such as PD programmes, DBR can provide a practical approach for improving practice and deepening the relationship between educational research and classroom practice.
EdTechHub.Copy: 2129771:XWT48UG5 shortDOI: 10/ggd8hp KerkoCite.ItemAlsoKnownAs: 10.1080/00131881.2019.1677168 10/ggd8hp 2129771:XWT48UG5 2339240:FNGCAY8H 2405685:SXE25TP7
Keywords: Design-based research; evidence-informed practice; practice; practitioners; professional development; teacher education

Understanding the Barriers and enablers of Effective Communities of Practice in Sierra Leone Through a Collaboration Between Dubai Cares and Open Development and Education - Lurvink, Anne-Fleur (Open Development & Education, 2019)

Call me educated: Evidence from a mobile phone experiment in Niger✰ - Aker, Jenny C; Ksoll, Christopher (Economics of Education Review, 2019)
Teacher absenteeism is an important obstacle to sustained learning gains in many developing countries. We report the results from a randomized evaluation of an adult education program in Niger, which included an additional intervention designed to improve teacher accountability and students’ learning. Villages were randomly assigned to one of three groups. The first was a two-year adult education program, with normal visits by non-governmental organization (NGO) and Ministry staff. The second included the same curriculum and visits as the first, but villages also received a mobile intervention: weekly phone calls to the teacher, village chief and two randomly selected students. The third was a pure control group, with no adult education program or calls. We find that both interventions improved students’ learning outcomes: across both years of the program, students in the standard adult education program increased their math and reading test scores by 0.19–0.22 s.d, respectively. The mobile phone intervention led to an additional increase in math and reading test scores of 0.12 and 0.15 s.d., with stronger effects amongst called students. We also address alternative threats to identification, namely, differential attrition and baseline imbalance, and find that the math results are robust across these different specifications. This suggests that using mobile phone technology as a means to communicate with teachers and students can improve learning outcomes, beyond its use as a pedagogical tool within the classroom.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.econedurev.2019.05.001 2339240:EX6NJUX9 2339240:VFF5WY9J 2405685:6VR2BZKJ 2405685:77X2RGGE 2405685:LTFZY8UK 2534379:MEYIS2SG
Keywords: Adult education; Information technology; Monitoring; Niger; Teacher absenteeism

Improving teacher professional development for online and blended learning: a systematic meta-aggregative review - Philipsen, Brent; Tondeur, Jo; Pareja Roblin, Natalie; Vanslambrouck, Silke; Zhu, Chang (Educational Technology Research and Development, 2019)
In order to fully realise the potential of online and blended learning (OBL), teacher professional development (TPD) strategies on how to teach in an online or blended learning environment are needed. While many studies examine the effects of TPD strategies, fewer studies target the specific important components of these strategies. This study addresses that gap by conducting a systematic review of qualitative data consisting of 15 articles on TPD that targets OBL. Using a meta-aggregative approach, six different synthesised findings were identified and integrated into a visual framework of the key components of TPD for OBL. These synthesised findings are the base for the action recommendations which present specific and contextualised suggestions. Taken together, the findings can inform in-service teachers and trainers, together with further research and development efforts that are concerned with TPD for OBL.
Extra URL: https://doi.org/10.1007/s11423-019-09645-8 KerkoCite.ItemAlsoKnownAs: 10.1007/s11423-019-09645-8 2405685:BVQU5XV8 2534378:4WR2J4Z5

Does Education Need a QALY and Is LAYS It? - Crawfurd, Lee; Hares, Susannah; Le Nestour, Alexis; Rossiter, Jack (Center For Global Development, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:HEH7E87J 2405685:YR4DSMZM

Pakistan: Learning Poverty Brief - Fasih, Tazeen; Baron, Juan; Geven, Koen Martijn (EduAnalytics, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:JFEQA28N

Guidelines on the Development of Open Educational Resources Policies - Miao, Fengchun; Mishra, Sanjaya; Orr, Dominic; Janssen, Ben (UNESCO; Commonwealth of Learning (COL), 2019)
The publication provides guidelines and a systematic approach to develop and implement open educational resources policies in different contexts to achieve the targets of Sustainable Development Goals 4. Using a six-stage approach, the guidelines provide several templates and questions along with theoretical underpinnings and practical examples to help government officials and experts develop policies that are grounded on the needs of the stakeholders.
Accepted: 2019-10-15T18:47:31Z ISBN: 978-1-894975-97-1 KerkoCite.ItemAlsoKnownAs: 2339240:48KYWJ83 2405685:G7A3VQ2D
Keywords: ⛔ No INSPIRE recid found

Developing Interactive Multimedia Flood Prevention Education (FPE) on Disaster Risk Reduction Learning for Students with Hearing Impairment in Special School - Robiansyah, Iva Evry; Mudjito; Yuliyati; Atiqoh (2019 5th International Conference on Education and Technology (ICET), 2019)
This study aims to describe the practicality of interactive multimedia flood prevention education (FPE) in improving the understanding of flood disaster risk reduction (DRR) and describing the understanding of flood disaster management learning for students with hearing impairment. This development research used the design of media development stages according to Luther with the development of media applications based on 5 stages namely: concept, design, material collecting, assembly, testing. Data were collected from through observation and tests. The result of this development product is interactive multimedia flood prevention education (FPE) to tackle flood risk among students with hearing impairment. Based on research on the development of interactive multimedia flood prevention education (FPE) to reduce the risk of flooding for students with hearing impairment in Special School Pasuruan City, it can be concluded that the results of the questionnaire show that the students' responses were very positive in using multimedia FPE in reducing the risk of flood disasters.
0 citations (Crossref) [2024-02-28] KerkoCite.ItemAlsoKnownAs: 10.1109/ICET48172.2019.8987227 2339240:W2CBCAC5 2405685:8HMZKBXQ
Keywords: disaster risk reduction; flood prevention education; interactive multimedia; special school; students with hearing impairment; ⛔ No INSPIRE recid found

Education for Employment Sector Development Program - Asian Development Bank (2019)
The proposed Education for Employment Sector Development Program (EESDP) will strengthen human capital in the Lao People's Democratic Republic (Lao PDR) and support inclusive growth and economic diversification. The policy-based loan will support reforms to align secondary education, technical and vocational education and training (TVET), and higher education with the country's workforce needs. This includes enhancing the role of secondary education in preparing youth for employment.
Archive Location: Lao People's Democratic Republic Last Modified: 2024-04-22T09:42+08:00 Publisher: Asian Development Bank KerkoCite.ItemAlsoKnownAs: 2339240:ZUTMQUXR 2405685:PC3ZKU2Q
Keywords: ⛔ No INSPIRE recid found

Agency and technology-mediated task repetition with young learners: Research and implications for primary classroom practice - Pinter, Annamaria (Language Teaching for Young Learners, 2019)
Abstract This paper offers a review of the TBLT literature for young learners with an aim to identify some gaps where future research and classroom practice could be targeted. The specific focus of this review is on procedural task repetition for children, arguing that in addition to the linguistic benefits, task repetition is associated with important gains in the affective domain. It is suggested that technology-mediated task repetition, via tablet devices, can further enhance both opportunities for learning and confidence building and enjoyment. Due to the technological affordances, the learners are firmly in charge of creating dynamic, fluid tasks through cycles of reflection and practice, polishing their performance along the way, stretching towards their ‘upper potential’. To date research within TBLT with children has not explored yet what types of tasks children enjoy working with and why and how task repetition is realised when using tablet devices to record their own performances. This paper suggests steps that can be taken in this direction both in research and classroom practice.
Publisher: John Benjamins KerkoCite.ItemAlsoKnownAs: 10.1075/ltyl.00010.pin 2339240:Z8R58PVM 2405685:QNFR2RAE

Moving beyond the predictable failure of Ed-Tech initiatives - Sancho-Gil, Juana M.; Rivera-Vargas, Pablo; Miño-Puigcercós, Raquel (Learning, Media and Technology, 2019)
The development of Information and Communication Technology has created waves of excitement about its power to fix educational problems and improve learning results, prompting a succession of policy efforts to integrate digital technology into education. Educators, schools and corporations are increasingly driving these initiatives. This article makes the argument that a narrow vision of digital technology, which both ignores the complexity of education and wastes valuable public resources, is becoming an obstacle to significant improvement and transformation in education. Utilising our research and experience in the field of educational technology, this paper problematises the common elision of ‘technology’ and ‘digital technology’. From this basis, we then critically reflect on various common approaches to introducing digital technology in education under the guise of promoting equality and digital inclusion. These include national government-led programmes, more recent trends for local school-led initiatives, and the role of non-formal education initiatives led by corporations/foundations. Amidst the varying surface-level ‘failure’ and/or ‘success’ of these approaches, we point to limited underpinning ‘information and knowledge society’ logics in framing the application of digital technology to education. As such we conclude by considering the educational challenges for future Ed-Tech initiatives.
EdTechHub.Copy: 2129771:L5ZJ7VXE shortDOI: 10/ggcdkp KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2019.1666873 10/ggcdkp 2129771:L5ZJ7VXE 2339240:CXEEHC7A 2339240:K8RVQM7G 2339240:R8SA4YDH 2339240:WW9JKI74 2405685:5ACMB7FC 2405685:FNPABIIG 2405685:K3CJ25QT 2405685:Q2EVH3HK
Keywords: Educational change; digital technology corporations; educational challenges; educational policies; school improvement

Innovative Delivery of Education in Bangladesh Using Mobile Technology - Cristol, Dean; Al-Sabbagh, Samah; Abdulbaki, Anwar; Majareh, Maryam; Tuhin, Salah Uddin; Gimbert, Belinda (2019)
Given the increasing use and accessibility of mobile technology, a pilot study, “Innovative Delivery of Education in Bangladesh Using Mobile Technology” was carried out using mobile learning devices to both increase and enrich the delivery of educational services in a remote Bangladesh district. The APTUS system was used to allow learners’ connection to digital learning platforms and content without electricity or internet access. The researchers maintained that mobile learning associated with Project Based Learning can effect student learning in five ways: (1) contingent learning, changing...
KerkoCite.ItemAlsoKnownAs: 2339240:4FSQZLHQ 2405685:2CUIABK2

Sierra Leone turns to technology and analytics to put quality back into education - Directorate of Science, Technology & Innovation (Sierra Leone) (2019)
Today, an estimated 2 million students return to school for the second year of the Free Quality School Education (FQSE) Program. The Government of Sierra Leone commits 21% of theRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2405685:Z3DPRDU6

A new methodological approach for evaluating the impact of educational intervention implementation on learning outcomes - Outhwaite, Laura A.; Gulliford, Anthea; Pitchford, Nicola J. (International Journal of Research & Method in Education, 2019)
Randomized control trials (RCTs) are commonly regarded as the ‘gold standard’ for evaluating educational interventions. While this experimental design is valuable in establishing causal relationships between the tested intervention and outcomes, reliance on statistical aggregation typically underplays the situated context in which interventions are implemented. Developing innovative, systematic methods for evaluating implementation and understanding its impact on outcomes is vital to moving educational evaluation research beyond questions of ‘what works’, towards better understanding the mechanisms underpinning an intervention’s effects. The current study presents a pragmatic, two-phased approach that combines qualitative data with quantitative analyses to examine the causal relationships between intervention implementation and outcomes. This new methodological approach is illustrated in the context of a maths app intervention recently evaluated in a RCT across 11 schools. In phase I, four implementation themes were identified; ‘teacher support’, ‘teacher supervision’, ‘implementation quality’, and ‘established routine’. In phase II, ‘established routine’ was found to predict 41% of the variance in children’s learning outcomes with the apps. This has significant implications for future scaling. Overall, this new methodological approach offers an innovative method for combining process and impact evaluations when seeking to gain a more nuanced understanding of what works in education and why.
shortDOI: 10/ggdbd4 KerkoCite.ItemAlsoKnownAs: 10.1080/1743727X.2019.1657081 10.1080/1743727x.2019.1657081 10/ggdbd4 2339240:AET3UUCZ 2339240:T4RNXVLL 2405685:EDBC9B8E 2405685:LJR2ZQYV
Keywords: Implementation; _C:Greece GRC; _C:India IND; _C:Malawi MWI; _C:Netherlands NLD; _C:Pakistan PAK; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:scheme:1; education; evaluation; intervention; mixed-methods

Science teachers’ beliefs and attitudes towards the use of interactive whiteboards in education - Tombak, Ceren; Ateskan, Armagan (Journal of Turkish Science Education, 2019)
This study aimed to explore the beliefs and attitudes of 36 science teachers (biology, physics and chemistry) in six high schools in Ankara towards the use of Interactive White Boards (IWB). Of these, three teachers from each school were chosen for interview and classroom observations according to their questionnaire results with purposeful sampling method. The results were analyzed with descriptive statistics and qualitative data analysis methods. According to the results, teachers agree that using IWBs facilitate reaching different sources and display them to the whole class immediately. Teachers describe the common use of IWBs as showing visual materials, videos and animations in science classes. The majority of teachers enjoy using the IWB technology and express positive feelings about it. Most teachers state that they follow the advances in educational technology regularly. Since the frequencies are approximately equal, no meaningful difference was found between teachers with different majors on staying current with technology. The findings show that biology and chemistry teachers use IWB more frequently than physics teachers. Although the teachers have positive attitudes towards the use of IWBs, it was seen that most of them do not feel comfortable while using them in the classrooms. The interviews indicate the reason for that as insufficient in-service trainings.
KerkoCite.ItemAlsoKnownAs: 10.12973/tused.10290a 2339240:DSLFZ7RZ 2405685:5IKGL694 6018420:WQIUGA7C

The Opportunities and Challenges for Developing ICT-Based Science Learning and Teaching in Ghana - Cullen, Jane; Mallet, Joshua (Pan-Commonwealth Forum, 2019)
Africa’s transition to an innovation-led, knowledge-based economy could drive the continent’s economic growth and lift millions out of poverty and there is opportunity to increase the number of skilled professionals across the chemistry, biology and physics disciplines. However not enough students enrol in science subjects in Higher Education in Ghana, with proportions admitted to public universities well short of the Government’s 60% target. Significant barriers for all young people include the lack of practical scientific equipment in schools, and barriers to young women include prevailing socio-cultural attitudes, a lack of female role models and unsupportive educational environments.
KerkoCite.ItemAlsoKnownAs: 2405685:JZX3ZXZ4

FunDza launches on WhatsApp to bring reading into the lives of young South Africans - turn.io (turn, 2019)
FunDza Literacy Trust has partnered with Turn.io to launch FunDza on WhatsApp to get its already popular reading content into the hands of thousands of new readers.
Library Catalog: www.turn.io EdTechHub.ItemAlsoKnownAs: 2405685:P48BZAHG

‘They are visually impaired, not blind … teach them!’: Grade R in-service teachers’ knowledge of teaching pre-reading skills to visually impaired learners - Kao, Matiekase A.; Mzimela, Patience J. (South African Journal of Childhood Education, 2019)
Background: Teaching reading skills is the cornerstone of all learning; therefore, teachers’ adherence to this mandate is important. However, it becomes complicated and challenging if the teacher has to teach pre-reading skills to Grade R learners with visual impairments. In light of this challenge, researchers have endeavoured to determine the Technological Pedagogical and Content Knowledge (TPACK) that teachers should possess for the effective teaching of reading in classrooms with visually impaired learners.Aim: This article explores a small sample of in-service teachers’ knowledge of using Braille to teach pre-reading skills to Grade R learners with visual impairments.Setting: The study was conducted in a School for the Blind in Maseru, Lesotho, where three Grade R in-service teachers teaching learners with visual impairments were purposively sampled.Methods: This study is underpinned by Koehler and Mishra’s theory of TPACK. An interpretivist, qualitative small-scale case study approach was employed, using semi-structured interviews and classroom observations. Document analysis was also used to corroborate findings.Results: Findings reveal that although some of the participants possess a high level of technological knowledge, they tend to teach Braille as a ‘stand-alone’ skill and fail to integrate it with the teaching of other pre-reading skills to Grade R learners.Conclusion: In-service teachers showed limited knowledge of some of the essential skills for teaching pre-reading skills to Grade R learners who are visually impaired. The study calls for supportive in-service teacher education programmes that equip Grade R teachers of learners with visual impairments with the necessary skills to teach pre-reading skills.
Grade R teachers, Sesotho, Females; shortDOI: 10/ggcr5r KerkoCite.ItemAlsoKnownAs: 10.4102/sajce.v9i1.651 10/ggcr5r 2339240:P4FMJXZX 2405685:4P9K8WRJ
Keywords: Braille; Grade R Learners; Pedagogical Knowledge; Pre-Reading Skills; Technological Knowledge; Visual Impairment

Is education ready to work in data-intensive environments? - World Bank (Medium, 2019)
The availability of good data can help lead to making good decisions. This is true in education, as it is in other sectors.
KerkoCite.ItemAlsoKnownAs: 2339240:Z34TZSCR 2405685:UTLWYIC3

How The Radio Can Reach The World’s Most Vulnerable Children - Lister, Josephine (2019)
Section: article KerkoCite.ItemAlsoKnownAs: 2339240:5QJA7JLD 2405685:VXYF7938

Ethical challenges of edtech, big data and personalized learning: twenty-first century student sorting and tracking - Regan, Priscilla M.; Jesse, Jolene (Ethics and Information Technology, 2019)
With the increase in the costs of providing education and concerns about financial responsibility, heightened consideration of accountability and results, elevated awareness of the range of teacher skills and student learning styles and needs, more focus is being placed on the promises offered by online software and educational technology. One of the most heavily marketed, exciting and controversial applications of edtech involves the varied educational programs to which different students are exposed based on how big data applications have evaluated their likely learning profiles. Characterized most often as ‘personalized learning,’ these programs raise a number of ethical concerns especially when used at the K-12 level. This paper analyzes the range of these ethical concerns arguing that characterizing them under the general rubric of ‘privacy’ oversimplifies the concerns and makes it too easy for advocates to dismiss or minimize them. Six distinct ethical concerns are identified: information privacy; anonymity; surveillance; autonomy; non-discrimination; and ownership of information. Particular attention is paid to whether personalized learning programs raise concerns similar to those raised about educational tracking in the 1950s. The paper closes with discussion of three themes that are important to consider in ethical and policy discussions.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10676-018-9492-2 2339240:NEA7QTCT 2405685:8LCYHU7L

Building Stronger Education Systems: Stories of Change (Global Partnership for Education, 2019)
The Global Partnership for Education (GPE) supports close to 70 developing countries to ensure that every child receives a quality education. The featured stories in this report show the progress that developing country partners are making in getting more children, especially girls, in school and learning. The results are not only evidence of their commitment to improve education, but also of the sustained and targeted support provided by GPE. Feature stories are included from the following countries: (1) Afghanistan; (2) Benin; (3) Burkina Faso; (4) Djibouti; (5) Eritrea; (6) Ethiopia; (7) Guyana; (8) Kenya; (9) Pakistan; (10) Papua New Guinea; and (11) Sudan.
Publication Title: Global Partnership for Education KerkoCite.ItemAlsoKnownAs: 2339240:MHPT5FM3 2405685:8XCGNDGA
Keywords: Access to Education; Barriers; Developing Nations; Disadvantaged; Early Childhood Education; Economic Development; Educational Change; Educational Improvement; Educational Needs; Educational Practices; Educational Quality; Equal Education; Foreign Countries; Reading Instruction; Reading Skills; Refugees; Rural Education; Technology Uses in Education; Womens Education

Lebanon starts transformation process to digital economy (MENAFN, 2019)
) BEIRUT, Sept 13 (KUNA) – Lebanese Minister of Telecommunications Mohamed Choucair said on Friday that the government has started the transformation process to the digital economy that acquires four percent of the country's national income. Choucair, who represented Prime Minister Saad Al-Hariri at the opening ceremony to 'Digital Lebanon Conference 201
KerkoCite.ItemAlsoKnownAs: 2339240:ZMQFZ38J 2405685:H3SPNCJ8

National Digital Plan HORIZON 2025 - Office of the Head of State (Government of Democratic Republic of Congo, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:32G7WA7C 2405685:94CM3VIY

Joint Evaluation of Myanmar Non-Formal Middle School Education-Equivalency Pilot Programme - UNICEF (UNICEF, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:DJDVLBPV 2405685:E4Z8N6RR

The Impacts of Teacher Training and Parental Awareness on Kindergarten Quality in Ghana - Wolf, Sharon; Aber, John Lawrence; Behrman, Jere (Innovations for Poverty Action, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:T5RRAJCQ

Elements Shaping the South African Education System of the Future [poster] - Barends, Heidi (2019)
A poster summarising the findings of the dissertation titles 'Elements Shaping the South African Education System of the Future' (DOI: 10.5281/zenodo.3370973)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3595240 2129771:FSCTULII 2405685:77J8XQBA
Keywords: Basic Education; Education System; Foresight Study; Future Study; Future Trends; South African Education; South African Education System; _not_EdTechHub; _zenodoOTHER

Elements Shaping the South African Education System of the Future [presentation] - Barends, Heidi (2019)
A summary presentation of the dissertation titled 'Elements Shaping the South African Education System of the Future' (DOI:10.5281/zenodo.3370973)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3595232 2129771:4BH928RM 2405685:HSWKSDPH
Keywords: Actor Diagram; Basic Education; Causal Loop Diagram; Education System; Foresight Study; Future Study; Future Trends; South African Education; South African Education System; Systems Approach; _not_EdTechHub; _zenodoOTHER

What Is Agile Methodology: A Primer on Moving Fast - Edell, Patrick (AngelList Blog, 2019)
Everything you need to know about agile methodologies and its many frameworks.
KerkoCite.ItemAlsoKnownAs: 2339240:Y7NF9Q4W 2405685:ZHA5T29U

Global perspectives on assistive technology: Proceedings of the GReAT Consultation 2019, Volume B - Day 2 (World Health Organization, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:4KTX7RSQ 2405685:3DN8XRDU

Elements Shaping the South African Education System of the Future - Barends, Heidi (2019)
The South African education system is deeply unjust because a child’s place of birth, skin colour and family’s income largely determines their educational attainment. Understanding future trends and developments can assist stakeholders in planning and decision making. Better decisions could ultimately improve the education system. Therefore, this research aims to answer three questions: What trends could impact the South African education system? What opportunities and threats arise due to these trends? Who could influence the system? To address these questions, a mixed-method approach was adopted. First, conceptual systems diagrams were developed to depict the current education system and its stakeholders. Then, semi-structured expert interviews were used to identify future trends, threats and opportunities. This study found that the trends impacting South Africa broadly align with global trends. Examples include an increase in privatisation, technology in schools and climate change. More violence in schools is the main outlier. The study found that the risks related to technology and climate change are not being planned or accounted for. Similarly, violence is currently not a priority. The study also found that participants agreed on who the major stakeholders are, but disagreed on what actions stakeholders should take.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3370973 2129771:SRHYMTCJ 2405685:P5HYT2GH
Keywords: Actor Diagram; Basic Education; CLD; Causal Loop Diagram; Education System; Foresight Study; Future Study; Future Trends; South African Education System; Systems Approach; _C:China CHN; _C:Germany DEU; _C:India IND; _C:Japan JPN; _C:Nigeria NGA; _C:Pakistan PAK; _C:South Africa ZAF; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:scheme:1; _not_EdTechHub; _zenodoOTHER

Factors affecting the teachers' intention to adopt audio-visual aids in education sector of Pakistan - Iqbal, Zeeshan; Malik, Maimoona; Iqbal, Farhan (International Journal of Innovation in Education, 2019)
An emergent body of research mainly from the developing countries indicated that behavioural and cultural factors have significant influence on the adoption of technology. Based on the theoretical ...
Publisher: Inderscience Publishers (IEL) KerkoCite.ItemAlsoKnownAs: 2339240:4A7QSXZC 2339240:NI4LNR9K 2405685:NM5VETS3 2405685:NWXVQMQC
Keywords: ⛔ No DOI found

The evidence ecosystem in South Africa: growing resilience and institutionalisation of evidence use - Stewart, Ruth; Dayal, Harsha; Langer, Laurenz; van Rooyen, Carina (Palgrave Communications, 2019)
The evidence-informed approach to policy-making and implementation is, at its core, about better decisions for a better future. It is focused on the effective use of scarce resources, on avoiding harm and maximising good. It is grounded in principles of equity and equality, of accountability and transparency. Given these characteristics, for those of us who work in this field, there is arguably a moral, economic, social and political case for paying closer attention to evidence-informed decision-making ecosystems in the South. Evidence-based policy and implementation, or evidence-informed decision-making in line with the most recent thinking, is often framed from two inter-related but limited perspectives: first, it is viewed as an approach that has originated from ‘developed’ Northern countries, and second, it is conceptualised as a technical intervention. However, there has been a shift in how the approach is conceived, moving away from assumptions that it is an intervention implemented from outside, from the North, for the benefit of the South. As part of this shift, certain initiatives in Africa have gained greater momentum. It is in acknowledging that there are different ways to think (epistemic diversity) about Southern evidence-informed decision-making, that this work has arisen. It seizes on the opportunity to view evidence-informed decision-making in a new light, exploring the evidence ecosystems in the South as systems strongly influenced by, but not defined by, Northern stimuli, including, but not limited to, technical interventions. This work set out to describe the evidence ecosystem in South Africa. In doing so, it finds that the ecosystem is increasingly resilient despite some limitations. It has strong structural foundations, includes many diverse organisations, is supported by not inconsiderable investment, is enabled by growing and significant capacity, contains iterations and innovations, and last but not least, incorporates complexity that gives the ecosystem resilience. The work demonstrates, through its focus on South Africa’s evidence ecosystem, that the global movement has much to learn from the South.
Number: 1 Publisher: Palgrave KerkoCite.ItemAlsoKnownAs: 10.1057/s41599-019-0303-0 2339240:572SM7LP 2405685:HPSP9B6K

5 Ways EdTech Helps Students With Special Needs in the Classroom - Davis, Chris (ViewSonic Library, 2019)
EdTech helps students with special needs to engage with learning better than ever before. Find out how to implement EdTech as assistive technology.
Library Catalog: www.viewsonic.com Section: Education KerkoCite.ItemAlsoKnownAs: 2339240:L69ICGF3 2405685:SCWN8NNM SCWN8NNM

Using Dual Systems theory to conceptualise challenges to routine when transforming pedagogy with digital technologies - Blundell, Christopher; Lee, Kar-Tin; Nykvist, Shaun (Teachers and Teaching, 2019)
(2019). Using Dual Systems theory to conceptualise challenges to routine when transforming pedagogy with digital technologies. Teachers and Teaching: Vol. 25, No. 8, pp. 937-954.
Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 2339240:9MZUUQP9 2339240:MJVTRQD2 2405685:IESPF387
Keywords: Barriers; Case Studies; Classroom Techniques; Correlation; Educational Change; Information Technology; Learning Theories; Student Behavior; Systems Approach; Teacher Attitudes; Teacher Role; Teacher Student Relationship; Teaching Methods; Technology Integration; ⛔ No DOI found

‘Without Education You Can Never Become President’: Teenage Pregnancy and Pseudo-empowerment in Post-Ebola Sierra Leone - Menzel, Anne (Journal of Intervention and Statebuilding, 2019)
This article analyses the emergence of ‘teenage pregnancy’ as a new policy focus in post-Ebola Sierra Leone and explores how Sierra Leoneans interpret the problem of ‘teenage pregnancy’. I argue that the new policy focus is not indicative of changing or new problems. Rather, ‘teenage pregnancy’ has created opportunities for donors and the Government of Sierra Leone to continue cooperation in gender politics. At the same time, Sierra Leoneans are clearly concerned about ‘teenage pregnancy’, and many agree with sensitization campaigns that responsibilize young women and girls while downplaying structural factors that render them vulnerable to arrangements involving transactional sex.
Publisher: Routledge _eprint: https://doi.org/10.1080/17502977.2019.1612992 KerkoCite.ItemAlsoKnownAs: 10.1080/17502977.2019.1612992 2405685:MKDQ3K53
Keywords: Sierra Leone; aid and development; gender politics; neoliberalism; sexual violence; teenage pregnancy

ICT and Education for Refugees in Transit - Wahyuni, Dewi Sari; Fatdha, T. Sy Eiva (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
Refugees in transit often have no access to formal education. Indonesia as one of transit countries has allowed these community school-age children to join public school. Unfortunately, teenagers and adults do not have similar consent. As most of them are stranded for a long time to skip their basic education, there should be a bridge so that they still can catch up with their secondary or even higher education level. During their uncertain waiting time, some international and national organizations and local institutions have provided them with private classes in specific subjects. The problem is these classes are unaligned with the lesson grade in host country formal education institution, which is categorized based on learners’ ages. Moreover, they are placed in separated places (detention centre, interception, community housings) which cost time and fare to get these refugees in one education centre. The alternative solution for handling this situation is by having blended learning, a combination of online learning platform and face-to-face meeting managed by teachers both from the host country and refugees. These students although they are limited by any means, have been familiar with ICT such as Microsoft Office, Photoshop, Multimedia and Internet. The online learning platform will muddle through time and distance in order to support them to take Package A, B, C (National Elementary, Junior and Senior High School Equivalency) tests as these tests are admitted at work and further study in host country as well as their destination countries without age limitation.
Number: 2 shortDOI: 10/ggsp4n KerkoCite.ItemAlsoKnownAs: 10.35307/saltel.v2i2.27 10/ggsp4n 2339240:PWKDILWA 2405685:VU2VVUBV
Keywords: Google Scholar/ "blended learning" refugee education; RER theme_pedagogies and modalities

ICT and Education for Refugees in Transit - Wahyuni, Dewi Sari; Fatdha, T. Sy Eiva (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
Refugees in transit often have no access to formal education. Indonesia as one of transit countries has allowed these community school-age children to join public school. Unfortunately, teenagers and adults do not have similar consent. As most of them are stranded for a long time to skip their basic education, there should be a bridge so that they still can catch up with their secondary or even higher education level. During their uncertain waiting time, some international and national organizations and local institutions have provided them with private classes in specific subjects. The problem is these classes are unaligned with the lesson grade in host country formal education institution, which is categorized based on learners’ ages. Moreover, they are placed in separated places (detention centre, interception, community housings) which cost time and fare to get these refugees in one education centre. The alternative solution for handling this situation is by having blended learning, a combination of online learning platform and face-to-face meeting managed by teachers both from the host country and refugees. These students although they are limited by any means, have been familiar with ICT such as Microsoft Office, Photoshop, Multimedia and Internet. The online learning platform will muddle through time and distance in order to support them to take Package A, B, C (National Elementary, Junior and Senior High School Equivalency) tests as these tests are admitted at work and further study in host country as well as their destination countries without age limitation.
0 citations (Crossref) [2024-02-28] Number: 2 KerkoCite.ItemAlsoKnownAs: 10.35307/saltel.v2i2.27 2339240:SI4JQMQW 2405685:7WQ2J687
Keywords: Education; ICT; Refugees; Transit; ⛔ No INSPIRE recid found

The Reliability of the Wisconsin Card Sorting Test in Clinical Practice - Kopp, Bruno; Lange, Florian; Steinke, Alexander (Assessment, 2019)
The Wisconsin Card Sorting Test (WCST) represents the gold standard for the neuropsychological assessment of executive function. However, very little is known about its reliability. In the current study, 146 neurological inpatients received the Modified WCST (M-WCST). Four basic measures (number of correct sorts, categories, perseverative errors, set-loss errors) and their composites were evaluated for split-half reliability. The reliability estimates of the number of correct sorts, categories, and perseverative errors fell into the desirable range (rel ≥ .90). The study therefore disclosed sufficiently reliable M-WCST measures, fostering the application of this eminent psychological test to neuropsychological assessment. Our data also revealed that the M-WCST possesses substantially better psychometric properties than would be expected from previous studies of WCST test-retest reliabilities obtained from non-patient samples. Our study of split-half reliabilities from discretionary construed and from randomly built M-WCST splits exemplifies a novel approach to the psychometric foundation of neuropsychology.
shortDOI: 10/ggd69x KerkoCite.ItemAlsoKnownAs: 10.1177/1073191119866257 10/ggd69x 2339240:IU952GRN 2405685:GDZY9HMF

Insights on ESL Student Teachers Reflecting Collaboratively Online Shubashini Suppiah Institute of Teacher Education Gaya Campus - Lee, S; Swanto, K; Lajium, S; Suppiah, D; Suppiah, Shubashini (2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.
KerkoCite.ItemAlsoKnownAs: 2339240:7QBPDK43 2405685:5VBFZ3XT

Insights on ESL Student Teachers Reflecting Collaboratively Online Shubashini Suppiah Institute of Teacher Education Gaya Campus - Suppiah, Shubashini; Lee, S; Swanto, K; Lajium, S (2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.
KerkoCite.ItemAlsoKnownAs: 2405685:KIIH2XNR

Nudging at Scale: Experimental Evidence from FAFSA Completion Campaigns - Bird, A., Kelli; Castleman, Benjamin; Denning, Jeffrey; Goodman, Joshua; Lamberton, Cait; Rosinger, Kelly Ochs (2019)
Do nudge interventions that have generated positive impacts at a local level maintain efficacy when scaled state or nationwide? What specific mechanisms explain the positive impacts of promising smaller-scale nudges? We investigate, through two randomized controlled trials, the impact of a national and state-level campaign to encourage students to apply for financial aid for college. The campaigns collectively reached over 800,000 students, with multiple treatment arms to investigate different potential mechanisms. We find no impacts on financial aid receipt or college enrollment overall or for any student subgroups. We find no evidence that different approaches to message framing, delivery, or timing, or access to one-on-one advising affected campaign efficacy. We discuss why nudge strategies that work locally may be hard to scale effectively.
KerkoCite.ItemAlsoKnownAs: 2339240:HFPDIEFC 2405685:H6VSP7UX 2405685:VPY45H37 2534379:ZU7H9IF5
Keywords: ___working_potential_duplicate

Insights on ESL student teachers reflecting collaboratively online - Suppiah, Shubashini; Wah, (PhD), Lee Kean; Swanto, (PhD), Suyansah; Lajium, (PhD), Denis Andrew (The English Teacher, 2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.
Place: Seri Kembangan Publisher: Malaysian English Language Teaching Association (MELTA) KerkoCite.ItemAlsoKnownAs: 2405685:N9ZPHXCW 2534378:DFCJXPJ2 2534378:VI3TK6EI 2534378:VWP4487Z
Keywords: Collaboration; Distance learning; English as a second language–ESL; Linguistics; Malaysia; Problem solving; Professional development; Reflective practice; Researchers; Social research; Student teachers; Teacher education; Teaching; Web 2.0; __:import:01; __:match:final; __:matched; __:study_id:2095770; __finaldtb; ⛔ No DOI found

The tyranny of national averages - Burke, Marshall (Medium, 2019)
Marshall Burke and Apoorva Lal, AtlasAI
KerkoCite.ItemAlsoKnownAs: 2339240:T8VCAZG2 2405685:7S7TEAT5 7S7TEAT5

Policy interventions for attraction and retention of female teachers in rural secondary schools - Kamere, Isabela M.; Makatiani, M. I.; Nzau, Arthur Kalanza (Msingi Journal, 2019)
The potential role of female teachers in achieving the Education for all (EFA) and the Sustainable Development Goals, specifically on ensuring inclusive and equitable quality education and promoting life-long learning opportunities for all (Goal 4), achieving gender equality and empowering all women and girls(Goal 5 ) is well documented. Available evidence, however, suggests that attraction and retention of female teachers in secondary schools located in rural areas remains a significant and on-going challenge. In response, policy makers in Kenya have recommended three key policy interventions namely decentralization of teacher recruitment, payment of hardship allowance and provision of housing. A literature search reveals a dearth of information on the perspectives of rural educators on the effectiveness of these interventions. The paper presents findings based on one objective of a broader study which was to: Establish the views of female teachers’ and other stakeholders’ regarding the effectiveness of strategies for attraction and retention of female teachers in Makueni County. This study adopted a mixed methods design. The paper presents findings from the qualitative component of the study. Interviews were used to gather data. Based on their interpretations, the authors provide useful insights and offer suggestions on how the implementation of these policies could be improved.
Number: 2 KerkoCite.ItemAlsoKnownAs: 10.33886/mj.v1i2.103 2339240:LPDCWUDG 2405685:RTKRV2ZQ
Keywords: Attraction; female teachers; retention

Toward systematic review automation: a practical guide to using machine learning tools in research synthesis - Marshall, Iain J.; Wallace, Byron C. (Systematic Reviews, 2019)
Technologies and methods to speed up the production of systematic reviews by reducing the manual labour involved have recently emerged. Automation has been proposed or used to expedite most steps of the systematic review process, including search, screening, and data extraction. However, how these technologies work in practice and when (and when not) to use them is often not clear to practitioners. In this practical guide, we provide an overview of current machine learning methods that have been proposed to expedite evidence synthesis. We also offer guidance on which of these are ready for use, their strengths and weaknesses, and how a systematic review team might go about using them in practice.
KerkoCite.ItemAlsoKnownAs: 10.1186/s13643-019-1074-9 2405685:APRCIQMH 2486141:J73ILZH9 2486141:RNYWM2AZ
Keywords: Evidence synthesis; Machine learning; Natural language processing; _Added-ailr-2024

Sierra Leone: Economic Development Documents-National Development Plan, 2019-23 - International Monetary Fund (IMF, African Department, 2019)
ISBN: 9781498324960 ISSN: 1934-7685 Issue: 218 Publisher: INTERNATIONAL MONETARY FUND Volume: 2019 KerkoCite.ItemAlsoKnownAs: 10.5089/9781498324960.002.A001 2339240:6RP4BCNR 2405685:LICLRGV3

Sierra Leone : Economic Development Documents-National Development Plan, 2019-23 - International Monetary Fund. African Dept. (2019)
The Government of Sierra Leone’s new Medium-term National Development Plan (MTNDP) 2019–2023 has been founded on a strong political commitment to deliver devel-opment results that would improve the welfare of Sierra Leone’s citizens. The plan charts a clear path towards 2023 en route to the goal of achieving middle-income status by 2039 through inclusive growth that is sustainable and leaves no one behind. For the next five years, the Free Quality School Education Programme is the government’s flagship programme to provide a solid base to enhance human capital development and to facilitate the transformation of the economy.
9781498324960/1934-7685 KerkoCite.ItemAlsoKnownAs: 2405685:DJ4XD4HB

The Future Use of Technology in Education and Learning in the Commonwealth - Unwin, Tim (The Round Table, 2019)
Modern Information and Communication Technologies (ICTs) have increasingly been used in education systems and for learning across the world over the last quarter of a century, and are frequently seen as being an important means of delivering the Sustainable Development Goals (SDGs), especially SDG4. However, rhetoric about their potential benefits has often led to uncritical adoption of inappropriate and costly technologies, that have not benefited the poorest and most marginalised. This contribution explores likely uses of such technologies in Commonwealth education systems in the future, and what needs to be done so that these do indeed benefit everyone, rather than just the privileged with access to the latest technologies. It begins with an overview of existing Commonwealth initiatives, and then explores how ICT use for learning throughout the life-cycle is likely to change over the next decade. The next section suggests how Commonwealth organisations can best support governments and citizens in ensuring equitable distribution of relevant learning opportunities and mitigating the negative aspects of technology use. In conclusion, it advocates for the need to focus especially on the poorest and most marginalised, and it highlights the challenges of a future in which machines and humans are ever more intertwined.
shortDOI: 10/gf9kk8 KerkoCite.ItemAlsoKnownAs: 10.1080/00358533.2019.1634891 10/gf9kk8 2339240:LBNLWGJJ 2405685:EJDDKWXT
Keywords: Commonwealth; Education; Qualitative Research; commentary; future; marginalisation; technology

"You give a little of yourself": family support for children's use of an IVR literacy system - Madaio, Michael A.; Kamath, Vikram; Yarzebinski, Evelyn; Zasacky, Shelby; Tanoh, Fabrice; Hannon-Cropp, Joelle; Cassell, Justine; Jasinska, Kaja; Ogan, Amy (Proceedings of the 2nd ACM SIGCAS Conference on Computing and Sustainable Societies, 2019)
Low levels of childhood literacy in global contexts may be mitigated by educational technologies, however, these technologies often rely on parents of sufficient literacy to effectively support their children. Given low levels of adult literacy in many low-resource contexts, we investigate the nature of low-literate adult support for children's use of a literacy technology designed to foster early literacy precursors. We deployed an interactive voice response (IVR) system with 38 families in a rural village in Côte d'Ivoire using the IVR for 5 weeks in their homes. Using call log data and grounded theory analyses of IVR observations and interviews, we find evidence that families leverage complex support networks where family members support children's use of the IVR in different ways, via a collective network of intermediaries. These results suggest opportunities to scaffold low-literate family supporters for educational technologies.
KerkoCite.ItemAlsoKnownAs: 10.1145/3314344.3332504 2339240:EGC7YGBE 2405685:BLAYAKS6
Keywords: HCI4D; IVR; ed tech; literacy; tech intermediaries

An exploration of agency in the localisation of open educational resources for teacher development - Wolfenden, Freda; Adinolfi, Lina (Learning, Media and Technology, 2019)
This study examines the practice of adaptation and translation (localisation) of Open Educational Resources (OER). It employs a sociocultural perspective to focus on the experiences of practitioners (localisers) who undertook the localisation of a suite of 125 OER created as part of a teacher professional development programme in India. This localisation process generated eight unique versions of the OER in five languages. Drawing on project reports, practitioner interviews and analysis of the adapted OER, the study explores how localisers created meaning for the task, the situational and linguistic factors that influenced and mediated their decisions to adapt the materials – or not – and the skills and experiences that emerged through the process. Although the findings revealed that changes to the materials were limited, suggesting that enacting localisation is more difficult than perhaps suggested by OER proponents, the analysis indicated forms of localisers’ emerging professional agency through this endeavour.
Publisher: Routledge _eprint: https://doi.org/10.1080/17439884.2019.1628046 Extra URL: https://doi.org/10.1080/17439884.2019.1628046 KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2019.1628046 2405685:D4SI9BWU 2534378:ALXXMXLY 2534378:ZPP9MH8V
Keywords: India; Open educational resources (OER); __:import:01; __:match:final; __:matched; __:study_id:2457357; __finaldtb; localisation; professional agency

The impact of Galli Galli Sim Sim on Indian preschoolers - Borzekowski, Dina L. G.; Singpurwalla, Darius; Mehrotra, Deepti; Howard, Donna (Journal of Applied Developmental Psychology, 2019)
While educational media can affect young children's development, rigorous studies rarely occur in low and middle income countries. Using an experimental design, researchers investigated the effect of an educational television series (Galli Galli Sim Sim (GGSS), the Indian version of Sesame Street) with 1340 children in 99 preschools in Lucknow, India. Boys and girls, ages three to seven and mostly from low income households, saw 30 min of television five days a week for twelve weeks, varying how much Galli Galli Sim Sim versus other programming children watched. Assessments occurred at baseline, endline, and six weeks later. Hierarchical models showed that Galli Galli Sim Sim receptivity, an independent variable that combines exposure and recall, significantly improved literacy, numeracy, socio-emotional strategies, and nutritional knowledge. Locally-produced educational media should be encouraged as it can positively affect potential school success and child development.
shortDOI: 10/gf84g5 KerkoCite.ItemAlsoKnownAs: 10.1016/j.appdev.2019.101054 10/gf84g5 2339240:MHHA268R 2405685:ER687Z8I 4803016:WC8Z9BF8

Translation Apps: Increasing Communication with Dual Language Learners - Lake, Vickie E.; Beisly, Amber H. (Early Childhood Education Journal, 2019)
Dual language learners (DLLs) represent one of the fastest growing populations in classrooms, and yet many teachers are monolingual and not trained in English as a Second Language. Many teachers strive to create an anti-bias classroom that puts goals of diversity and equity at the center of all that they do, but are unsure of effective strategies for communicating with all students. By supporting the home language, teachers show their DLLs and native English speakers that every child’s home language is important and welcome in the classroom. Using translation apps can help teachers talk to their students, build relationships with children and families, and support bilingualism. Once teachers and children can communicate successfully, DLLs can increase their understanding of content, engagement, motivation, communication, and sense of self-esteem. The three apps discussed in this article, Speak and Translate, Microsoft Translator, and Google Translate have been shown to be helpful in facilitating interactions with children in their home language. Additional information is provided on using these apps, as well as their potential benefits and drawbacks.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10643-019-00935-7 2405685:J5V4QR7H 4042040:AR5BTB3I
Keywords: Anti-bias curriculum; Dual language learners; Technology; Translation apps

Factors affecting cloud computing adoption in the Indian school education system - Singh, Jewan; Mansotra, Vibhakar (Education and Information Technologies, 2019)
Cloud computing is becoming a leading trend worldwide, due to its enhanced reliability, scalability, flexibility, availability and processing throughput. However, the decision related to adoption of the cloud computing model is often complicated by challenges and uncertainties about the expected business value and its overall impact on the organisation. Till date, different contemporary technology acceptance theories and models have been used to test and validate adoption chances of cloud computing at organisational and individual levels. However, no experimental study has been conducted to provide a holistic evaluation of the determinants of cloud computing in the Asian world particularly in the context of the Indian school education system. Due to lack of such studies, we propose a theoretical model based on the TOE framework to explain the role of technological, organisational and environmental factors on the adoption of cloud computing in the Indian school education system. The data was collected from fifty-six 56 randomly selected secondary schools through questionnaire based survey to examine the relationship between the variables employing 5-points Likert scale. Reliability and validity measures were used to establish the quality and the usefulness of the collected data. In addition multi co-linearity test was also conducted. In order to test the research hypothesis, multiple regression analysis was conducted. The results indicate that relative advantage, compatibility, and complexity representing technological factors; top management support representing organisational factors; and competitive pressure, external expertise and attitude towards change representing environmental factors were found to have an positive and significant influence on the adoption of cloud computing services in the Indian school education system. The findings have a great significance since they can provide knowledge about cloud computing factors as well as insights and directions to the education policy planners and decision makers for successful adoption of cloud computing technology in India.
shortDOI: 10/ggjpd8 KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-019-09878-3 10/ggjpd8 2339240:CHA5JH65 2405685:LJBW3Q45

One step at a time: the effects of an early literacy text-messaging program for parents of preschoolers - York, Benjamin N.; Loeb, Susanna; Doss, Christopher (Journal of Human Resources, 2019)
Large systematic differences in young children’s home learning experiences have long-term economic consequences. Many parenting programs place significant demands on parents’ time and inundate parents with information. This study evaluates the effects of READY4K!, an eight-month-long text-messaging intervention for parents of preschoolers that targets the behavioral barriers to engaged parenting. We find that READY4K! increased parental involvement at home and school by 0.15 to 0.29 standard deviations, leading to child gains in early literacy of about 0.11 standard deviations. The results point to the salience of behavioral barriers to parenting and the potential for low-cost interventions to reduce these barriers.
Publisher: University of Wisconsin Press KerkoCite.ItemAlsoKnownAs: 10.3368/jhr.54.3.0517-8756R 2405685:UV7WIAIX
Keywords: C93; D91; I21

Integrating social media platforms into higher education pedagogy in Ghana - Appiah-Boateng, Patricia (University of Ghana, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:YTE259DI 2405685:AMGNJRAB

Connected Society: The State of Mobile Internet Connectivity 2019 - Bahia, Kalvin; Suardi, Stefano (GSMA, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:T6WZDVKT

Medium- and Long-Term Educational Consequences of Alternative Conditional Cash Transfer Designs: Experimental Evidence from Colombia - Barrera-Osorio, Felipe; Linden, Leigh L.; Saavedra, Juan E. (American Economic Journal: Applied Economics, 2019)
In 2005 the city of Bogota, Colombia, introduced three conditional cash transfer programs for secondary schooling, randomly assigning socioeconomically disadvantaged students to different payment structures. We show, through administrative data, that forcing families to save one-third of the transfer increases long-term human capital accumulation by means of additional tertiary education—which is not incentivized—, casting doubt on conditionalities as a driving mechanism. Directly incentivizing on-time tertiary enrollment does no better than forcing families to save a portion of the transfer. Whereas forcing families to save increases enrollment in four-year universities, incentivizing tertiary enrollment only increases enrollment in low-quality colleges.
KerkoCite.ItemAlsoKnownAs: 10.1257/app.20170008 2405685:Q5ED3LVK
Keywords: Education; Financial Aid; Returns to Education; Human Capital; Household Saving; Human Development; Income Distribution; Labor Productivity; Economic Development: Human Resources; Migration; Occupational Choice; Personal Finance; State and Local Government: Health; Public Pensions; Analysis of Education; Educational Finance; Skills; Welfare

Bangladesh Primary Education Annual Sector Performance Report (ASPR) 2019 - Directorate of Primary Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BCNM4PNJ 2405685:CW438FLX

Meeting the Academic and Social-Emotional Needs of Nigeria’s Out-of-School Children What works and what doesn’t for an accelerated learning program - IRC (International Rescue Committee, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:H8MY7YJY 2405685:44XRZFQA

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, E.; Laurillard, D. (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.
Number: 2 Publisher: Taylor & Francis KerkoCite.ItemAlsoKnownAs: 2339240:3R3E5UKD 2405685:IWSGHR2Y

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, Eileen; Laurillard, Diana (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.
Publisher: UCL IOE Press shortDOI: 10/gg39w8 KerkoCite.ItemAlsoKnownAs: 10.18546/LRE.17.2.04 10.18546/lre.17.2.04 10/gg39w8 2339240:8UKVPWIZ 2339240:HI8ZPSQY 2339240:IQ8CXXW6 2405685:BPEFU8Q5 2405685:G4UWRHU7 2405685:HZVTXVSX 2534378:G73NNFJ5 2534378:SB3A7XEN 2534378:XASAZC2M
Keywords: BLENDED learning; CO DESIGN MOOCS REFUGEES TEACHERS THEORY OF CHANGE; DIGITAL technology; Design; Digital technology; Education; Google Scholar/ "blended learning" refugee education; Lebanon; MASSIVE open online courses; MOOCs; Online instruction; PROFESSIONAL education; Professional development; RER theme_supporting educators; TEACHER development; __:import:01; __:match:final; __:matched; __:study_id:2095772; ___working_potential_duplicate; __finaldtb; co-design; refugees; teachers; theory of change

The EdTech Lab Series: Insights from rapid evaluations of EdTech products - Sampson, Rob; Johnson, Doug; Somanchi, Anmol; Barton, Hannah; Joshi, Ruchika; Seth, Madhav; Shotland, Marc (Central Square Foundation, 2019)
EdTechHub.ItemAlsoKnownAs: 2405685:4L2N52EL

Teaching at the Right Level (TaRL) - HundrED.org (2019)
Simple, scalable, effective and learner centered. We tailor instruction to a child with fun, level-targeted activities to enable them to learn basic numeracy. Our model is a 30-day intervention implemented one hour a day. The pillars; assess and group students by ability, use targeted instruction, employ fun and engaging learner appropriate materials and maintain strong implementation systems.
Section: innovation KerkoCite.ItemAlsoKnownAs: 2405685:Q788MU3T

How TV white space is helping bridge the digital divide - Harris, Briony (On the Issues, 2019)
How the need for reliable internet in Essex County, New York, led to a business that services the local community.
Section: Rural Broadband KerkoCite.ItemAlsoKnownAs: 2339240:5GTBVDTK 2405685:7N7JWBUX

Growth Mindset Predicts Student Achievement and Behavior in Mobile Learning - Kizilcec, René F.; Goldfarb, Daniel (Proceedings of the Sixth (2019) ACM Conference on Learning @ Scale, 2019)
Students’ personal qualities other than cognitive ability are known to influence persistence and achievement in formal learning environments, but the extent of their influence in digital learning environments is unclear. This research investigates non-cognitive factors in mobile learning in a resourcepoor context. We surveyed 1,000 Kenyan high school students who use a popular SMS-based learning platform that provides formative assessments aligned with the national curriculum. Combining survey responses with platform interaction logs, we find growth mindset to be one of the strongest predictors of assessment scores. We investigate theory-based behavioral mechanisms to explain this relationship. Although students who hold a growth mindset are not more likely to persist after facing adversity, they spend more time on each assessment, increasing their likelihood of answering correctly. Results suggest that cultivating a growth mindset can motivate students in a resource-poor context to excel in a mobile learning environment.
KerkoCite.ItemAlsoKnownAs: 10.1145/3330430.3333632 2339240:L3XGQDF9 2405685:WYTNLMM6

WhatsApp utilisation at an initial teacher preparation programme at a university of technology in South Africa - Mabaso, Nkosinomusa; Meda, Lawrence (Proceedings of the 7th Teaching & Education Conference, London, 2019)
Table of Content - Article Detail - Proceedings of the 7th Teaching & Education Conference, London
KerkoCite.ItemAlsoKnownAs: 2339240:CTUPKLXW 2405685:DMAXXRDD
Keywords: ⛔ No DOI found

WhatsApp utilisation at an initial teacher preparation programme at a university of technology in South Africa - Mabaso, Nkosinomusa; Meda, Lawrence (Proceedings of the 7th Teaching & Education Conference, London, 2019)
Table of Content - Article Detail - Proceedings of the 7th Teaching & Education Conference, London
KerkoCite.ItemAlsoKnownAs: 2339240:CTUPKLXW 2405685:DMAXXRDD
Keywords: ⛔ No DOI found

Over 6 lakh slum dwellers in Dhaka: minister - Star Online Report (The Daily Star, 2019)
Local Government Division minister Tazul Islam informs the parliament that around 6.46 lakh people are now living in around 3,394 slums in Dhaka.
KerkoCite.ItemAlsoKnownAs: 2339240:8C33Q5YU 2405685:YQPTMS7R

Improving reading and arithmetic outcomes at scale: Teaching at the Right Level (TaRL), Pratham’s approach to teaching and learning - Lakhsman, Samyukta (Revue internationale d’éducation de Sèvres, 2019)
In India, depsite a gross enrolment rate of more than 95%, performance levels remain low, particularly for children of illiterate or undereducated families. To contend with this, the “Teaching at the Right Level » project was implemented. This has taken many forms: the “camps for learning”, either repeated short term sessions (6 to 10 days), or long term sessions (30 to 50 days); and partnership arrangements with public school system authorities. The project’s methodology, attained objectives and its prospects are presented.
Publisher: Centre international d’études pédagogiques (CIEP) KerkoCite.ItemAlsoKnownAs: 2339240:IXHYXHXW 2405685:9ERHJMQM
Keywords: ⚠️ Invalid DOI; ⛔ No DOI found

Pathways to Impact: Insights from Research Partnerships in Uganda and India - Hinton, Rachel; Bronwin, Rona; Savage, Laura (IDS Bulletin, 2019)
This article sets out a perspective from the United Kingdom’s Department for International Development (DFID) on the challenges of achieving research uptake. Two country case studies are presented from India and Uganda, which explore research projects under the Economic and Social Research Council ESRC-DFID-funded Raising Learning Outcomes programme. These case studies focus on relationships between the key stakeholders that enable policy debate relevant to the funded research. They are not a direct assessment of the impact that this research has had. Rather, this article explores the messy and iterative processes that DFID advisers are engaged in within the networks that they are embedded (and those that they are not), the way that they use partnerships to access evidence and promote it into policy debate, and the other drivers that matter. This article is important as a contribution to ongoing efforts to improve the quality and usage of education evidence in low-income contexts.
Number: 1 KerkoCite.ItemAlsoKnownAs: 10.19088/1968-2019.105 2339240:JWHLVPZ9 2405685:U3THZZ5F
Keywords: Impact; Policy Engagement; Research Partnership; Research Uptake

Mapping the landscape of education research by scholars based in sub-Saharan Africa Insights from the African Education Research Database - Rose, Pauline; Downing, Pheobe; Asare, Samuel; Mitchell, Rafael (Zenodo, 2019)
This report outlines key features of education research undertaken by scholars based in sub-Saharan Africa, as represented in the African Education Research Database. The database catalogues social science research with implications for education policy and practice in sub-Saharan Africa, published in reputable journals and written by at least one researcher based in the region. In exclusively cataloguing research conducted by researchers based in sub-Saharan Africa, the African Education Research Database is a unique resource for educational development research and policy in the region.
shortDOI: 10/ggjnpx KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3242314 10/ggjnpx 2339240:PEDMUGX2 2339240:QGS6S4IS 2405685:JA5F2U7R 2405685:ZM2IB7JE
Keywords: Reviewed; _zenodoOTHER

Project Information Document (PID): Sierra Leone Free Education Project (P167897) - World Bank (World Bank Group, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:6FWAUCW5 2405685:XAKZSJBD

A primer on standardized testing: History, measurement, classical test theory, item response theory, and equating - Himelfarb, Igor (Journal of Chiropractic Education, 2019)
This article presents health science educators and researchers with an overview of standardized testing in educational measurement. The history, theoretical frameworks of classical test theory, item response theory (IRT), and the most common IRT models used in modern testing are presented.A narrative overview of the history, theoretical concepts, test theory, and IRT is provided to familiarize the reader with these concepts of modern testing. Examples of data analyses using different models are shown using 2 simulated data sets. One set consisted of a sample of 2000 item responses to 40 multiple-choice, dichotomously scored items. This set was used to fit 1-parameter logistic (PL) model, 2PL, and 3PL IRT models. Another data set was a sample of 1500 item responses to 10 polytomously scored items. The second data set was used to fit a graded response model.Model-based item parameter estimates for 1PL, 2PL, 3PL, and graded response are presented, evaluated, and explained.This study provides health science educators and education researchers with an introduction to educational measurement. The history of standardized testing, the frameworks of classical test theory and IRT, and the logic of scaling and equating are presented. This introductory article will aid readers in understanding these concepts.
KerkoCite.ItemAlsoKnownAs: 10.7899/JCE-18-22 2339240:6S5MIL7N 2405685:ZB8LXLCI

Planning for the Total Cost of Edtech Initiatives - edWeb (edWeb, 2019)
Strategic planning for edtech is an endless journey—and not just because of constantly evolving hardware and software. Upgrading infrastructure, device maintenance, and ongoing professional development, in addition to program and device costs, mean tech initiatives need permanent budget lines that take into account the total cost. In the edWebinar, “Strategic Technology Planning and Investment,” which is part of CoSN’s Empowered Superintendent series for edWeb, three superintendents who’ve been in the trenches for all aspects of district edtech plans discussed effective financial planning for technology.
KerkoCite.ItemAlsoKnownAs: 2339240:M3CJMVFE 2405685:D6RP9ZAL

Community-Based Teacher Training: Transformation of Sustainable Teacher Empowerment Strategy in Indonesia - Mardapi, Djemari; Herawan, Tutut (Journal of Teacher Education for Sustainability, 2019)
Teacher empowerment is a central issue in relation to the efforts to improve the quality of education. However, teacher empowerment will remain an abstract idea if its implementation is not supported by an appropriate strategy. The demands for a quality education will be unreciprocated if teachers do not have the opportunity to empower themselves. This research aims to investigate the teacher empowerment strategy in Indonesia, which has been conducted by employing a community-based teacher training program. This study has highlighted several research questions: What is meant by community-based training program? Why is the training program needed? Who is the target of the training program? What model has been used to implement the training? What are the results of the training that has been executed? This research was conducted from November 2018 to January 2019. The research data were collected by means of documentation studies and interviews. The data analysis was carried out quantitatively and qualitatively, where the quantitative analysis was processed based on the document study data, meanwhile the qualitative analysis was performed based on the interview data. The research results showed that community-based teacher training was transformation of teacher development strategy as a follow-up on teachers’ competency test in Indonesia. The community-based teacher training succeeded in increasing the professionalism of teachers in Indonesia, particularly in terms of implementing their pedagogical and professional competencies. The training is also successful in motivating the teachers to engage themselves in continuous learning efforts through building strong teachers’ network and working collaboratively with colleagues. Quantitatively, training was proven to increase the average of teacher competency by 23.97 (on a scale of 100). The research results are expected to provide information about the best practice in teacher coaching that is conducted massively in a national scope based on the local community so that a lifelong learning culture for teachers is established to support the development of sustainable education.
KerkoCite.ItemAlsoKnownAs: 10.2478/jtes-2019-0004 2405685:8YANT76F

Education for sustainable development in Africa: a critique of regional agendas - Tikly, Leon (Asia Pacific Education Review, 2019)
Education is often perceived in policy agendas as playing a transformative role in realising sustainable development and the SDGs on the continent. The assumption is based, however, on an insufficiently critical understanding of the historical role of education in supporting unsustainable development. The article provides a critical account of the relationship between education policy and sustainable development in Africa as an aspect of the postcolonial condition, i.e. as an aspect of the colonial legacy and of Africa’s position in relation to contemporary processes of globalisation. It is argued that if education is to play a transformative role in relation to sustainable development then education policy needs to be fundamentally re-oriented and harnessed to wider processes of economic, cultural and political transformation in the interests of social and environmental justice.
KerkoCite.ItemAlsoKnownAs: 10.1007/s12564-019-09600-5 2405685:UUXGULFV

A longitudinal study of learning, progression, and personal growth in Sierra Leone - Johnson, David; Hsieh, Jenny (University of Oxford, 2019)
EdTechHub.ItemAlsoKnownAs: 2405685:A2EVGSWW

The Influence of Teachers’ Professional Development Activities on the Factors Promoting ICT Integration in Primary Schools in Mongolia - Li, Shengru; Yamaguchi, Shinobu; Sukhbaatar, Javzan; Takada, Jun-ichi (Education Sciences, 2019)
This paper examines the influences of professional development activities on important teacher-level factors that are important for the use of Information and Communication Technology (ICT) in education for primary school teachers in Mongolia. The study utilizes the survey data collected in 2012 (n = 826) and 2016 (n = 1161) to identify the changes in factors that are important to the use of ICT in education. The study result shows that six teacher level factors that are important for the ICT integration have been improved over time through professional development activities. These are professional competency in educational use of ICT, collaboration for ICT integration, benefits on use of ICT, autonomy to innovate, recognition as a professional, and skills and practices in educational use of ICT. This provides supporting evidence to educational practitioners for the implementation of effective professional development programs to promote ICT integration in education, especially in the developing country’s context.
Number: 2 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/educsci9020078 2339240:XWWZXZ76 2405685:EENQXYD4
Keywords: ICT in education; ___working_potential_duplicate; auto_merged; education policy; educational change; factors promoting ICT integration; teacher’s professional development

Education Strategic Plan 2019–2023 - Ministry of Education, Youth and Sports, Kingdom of Cambodia (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QNB3YJ86 2405685:NBUQMD4W

Effect of M-Learning on Students' Academic Performance Mediated by Facilitation Discourse and Flexibility - Shuja, Aleema; Qureshi, Ijaz A.; Schaeffer, Donna M.; Zareen, Memoona (Knowledge Management & E-Learning, 2019)
Conventional classroom instruction had already been transformed in to electronic mode of teaching and learning. Use of mobile technology is evolving in global and local context, as in Pakistan. Gaining insights from Media Richness Theory, the study intends to examine how m-learning pedagogy, opens up avenues for students' learning and enhances their educational performance, endorsed by facilitation discourse and flexibility. In this cross-sectional study, data was collected from students in Private Universities in Lahore Pakistan. Drawing results from structural equation modelling, findings revealed that use of mobile devices is on great demand for providing flexible and discussion-oriented learning to students and lifts up their academic output. Facilitation discourse and flexibility play a robust intervening role in producing pronounced impact of m-learning on learners' effectiveness.
Publisher: Laboratory of Knowledge Management & E-Learning KerkoCite.ItemAlsoKnownAs: 2339240:9C84A8N2 2405685:HYP2M2IS
Keywords: Academic Achievement; College Students; Discussion (Teaching Technique); Distance Education; Educational Technology; Foreign Countries; Handheld Devices; Private Colleges; Productivity; Teacher Role; Technology Uses in Education; Telecommunications; ⛔ No DOI found

WhatsApp: Creating a virtual teacher community for supporting and monitoring after a professional development programme - Moodley, Maglin (South African Journal of Education, 2019)
KerkoCite.ItemAlsoKnownAs: 10.15700/saje.v39n2a1323 2339240:R7L9J4C3 2405685:HSIJJWM4

Assessment of the effectiveness of ICT on Teacher Trainees in Colleges of education. A Case of St. Monica's College of Education - Osei Frimpong, Kojo; Asare, Samuel; Caroline, Owusu-Mintah (Asian Journal of Computer Science and Information Technology, 2019)
The use of ICT in teacher training colleges has relatively improve teaching and learning. The effective use of various ICT tools such the computer, smart phones and PDAs has brought innovative ideas in teacher trainees. This study aimed at finding out the factors influencing the use of ICT tools in enhancing teaching and learning process in the various teacher training institutions in Ghana. A survey was used in order to investigate the study. It was revealed from the findings of the study that students and tutors in the various colleges of education have now accepted the use of ICT in teaching and learning process. However some students still see ICT as difficult due to various factors such as inadequate computers in the various colleges for practical tution and poor access to the internet for learning.
KerkoCite.ItemAlsoKnownAs: 2339240:DVBYU842 2405685:VRJIV787
Keywords: ⛔ No DOI found

Positive disruption: health and education in a digital age - Pathways for Prosperity Commission (2019)
Positive disruption: health and education in a digital age offers guidance on how digital technologies can be used to improve the lives of people in developing countries, while keeping a careful eye on the limitations and risks of focusing solely on hardware over people and processes. Technology is not a silver bullet and history is littered with poor investments in this area. To ensure health and education services are effective, efficient and equitable, governments need to be wise with their choices.
KerkoCite.ItemAlsoKnownAs: 2339240:GGB2D6PB 2405685:BB5GTZSI

How low cost wireless broadband networks are connecting ‘last-mile’ communities in Djibouti - International Telecommunication Union (ITU News, 2019)
By ITU News Twenty per cent of Djibouti’s homes have access to a computer, while internet access is available to just under 10 per cent of households, according to ITU Data. Within the framework of the Djibouti Vision 2035, the country has embarked on a programme to strengthen its ICT sector with a view to providing quality telecommunication services at
Section: Broadband/Network KerkoCite.ItemAlsoKnownAs: 2339240:PCSI9Z3T 2405685:P3J7K3QM

Assessing Early Childhood Fluid Reasoning in Low- and Middle-Income Nations: Validity of the Wechsler Preschool and Primary Scale of Intelligence Across Seven MAL-ED Sites - Ruan-Iu, Linda; Pendergast, Laura L.; Rasheed, Muneera; Tofail, Fahmida; Svensen, Erling; Maphula, Angelina; Roshan, Reeba; Nahar, Baitun; Shrestha, Rita; Williams, Brittney; Schaefer, Barbara A.; Scharf, Rebecca; et al. (Journal of Psychoeducational Assessment, 2019)
An adapted version of the Wechsler Preschool and Primary Scale of Intelligence—Third Edition (WPPSI-III) was administered to assess cognitive functioning among 1,253 5-year-old children from the Malnutrition and Enteric Disease (MAL-ED) study—an international, multisite study investigating multiple aspects of child development. In this study, the factor structure and invariance of the WPPSI-III were examined across seven international research sites located in Bangladesh, Brazil, India, Nepal, Pakistan, South Africa, and Tanzania. Using a multiple indicator multiple cause (MIMIC) modeling approach, the findings supported the validity of a fluid reasoning dimension (comprised of block design, matrix reasoning, and picture completion subscales) across each of the seven sites, although the scores were noninvariant. Accordingly, these scores are recommended for research purposes and understanding relationships between variables but not for mean comparisons or clinical purposes.
shortDOI: 10/ggd57h KerkoCite.ItemAlsoKnownAs: 10.1177/0734282919850040 10/ggd57h 2339240:24DRAS7L 2405685:JVQJPXK3

On Tipping Points and Nudges: Review of Cass Sunstein's How Change Happens - Brescia, Raymond H. (2019)
In How Change Happens, Cass Sunstein explores the mechanisms through which social change can occur, the triggers that can cause it, and the pitfalls along the road to change. For Sunstein, small influences, which arise through what he has called “nudges,” can have large impacts, particularly where they indicate that support for existing norms has fallen. When this occurs, it can reveal hidden preferences that might have existed all along, but individuals were discouraged from making them public because of the existence of those norms. Once support for an existing norm begins to disappear, it can create a tipping point and then a “norm cascade”: when support for a new norm takes hold securely in society. In recent years, several works have appeared that have attempted to explain the sources of social change by looking at examples of successful campaigns and trying to divine the sources of such successes. Sunstein offers a different perspective. He provides more of a theoretical view on the sources of social change, not just identifying the levers that can bring it about but also some guidance on how to utilize them. It is a welcome addition to the scholarship on social change and stands as an elegant and insightful complement to some of the other, recent and more inductive scholarship on the subject. As a way to test Sunstein’s theory of social change, this review asks whether that theory can help explain recent developments, namely, the victory of the marriage equality campaign and the rise of a new and emboldened white nationalism in the wake of the election of Donald Trump to the U.S. presidency. As a review of these phenomena shows, Sunstein’s theory of change helps to provide insights into how such change came about, but, it also raises more questions. Indeed, questions still linger, like when is a nudge enough, can we identify what will make something “tip”? Nevertheless, Sunstein offers deep insights into the inner workings of social change and how norm entrepreneurs can understand not just how change happens but also how to bring it about.
KerkoCite.ItemAlsoKnownAs: 2339240:9ULKIFSJ 2405685:HDU54ARW
Keywords: Nudges; Social Change

A systematic review of personalized learning: comparison between E-Learning and learning by coursework program in Oman - Tawafak, Ragad; Romli, Awanis; Iqbal Malik, Sohail; Alnaseeri, Mohanaad; Alfarsi, Ghaliya (International Journal of Emerging Technologies in Learning (iJET), 2019)
There is a need for several applications and technologies in the higher education institutions in Oman to enhance the educational process. This systematical study investigates the simultaneous influence of technology implementation with e-learning and traditional coursework program instruction on the enhancement and development of assessment method for undergraduates in different programs. This paper aims to analyze the current articles that handle with the learning process and compare between the understanding and acceptance of E-Learning mechanism and traditional coursework method of teaching for improving assessment method and evaluation of academic performance. The method works on the benefits of increasing E-Learning process for educational skills as an assistance tool with faculty material and class discussion. In this study, surveys were distributed to two different universities and college in Oman to assess their satisfaction of learning model. The findings of this paper assisted the model that may help to improve both the teaching method and academic performance of student learning outcomes.
KerkoCite.ItemAlsoKnownAs: 10.3991/ijet.v14i09.10421 2339240:7WIRDBU5 2405685:NW3WGQ5N

Unlocking Talent Through Technology Malawi - VSO (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:5A6J5JZU 2405685:LPRCAQI5

Upgrading the ICT questionnaire items in PISA 2021 - Lorenceau, Adrien; Marec, Camille; Mostafa, Tarek (2019)
This paper explains the rationale for updating the OECD Programme for International Student Assessment (PISA) 2021 questionnaire on Information and Communication Technology (ICT) and shows how it covers policy topics of current relevance. After presenting key findings based on previous ICT-related PISA data, the paper provides a summary of the PISA 2021 ICT framework guiding the development of the questionnaire. The paper then describes the process followed by the OECD/PISA secretariat for the development of the PISA 2021 ICT questionnaire items. The paper concludes by drawing some lessons that would inform future development of this instrument.
shortDOI: 10/ggjtph KerkoCite.ItemAlsoKnownAs: 10.1787/d0f94dc7-en 10/ggjtph 2339240:ZALQGM98 2405685:HAXV82VZ

Literature search protocol for the Evidence hub: Education partnerships between the state and non-state sector. - Rose, P; Downing, P (2019)
This methodological note provides an overview of a joint project to catalogue the research evidence on collaborations between the state and non-state sector in education in low income, lower-middle and upper-middle income countries. This document outlines the search protocol for the literature search, data extraction, and the development of the database.
shortDOI: 10/ggkzr2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.2677613 10/ggkzr2 2339240:FTG4QDZF 2405685:CA7UBFY3
Keywords: Secondary Review; _zenodoOTHER

“He is suitable for her, of course he is our relative”: a qualitative exploration of the drivers and implications of child marriage in Gezira State, Sudan - Dean, Laura; Obasi, Angela; Sony, Asma El; Fadul, Selma; Hassan, Hanaa El; Thomson, Rachael; Tolhurst, Rachel (BMJ Global Health, 2019)
Introduction Child marriage is a fundamental development challenge for women and girls, with significant negative health and social outcomes. Sudan has a high rate of child marriage, with 34% of women aged 20–24 married before their 18th birthday. Since limited preventive interventions exist, we aimed to inform the evidence base to strengthen strategic action, using mixed qualitative methods to enhance study credibility. This study is the first to conduct a rigorous qualitative examination of the drivers of child marriage from the perspective of key stakeholders involved in marriage decision making within Sudan, and makes a significant contribution towards global knowledge by developing an evidence-based conceptual framework. Methods Initially, we completed 14 focus group discussions separated by gender with mothers, fathers, and girls married as adolescents, and 23 key informant interviews. We then used a critical incident case study approach to explore 11 ‘cases’ of child marriage (46 interviews). Results Findings indicate that gendered social norms and values, underpinned by religious beliefs and educational accessibility, interconnect to shape marriage decisions. In this context, many child marriages are triggered by an intrakinship proposal and further enabled by the relative lack of autonomy and influence of girls and women in marriage decision-making processes. Discussion Interconnected drivers demand context-specific holistic and multisectoral approaches, which should include simultaneous strategies to expand access to education, health services and livelihood opportunities, and evoke legal change, and participatory social and attitudinal processes that include the engagement of religious leaders and men.
Publisher: BMJ Specialist Journals Section: Research KerkoCite.ItemAlsoKnownAs: 10.1136/bmjgh-2018-001264 2339240:CZMCDL8D 2405685:YWXI8CIJ
Keywords: child health; qualitative study

Do children benefit from internet access? Experimental evidence from Peru - Malamud, Ofer; Cueto, Santiago; Cristia, Julian; Beuermann, Diether W. (Journal of Development Economics, 2019)
This paper provides experimental evidence for the impact of home internet access on a broad range of child outcomes in Peru. We compare children who were randomly chosen to receive laptops with high-speed internet access to (i) those who did not receive laptops and (ii) those who only received laptops without internet. We find that providing free internet access led to improved computer and internet proficiency relative to those without laptops and improved internet proficiency compared to those with laptops only. However, there were no significant effects of internet access on math and reading achievement, cognitive skills, self-esteem, teacher perceptions, or school grades when compared to either group. We explore reasons for the absence of impacts on these key outcomes with survey questions, time-diaries, and computer logs.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jdeveco.2018.11.005 2339240:DR36TXTM 2405685:RNJDQM5M
Keywords: Academic achievement; Cognitive skills; Digital skills; Education; Experimental; Internet access; Technology

Policy adoption of learner-centred pedagogy in Rwanda: A case study of its rationale and transfer mechanisms - van de Kuilen, Hester S.; Altinyelken, Hulya Kosar; Voogt, Joke M.; Nzabalirwa, Wenceslas (International Journal of Educational Development, 2019)
This study explores why and how learner-centred pedagogy (LCP) as a policy has been adopted in Rwanda, despite ample evidence of the failure of LCP in developing countries. The case of Rwanda, as a late adopter, shows that at this stage of pedagogy diffusion the influence of global mechanisms and actors has been amplified. This study draws upon interviews with key stakeholders and relevant documents during the 2011–2016 period. The transfer process is examined by analysing the rationale offered and mechanisms deployed by the Rwandan government and aid agencies.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2019.03.004 2405685:Y8VHDCAP
Keywords: Competence-based education; Curriculum reform; Education policy transfer; Learner-centred pedagogy; Policy adoption; Rwanda

Channeling Fisher: Randomization Tests and the Statistical Insignificance of Seemingly Significant Experimental Results* - Young, Alwyn (The Quarterly Journal of Economics, 2019)
I follow R. A. Fisher'sThe Design of Experiments (1935), using randomization statistical inference to test the null hypothesis of no treatment effects in a comprehensive sample of 53 experimental papers drawn from the journals of the American Economic Association. In the average paper, randomization tests of the significance of individual treatment effects find 13% to 22% fewer significant results than are found using authors’ methods. In joint tests of multiple treatment effects appearing together in tables, randomization tests yield 33% to 49% fewer statistically significant results than conventional tests. Bootstrap and jackknife methods support and confirm the randomization results.
KerkoCite.ItemAlsoKnownAs: 10.1093/qje/qjy029 2339240:G2QYJFDN 2405685:P6MR9BF6

A Conceptual Model for Measuring and Supporting Self-Regulated Learning using Educational Data Mining on Learning Management Systems - Araka, Eric; Maina, Elizaphan; Gitonga, Rhoda; Oboko, Robert (2019 IST-Africa Week Conference (IST-Africa), 2019)
Self-Regulated Learning (SRL) is a field in educational psychology that as attracted tremendous research studies from various communities including ICTs. Recent studies and meta-analysis have greatly contributed to the domain knowledge that the use SRL strategies boost academic performance for learners. Despite these developments in SRL, our understanding on the tools and instruments to measure SRL in online learning environments is limited as the use of traditional tools developed for face-to-face classroom settings are still used to measure SRL on e-learning systems. Additionally, most of these studies focus on SRL on Massive Open Online Course (MOOC) environments and only analyse SRL strategies with limited attention to the scaffolds or interventions employed to stimulate growth of SRL skills in learners. The modern Learning Management Systems (LMS) such as Moodle allow storage of datasets on student activities. Consequently, it is possible to use Educational Data Mining (EDM) to extract learner patterns which can be used to support SRL and explore how SRL strategies change over time and inform the instructor. In view of this, the research examines the current SRL measurement and promotion tools for e-learning environments and proposes a conceptual model grounded on EDM for implementation as a solution to measuring and promoting SRL strategies for learners within LMS.
ISSN: 2576-8581 KerkoCite.ItemAlsoKnownAs: 10.23919/ISTAFRICA.2019.8764852 2339240:VAYVYVZ9 2405685:IGGGX8LC
Keywords: Data mining; Electronic learning; Instruments; Interventions; Learning Management systems; Learning management systems; Measurement and Promotion; Online learning; Process control; Scaffolds; Self-Regulated Learning; Software agents; Tools; e-learning

Technology-Mediated Learning Theory - Bower, Matt (British Journal of Educational Technology, 2019)
Technology-enhanced learning research, such as that relating to the use of online technologies in formal learning contexts, is sometimes criticised for being under-theorised. This paper draws together areas of research and theory that have previously been somewhat separately treated, to support the integrated analysis and research of situations where technology mediates learning. First, key areas of research and theory relating to technology-mediated learning are introduced, along with their associated conceptual underpinnings and assumptions, in terms of premises. These areas are then explained with relation to one another regarding how they can be used to holistically understand learning in contexts where technology mediates learning. The implications of the theoretical concepts are discussed in terms of the future conduct of technology-mediated learning research, as well as the scope and conditions under which the theorisations apply.
Publisher: Wiley-Blackwell KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12771 2339240:DUA7DI6P 2405685:48HFJPQV
Keywords: Educational Technology; Electronic Learning; Learning Theories; Meta Analysis; Technology Integration; Technology Uses in Education

National Policy on Information and Communication Technologies (ICT) in Education - Federal Ministry of Education (Federal Government of Nigeria, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:9MKT5TJD 2405685:AIGIA8UL

Connecting the Last Mile, a Fundamental of Digital Transformation - Garba, Aminata A. (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:NVSNZNY9 2405685:69ZV4LDK

Summative GPE country program evaluation - Thompson, Dale E (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:6QEDUC5K 2405685:FCYV6JLI 4803016:ET9CKE5Z

Capturing cost data: a first-mile problem - Holla, Alaka (2019)
Before we bought our house, my husband and I knew the price. The real estate agent wasn’t allowed to give us a back-of-the-envelope estimate right at the end of the process. She wasn't allowed to just declare that the house was low cost, affordable, or sustainable for our budget. We ...
KerkoCite.ItemAlsoKnownAs: 2339240:6P53FYVF 2405685:DNBLYQQA

The Need For Bilingual Education In Afghanistan – OpEd - Hatsaandh, Abdul Hamid (Eurasia Review, 2019)
Although Afghanistan a linguistically diverse country, yet only two languages, Pashto and Dari, are used as mediums of instruction in schools. Bilingual education is, so far, alien to Afghanistan. …
KerkoCite.ItemAlsoKnownAs: 2405685:K6IS2ZXF 4042040:VEMTNZGC

L1-based multilingual education in the Asia and Pacific region and beyond - Benson, Carol; Kirkpatrick, Andy; Liddicoat, Anthony J. (The Routledge International Handbook of Language Education Policy in Asia, 2019)
This must-have handbook offers a comprehensive survey of the field. It reviews the language education policies of Asia, encompassing 30 countries sub-divided by regions, namely East, Southeast, South and Central Asia, and considers the extent to which these are being implemented and with what effect. The most recent iteration of language education policies of each of the countries is described and the impact and potential consequence of any change is critically considered. Each country chapter provides a historical overview of the languages in use and language education policies, examines the ideologies underpinning the language choices, and includes an account of the debates and controversies surrounding language and language education policies, before concluding with some predictions for the future.
KerkoCite.ItemAlsoKnownAs: 10.4324/9781315666235-3 2405685:RGBXIMBH 4042040:IP29C89Y

Language Education Policy in Vietnam - Nguyen, Mai; Nguyen, Van Huy (The Routledge International Handbook of Language Education Policy in Asia, 2019)
This chapter provides an overview of past and current language education policies in Vietnam. Our reviews and critical discussions centre on state rules and regulations regarding the teaching and learning of Vietnamese, ethnic minority languages, and foreign languages. Historically speaking, language education policy in Vietnam has been largely contingent on the country’s changing political, social, and economic circumstances. Notably, current language education policy reflects the predominant status of Vietnamese as the medium of instruction across school levels. Ethnic minority language education has also received substantial policy attention, although its enactment leaves considerable room for improvement. Foreign language education policy prioritises English given its status as an international language, while also encouraging the teaching and learning of other languages. The chapter concludes with predictions and implications for future development with regard to the role and status of these relevant languages.
KerkoCite.ItemAlsoKnownAs: 2339240:4VB42GR4 2405685:IXJCZC8Y

IDENTIFICAÇÃO DO MODELO DE NEGÓCIO DE UMA START-UP/TIC: ESTUDO DE CASO NA EMPRESA GEEKIE - Lulia Filho, Herivelto; Turri, Silvia Novaes Zilber; Silva, Eduardo Corneto; Santos, Edna de Souza Machado (Investigação Científica nas Ciências Humanas e Sociais Aplicadas 3, 2019)
This study does not only understand the state of the art of the startups, but also understand how a small company of technology-based structure, shape its business model to grow and strengthen their business. For this this article has how objective of research, identify and describe the business model of a Startup/ICT Brazilian that work in the area of the education. It was used the concepts of case study, when analyzing the company Start-up/ICT Geekie, but will be used only secondary data, being this research a documentary research. The results show that the adaptive learning platform Start-up/ICT Geekie offers innovative service, personalizing and customizing education schools where works. The business model creates value for students, teachers and schools. Limitations of this article are in not obtaining primary data direct in the Geekie company and have only one company as study focus which limits the understanding of the business model of firms in the education sector.
KerkoCite.ItemAlsoKnownAs: 10.22533/at.ed.69219160413 2339240:D9EVHTG4 2405685:V6X4436E

Do higher salaries yield better teachers and better student outcomes? - Cabrera, José María; Webbink, Dinand (Journal of Human Resources, 2019)
We study the effects of a policy aimed at attracting more experienced and better qualified teachers in primary schools in disadvantaged neighborhoods in Uruguay. Teachers in these schools could earn higher salaries, and more experienced teachers are given priority in choosing teaching positions. Eligibility for the program was based on a poverty index with a cutoff rule. Estimates from regression discontinuity models show that the policy successfully led to ‘hiring experience from other schools’, and also increased tenure. Overall, the effect on student outcomes was small. We rationalize this result by showing that the program may have increased experience in ways that are not strongly associated with improved student outcomes. Consistent with this, we do find achievement gains for students in schools that saw a reduction in the share of very inexperienced teachers. The results underscore that increases in teacher pay may only improve student outcomes if it increases those teacher characteristics that actually improve student outcomes.
Publisher: University of Wisconsin Press KerkoCite.ItemAlsoKnownAs: 10.3368/jhr.55.4.0717-8911R3 2339240:7TS6UAPR 2405685:IIE4HRSX
Keywords: I2; J24; disadvantaged students; student performance; teacher experience; teacher salaries

Malawi Economic Outlook - African Development Bank (African Development Bank - Building today, a better Africa tomorrow, 2019)
Recent macroeconomic and financial developments Growth in Malawi’s economy decelerated in 2020 to 1.7% from 5.7 % in 2019. The slowdown in GDP growth was driven by the outbreak of COVID–19, which necessitated a partial lockdown of the economy, resulting in subdued economic activities—mainly in tourism, the accommodation and food subsectors, transportation, and agriculture. Other sectors affected by disruptions from the COVID–19 pandemic disruptions were manufacturing and mining and quarrying.
Publisher: African Development Bank Group KerkoCite.ItemAlsoKnownAs: 2339240:QAWBXWAY 2405685:XKHR65LI

The impact of an educational media intervention to support children’s early learning in Rwanda - Borzekowski, Dina L. G.; Lando, Agnes Lucy; Olsen, Sara; Giffen, Lauren (International Journal of Early Childhood, 2019)
Children in developing countries often lack sufficient support for early learning skills prior to beginning school. This research evaluates an educational media intervention using an animated cartoon program, Akili and Me. The program was originally created in Tanzania to teach early learning skills. This program was adapted in content and language use in this study in Rwanda. The two-week intervention involved primary school students (mean age = 7.1 years) who were randomized into two groups (intervention and comparison group). The intervention group viewed one Ankit and Me episode a day for five days. This viewing was repeated the following week. Similarly, the comparison watched the same amount of television but the content consisted of local popular programs. Baseline and follow-up assessments evaluated 10 areas of early learning, using an adaptation of the International Development and Early Learning Assessment (IDELA), and also children’s media receptivity. At follow-up, children in the intervention program, Akili and Me, had significantly higher scores for counting, number recognition, shape knowledge, letter identification, color identification, body part recognition, health knowledge, and vocabulary. The analyses provide promising evidence that locally produced educational media interventions can impact early learning skills, even among children living in resource-poor communities.
KerkoCite.ItemAlsoKnownAs: 10.1007/s13158-019-00237-4 2339240:5UZ7CZS4 2405685:VT6DTZZJ

Gauging the E-Readiness for the Integration of Information and Communication Technology Into Pre-Tertiary Education in Ghana: An Assessment of Teachers' Technological Pedagogical Content Knowledge (TPACK) - Gyaase, Patrick Ohemeng; Gyamfi, Samuel Adu; Kuranchie, Alfred (International Journal of Information and Communication Technology Education (IJICTE), 2019)
Countries are investing in information and communication technology (ICT) infrastructure and educating their citizens for effective ICT utilization. The attainment of the anticipated benefits hinges on effective integration of ICT in various levels of education. Effective integration of ICT requires...
shortDOI: 10/ggjtn5 KerkoCite.ItemAlsoKnownAs: 10.4018/IJICTE.2019040101 10/ggjtn5 2339240:DI3QR5XW 2405685:B5VHAXKP

Rigorous large-scale educational RCTs are often uninformative: Should we be concerned? - Lortie-Forgues, Hugues; Inglis, Matthew (Educational Researcher, 2019)
There are a growing number of large-scale educational randomized controlled trials (RCTs). Considering their expense, it is important to reflect on the effectiveness of this approach. We assessed the magnitude and precision of effects found in those large-scale RCTs commissioned by the UK-based Education Endowment Foundation and the U.S.-based National Center for Educational Evaluation and Regional Assistance, which evaluated interventions aimed at improving academic achievement in K?12 (141 RCTs; 1,222,024 students). The mean effect size was 0.06 standard deviations. These sat within relatively large confidence intervals (mean width = 0.30 SDs), which meant that the results were often uninformative (the median Bayes factor was 0.56). We argue that our field needs, as a priority, to understand why educational RCTs often find small and uninformative effects.
Publisher: American Educational Research Association KerkoCite.ItemAlsoKnownAs: 10.3102/0013189X19832850 2339240:D96NKMSM 2405685:5ZWZTBBI

Challenge and srivers of over-Enrollment in the early years of primary school in Uganda - Weatherholt, Tara; Jordan, Rachel; Crouch, Luis; Barnett, Ed; Pressley, Jennifer (International Journal of Early Childhood, 2019)
Consistent over-enrollment, together with low official repetition rates, in the early years of school indicates inaccurate reporting of repetition, which may mask the reasons for low primary school completion. Actual repetition rates may be higher and pose issues for teachers through overcrowding of classrooms and issues for governments through inefficient education systems. This research explores repetition rates of students in Primary 1 in Uganda and considers the implications for efficiency and quality of education for the early years of school. The sample comprised 1440 students in Primary 1 classrooms in 120 schools. Interviews were conducted with 1318 caregivers of randomly selected students and 1439 teachers of the same students, and official records from 118 schools were examined to compare age and repetition rates. Findings showed that caregiver- and teacher-reported repetition is much higher than officially reported by schools; that repetition is strongly linked to non-attendance in pre-primary schooling; and that caregivers reported more over-age students, fewer target-age students, and more under-age students than official school records. Policy implications include the need for dialogue around repetition rates and the possible efficiency effects of less-costly, pre-primary education on the total primary schooling cycle.
KerkoCite.ItemAlsoKnownAs: 10.1007/s13158-019-00238-3 2339240:3WMYLF8F 2405685:975JWM6R 4656463:2HX448CB
Keywords: Early childhood; Education efficiency; Low-income countries; Pre-primary education; Repetition

A Tablet based tool to aid learning of mathematics for Basic 1 & 2 pupils in Berekuso - Dotse, Etonam. Y. (Ashesi University, 2019)
EdTechHub.ItemAlsoKnownAs: 2405685:9K498IG7

Using technology to bring education to the most remote areas - Global Partnership for Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:CV6J6IEN 2405685:Q6H4DRVL

Summative GPE country program evaluation - GPE (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:LE4APHVD 2405685:BVBDM9S7

Making a difference in the real world? A meta-analysis of the quality of use-oriented research using the Research Quality Plus approach - MacLean, Robert; Sen, Kunal (Research Evaluation, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1093/reseval/rvy026 2405685:3ZCA5Q9I 2405685:RQH3MJ5X 2534378:937GVQ39
Keywords: ___working_potential_duplicate

Plano Estrategico de Educacao: 20ª Reunião Anual de Revisão, 2019 - Ministerio da Educacao e Desinvolvimento Humano (Republica de Mocambique, 2019)
EdTechHub.ItemAlsoKnownAs: 2405685:NR68YRDT

Ghana Beyond Aid Charter and Strategy Document (Draft) - Ministry of Education, Ghana (Ministry of Education, Ghana, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:DDRYSZAJ 2405685:H6JD3GSF

Disrupting education? Experimental evidence on technology-aided instruction in India - Muralidharan, Karthik; Singh, Abhijeet; Ganimian, Alejandro J. (American Economic Review, 2019)
We study the impact of a personalized technology-aided after-school instruction program in middle-school grades in urban India using a lottery that provided winners with free access to the program. Lottery winners scored 0.37 sigma higher in math and 0.23 sigma higher in Hindi over just a 4.5-month period. IV estimates suggest that attending the program for 90 days would increase math and Hindi test scores by 0.6 sigma and 0.39 sigma respectively. We find similar absolute test score gains for all students, but much greater relative gains for academically-weaker students. Our results suggest that well-designed, technology-aided instruction programs can sharply improve productivity in delivering education.
shortDOI: 10/ggqfkz KerkoCite.ItemAlsoKnownAs: 10.1257/aer.20171112 10/ggqfkz 2339240:2URYXAL4 2339240:4YAVCBCF 2339240:7V3XB7ZJ 2339240:8LAH5EZS 2339240:FPI5PFGU 2339240:QRHQXRYZ 2339240:U2V8LTLL 2339240:V85IRLNH 2405685:7WM44UJQ 2405685:AJVTKPNE 2405685:EKZSBGYG 2405685:EWWJF7S6 2405685:EZDRM9UV 2405685:HDWKAHGN 2405685:MADAMGDT 2405685:N2HAMNQ9 2405685:SYASQJ2L 2405685:YFXKBCTF 2534378:JMN7CGMF
Keywords: Analysis of Education; Returns to Education; Education: Government Policy; Human Capital; Human Development; Income Distribution; Labor Productivity; Economic Development: Human Resources; Migration; Occupational Choice; Quality: H; Relevance: H; Skills; _THEME: Teacher Professional Development; ___working_potential_duplicate; ⛔ No DOI found

Mapping Teacher Distribution Analysis with Digitation Technology Implementation to Improve Education Management in Bengkulu City - Nirwana, Nirwana; Vatresia, Arie; Utama, F. P. (Atlantis Press, 2019)
Embedded technology in education management is one of the most important things as an aid for Education Department. Not only help in learning process, the use of technology has been also used in many part of education to improve learning process. In this paper, we proposed the idea of mapping the digitation of High School (SMA) in Bengkulu city to manage...
ISSN: 2352-5398 KerkoCite.ItemAlsoKnownAs: 10.2991/icetep-18.2019.49 2405685:W6VBYJPS 2486141:QIPGVMGF

Tayari Parent Engagement Pilot Intervention Summary Report - RTI International (RTI International, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:9ZPSTQTV 2405685:7KA8C2XD

AENN Data Utilisation + Dashboard Co-creation Workshop Report - Viamo (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:W3YICELF

Unbundling the 13 million out-of-school children in Nigeria - Ishaku, Joseph; Oraka, Onome (Southern Voice (Nigeria), 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:RNM3ZT93

Cyclone Idai: On the Ground Data from Mozambique - Becker, Nick (GeoPoll, 2019)
GeoPoll has conducted an SMS survey in Mozambique to reach those affected by Cyclone Idai. Data from Sofala province and Beira city following the cyclone.
EdTechHub.ItemAlsoKnownAs: 2405685:BNT75G27

The Politics of Education in Developing Countries: From Schooling to Learning - Hickey, Sam; Hossain, Naomi (Oxford University Press, 2019)
Why have many developing countries that have succeeded in expanding access to education made such limited progress on improving learning outcomes? There is a growing recognition that the learning crisis constitutes a significant dimension of global inequality and also that educational outcomes in developing countries are shaped by political as well as socio-economic and other factors. The Politics of Education in Developing Countries focuses on how politics shapes the capacity and commitment of elites to tackle the learning crisis in six developing countries: Bangladesh, Cambodia, Ghana, Rwanda, South Africa, and Uganda.The problem of education quality is serious across the Global South. The Politics of Education in Developing Countries: From Schooling to Learning deploys a new conceptual framework-the domains of power approach-to show how the type of political settlement shapes the level of elite commitment and state capacity to improving learning outcomes. The domain of education is prone to being highly politicized, as it offers an important source of both rents and legitimacy to political elites, and can be central to paradigmatic elite ideas around nation-building and modernity. Of particular importance is the relative strength of coalitions pushing for access as against those focused on issues of higher quality education. This book concludes with a discussion of entry points and strategies for thinking and working politically in relation to education quality reforms and critical commentaries.
KerkoCite.ItemAlsoKnownAs: 2339240:ZZAYYIKN 2405685:QACRC4YY 4656463:KABW2JXP

Academic Bridge: is set to transform education system - Atieno, Lydia (The New Times | Rwanda, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:9XCSN65E 2405685:8PP2AEWX

The Impact of an Educational Media Intervention to Support Children’s Early Learning in Rwanda - Borzekowski, Dina; Lando, Agnes Lucy; Olsen, Sara; Giffen, Lauren (International Journal of Early Childhood, 2019)
Children in developing countries often lack sufficient support for early learning skills prior to beginning school. This research evaluates an educational media intervention using an animated cartoon program, Akili and Me. The program was originally created in Tanzania to teach early learning skills. This program was adapted in content and language use in this study in Rwanda. The two-week intervention involved primary school students (mean age = 7.1 years) who were randomized into two groups (intervention and comparison group). The intervention group viewed one Ankit and Me episode a day for five days. This viewing was repeated the following week. Similarly, the comparison watched the same amount of television but the content consisted of local popular programs. Baseline and follow-up assessments evaluated 10 areas of early learning, using an adaptation of the International Development and Early Learning Assessment (IDELA), and also children’s media receptivity. At follow-up, children in the intervention program, Akili and Me, had significantly higher scores for counting, number recognition, shape knowledge, letter identification, color identification, body part recognition, health knowledge, and vocabulary. The analyses provide promising evidence that locally produced educational media interventions can impact early learning skills, even among children living in resource-poor communities.
shortDOI: 10/gf84g7 KerkoCite.ItemAlsoKnownAs: 10.1007/s13158-019-00237-4 10/gf84g7 2339240:4M44CELZ 2339240:S9UUM2LQ 2339240:U3CZV6QS 2405685:CFDKXVTN 2405685:D2RCFMG5 2405685:LXHQCK2G 2405685:S9R2V6GT 4803016:Z6Y5C2HY
Keywords: Literacy; Media receptivity; Numeracy; Rwanda; School readiness skills; Television; ___working_potential_duplicate

What makes a good classroom? New UIS data on school conditions - UNESCO (UNESCO, 2019)
New data from the UNESCO Institute for Statistics (UIS) reveal serious disparities in the schooling conditions facing children and teachers – from access to electricity, clean drinking water and single sex-toilets to Internet access and computers. Classroom conditions are key in providing a quality education for all. For children who struggle to enrol in school, for example due to poverty or discrimination on the grounds of gender or disability, poor school conditions can further undermine their chances of a quality education. What are the new data looking at?
KerkoCite.ItemAlsoKnownAs: 2339240:4DRK8RBZ 2405685:PT5I7FT5

1. Use of smartphones and social media is common across most emerging economies - Silver, Laura; Smith, Aaron; Johnson, Courtney; Jiang, JingJing; Anderson, Monica; Rainie, Lee (Pew Research Center, 2019)
Large majorities in the 11 emerging and developing countries surveyed either own or share a mobile phone, and in every country it is much more common to
KerkoCite.ItemAlsoKnownAs: 2339240:BNUHV8IL 2405685:ZQ6UX9B6

Examining the Impact of an English in Action Training Program on Secondary-School English Teachers’ Classroom Practice in Bangladesh - Karim, Abdul; Mohamed, Abdul (The Qualitative Report, 2019)
English teachers in Bangladesh have undergone numerous training programs. Both government-initiated and donor-sponsored training programs have been in operation in Bangladesh. Government initiated institutions to train teachers are Primary Training Institutes (PTIs) and Teacher Training Colleges (TTCs). However, researchers seemed to label training provided by PTIs and TTCs as inadequate. Bridging the gaps intrigued government of Bangladesh to devise donor-aided training programs, including English Language Teaching Improvement Project (ELTIP), English for Teaching, Teaching for English (ETTE), Secondary Education Quality and Access Enhancement Project (SEQAEP), Teaching Quality Improvement in Secondary Education Project (TQI-SEP). Studies reported their potential failure to bring changes in English teachers’ classroom practices. English in Action (EIA) was the last donor-funded project that incorporated schoolbased training program. The aim of the study was to examine the impact of EIA training program on secondary-school English teachers’ classroom practice in Bangladesh, drawing the questions in relation to the elements learned in the training program and the elements practiced in the training program. The present study undertook the Integrated Approaches to Teacher Development suggested by Hargreaves and Fullan (1992) and Reflective Model developed by Wallace (1991). This study adopted phenomenological approach since it subsumed the experience of an activity or concept from the participants’ perspective. Eight Participants were selected who had been trained from EIA training program and who had experience of participating in other donor-aided program, in the spirit of yielding the uniqueness of EIA which informed the sustainability of this program. It had been divulged that teachers learned a lot of activities that were related to English language teaching. However, the present studies observed limited practice of such activities in the classroom.
KerkoCite.ItemAlsoKnownAs: 10/gj37h4 2339240:A6YSCF88 2405685:FPNL6NJJ

Moving teachers to Malawi’s remote communities: A data-driven approach to teacher deployment - Asim, Salman; Chimombo, Joseph; Chugunov, Dmitry; Gera, Ravinder (International Journal of Educational Development, 2019)
There are severe geographical disparities in pupil-teacher ratios (PTR) across Malawi, with most teachers concentrated near commercial centers and in rural schools with better amenities. Most of the variation in PTR is concentrated in small sub-district areas, suggesting a central role for micro-geographic factors in teacher distribution. Employing administrative data from several government sources, regression analysis reveals that school-level factors identified by teachers as desirable are closely associated with PTR, including access to roads, electricity, and water, and distance to the nearest trading center, suggesting a central role for teachers’ interests in PTR variation. Political economy network mapping reveals that teachers leverage informal networks and political patronage to resist placement in remote schools, while administrative officials are unable to stand up to these formal and informal pressures, in part because of a lack of reliable databases and objective criteria for the allocation of teachers. This study curates a systematic database of the physical placement of all teachers in Malawi and links it with data on school facilities and geo-spatial coordinates of commercial centers. The study develops a consistent and objective measure of school remoteness, which can be applied to develop policies to create rules for equitable deployments and targeting of incentives. Growing awareness of disparities in PTRs among district education officials is already showing promising improvements in targeting of new teachers. Simulation results of planned policy applications show significant potential impacts of fiscally-neutral approaches to targeted deployments of new cohorts, as well as retention of teachers through data-calibrated incentives.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2018.12.002 2339240:7QKQHXG2 2405685:GWKND7GG
Keywords: Data-driven model; Deployments; Malawi; Political economy; Schools; Teachers

Reforming teacher education in Nigeria: Laying a foundation for the future - Barnes, Adrienne E.; Boyle, Helen; Zuilkowski, Stephanie Simmons; Bello, Zaliha Nasiruddeen (Teaching and Teacher Education, 2019)
Teacher educators in Nigeria receive limited professional development, particularly regarding the instruction of early grade reading skills. As part of the USAID-funded Northern Education Initiative Plus project, Florida State University faculty provided intensive teacher educator professional development to staff at four Teacher Education Institutions in northern Nigeria. Positive impacts on teacher educator knowledge, skills, and attitudes were observed related to content and pedagogical knowledge, use of participatory teaching and learning activities in the college classrooms, and improvement in student teacher engagement and learning. Continued success of the implemented model for training will be dependent upon national adoption and scale up.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2018.12.017 2339240:982EMD2L 2405685:7EPWKCK2

Systems Research in Education: Designs and methods - Magrath, Bronwen; Aslam, Monazza; Johnson, David (Research in Comparative and International Education, 2019)
This exploratory paper seeks to shed light on the methodological challenges of education systems research. There is growing consensus that interventions to improve learning outcomes must be designed and studied as part of a broader system of education, and that learning outcomes are affected by a complex web of dynamics involving different inputs, actors, processes and socio-political contexts. How should researchers in comparative and international education respond to this call for complexity? To begin to answer this question, we draw on recent and ongoing research within the Raising Learning Outcomes in Education Systems research programme – a programme of 30 projects funded by the UK’s Department for International Development (DFID) and Economic and Social Research Council (ESRC). The paper explores critical ways in which the methods used by individual research projects, and across the programme as a whole, offer opportunities and raise challenges for advancing systems thinking in education research.
Publisher: SAGE Publications zotzenLib.CopiedFrom: 2339240:XYCSYPYB KerkoCite.ItemAlsoKnownAs: 10.1177/1745499919828927 2339240:XYCSYPYB 2405685:M5TVF9HF 2405685:P563XUWZ 2405685:WBX6TN7Z
Keywords: Research methodology; ___working_potential_duplicate; education systems; mixed-methods research

Systems Research in Education: Designs and methods - Magrath, Bronwen; Aslam, Monazza; Johnson, David (Research in Comparative and International Education, 2019)
This exploratory paper seeks to shed light on the methodological challenges of education systems research. There is growing consensus that interventions to improve learning outcomes must be designed and studied as part of a broader system of education, and that learning outcomes are affected by a complex web of dynamics involving different inputs, actors, processes and socio-political contexts. How should researchers in comparative and international education respond to this call for complexity? To begin to answer this question, we draw on recent and ongoing research within the Raising Learning Outcomes in Education Systems research programme – a programme of 30 projects funded by the UK’s Department for International Development (DFID) and Economic and Social Research Council (ESRC). The paper explores critical ways in which the methods used by individual research projects, and across the programme as a whole, offer opportunities and raise challenges for advancing systems thinking in education research.
Publisher: SAGE Publications zotzenLib.CopiedFrom: 2339240:XYCSYPYB KerkoCite.ItemAlsoKnownAs: 10.1177/1745499919828927 2339240:XYCSYPYB 2405685:M5TVF9HF 2405685:P563XUWZ 2405685:WBX6TN7Z
Keywords: Research methodology; ___working_potential_duplicate; education systems; mixed-methods research

Global, regional and national burden of emergency medical diseases using specific emergency disease indicators: analysis of the 2015 Global Burden of Disease Study - Razzak, Junaid; Usmani, Mohammad Farooq; Bhutta, Zulfiqar A. (BMJ Global Health, 2019)
Objective There are currently no metrics for measuring population-level burden of emergency medical diseases (EMDs). This study presents an analysis of the burden of EMDs using two metrics: the emergency disease mortality rate (EDMR) and the emergency disease burden (EDB) per 1000 population at the national, regional and global levels. Methods We used the 1990 and 2015 Global Burden of Disease Study for morbidity and mortality data on 249 medical conditions in 195 countries. Thirty-one diseases were classified as ‘emergency medical diseases’ based on earlier published work. We developed two indicators, one focused on mortality (EDMR) and the other on burden (EDB). We compared the EDMR and EDB across countries, regions and income groups and compared these metrics from 1990 to 2015. Results In 2015, globally, there were 28.3 million deaths due to EMDs. EMDs contributed to 50.7% of mortality and 41.5% of all burden of diseases. The EDB in low-income countries is 4.4 times that of high-income countries. The EDB in the African region is 273 disability-adjusted life years (DALYs) per 1000 compared with 100 DALYs per 1000 in the European region. There has been a 6% increase in overall mortality due to EMDs from 1990 to 2015. Globally, injuries (22%), ischaemic heart disease (17%), lower respiratory infections (11%) and haemorrhagic strokes (7%) made up about 60% of EMDs in 2015. Conclusion Globally, EMDs contributed to more than half of all years of life lost. There is a significant disparity between the EDMR and EDB between regions and socioeconomic groups at the global level.
Publisher: BMJ Specialist Journals Section: Research KerkoCite.ItemAlsoKnownAs: 10.1136/bmjgh-2018-000733 2339240:74NSEPBV 2405685:5V7P8KVF

Scaling access and impact: Realizing the power of edtech (Omidyar Network, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:N6XVFXYL 2405685:WY27U4SB

Exploring relationships between Kolb's learning styles and mobile learning readiness of pre-service teachers: a mixed study - Ata, Rıdvan; Cevik, Mustafa (Education and Information Technologies, 2019)
The aim of this research is to reveal relations between Kolb's learning styles and mobile learning readiness of pre-service teachers in depth in regard to different variables and identify their mobile learning perspectives. The study group consisted of 352 students enrolled in undergraduate programs in education faculties of different universities in Turkey. The convergent parallel design was used as a mixed method strategy. The survey model, as a quantitative component, was used to describe the present situation and embedded interviews, as a qualitative component, were carried out to deeply reveal pre-service teachers' perspectives on mobile learning depending on their learning styles. The "Learning Styles Inventory - Version III" as well as the "Mobile Learning Readiness Scale" were administered to participants. ANOVA, Tukey-HSD test and Structural Equation Modelling were used to analyze the quantitative data. The qualitative data were analyzed by the content analysis method. Results suggest that 126 (36%) of the pre-service participating in the study were with the assimilating learning style, 92 (26.29%) participants were with the diverging learning style, 73 (20.85%) were with the converging learning style and 59 (16.85%) were with the accommodating learning style. Furthermore, it was observed that there is a statistically significant relationship between the learning styles of the pre-service teachers and their m-learning readiness. In addition, it was observed that while optimism, self-directed learning and self-efficacy have a strong effect on m-learning; mother education, monthly income, gender, internet use frequency have a moderate effect on m-learning within different learning styles. Qualitative data were also in line with the results of quantitative data. Findings were discussed in light of relevant literature. [ABSTRACT FROM AUTHOR]
Cam URL: KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-018-9835-y 2339240:TLEYZERM 2405685:98J9QFGS 2405685:W5HNS2SW 2534378:C5QGSSCL 2534378:GYJXUNMQ 2534378:JUQIJQKF 2534378:NDFQ6HKN 2534378:PPGAVAAJ 2534378:REYB4EAQ
Keywords: COGNITIVE styles; Cognitive Style; Cognitive style; Computers–Information Science And Information Theory; Content Analysis; EDUCATIONAL programs; ERIC; Current Index to Journals in Education (CIJE); Educational Attainment; Foreign Countries; Gender Differences; Handheld Devices; Higher Education; Income; Independent Study; Independent study; Kolb's learning styles; Kolb’s learning styles; LEARNING readiness; Learning Readiness; Learning Style Inventory; MOBILE learning; Measures (Individuals); Mobile learning; Mothers; Positive Attitudes; Postsecondary Education; Pre-service teachers; Preservice Teachers; STUDENT teachers; Self Efficacy; Structural Equation Models; Structural equation modelling; Student Attitudes; Teacher Education Programs; Telecommunications; Turkey; Undergraduate Students; __:import:01; __:match:final; __:matched; __:study_id:2095788; __finaldtb

Beyond the Basics: Improving Post-Primary Content Delivery through Classroom Technology - Beg, Sabrin A; Lucas, Adrienne M; Halim, Waqas; Saif, Umar (National Bureau of Economic Research, 2019)
Using an RCT in middle schools in Pakistan, we test the effect of a government- implemented in-class technology and brief teacher training intervention on student achievement in grade level mathematics and science. After only 4 months of exposure, student's combined math and science score increased by 0.3 standard deviations on both project and government tests, 59 percent more than the control group. Students were also more likely to pass the provincial high-stakes exams. Increased attendance by both students and teachers indicate technology can increase other inputs. At the 200 school scale, this program is extremely cost-effective.
Series: Working Paper Series KerkoCite.ItemAlsoKnownAs: 10.3386/w25704 2339240:8S5BZEQ5 2339240:N3IQ9VDH 2405685:56WJPPUE 2405685:MXHG8QD6
Keywords: EXCLUSION CRITERIA APPLIED; Quality: H; Relevance: M

Open Access Research: A Review of DFID’s Policy and Practice - Fosci, Mattia; Johnson, Rob; Chiarelli, Andrea (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:2C224QX7 2129771:C79Y6RX2 2405685:SHZYZGLN

The Impact of IRC’s Healing Classrooms Tutoring on Children’s Learning and Social-Emotional Outcomes in Niger - IRC (International Rescue Committee, 2019)
During school year 2016-2017, the International Rescue Committee (IRC) delivered Healing Classrooms remedial tutoring programming and additional low-cost, targeted social-emotional learning (SEL) interventions to children in Diffa, a region in Niger affected by recurrent Boko Haram attacks. We found that, after twenty-two weeks of program implementation, access to Healing Classrooms tutoring significantly improved students’ reading and math skills, and adding targeted SEL interventions to Healing Classrooms tutoring improved children’s overall school grades. However, we found little evidence of direct impacts of the additional targeted SEL strategies on children’s social-emotional outcomes.
KerkoCite.ItemAlsoKnownAs: 2339240:2ZE74HFK 2405685:M4ATP9QQ

Data Collection Survey on Possibilities of Educational Support with ICT and Japanese Companies Promotion in Mongolia - JICA (Japan International Cooperation Agency, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:239E56EY 2405685:4MTLKFBX
Keywords: ___working_potential_duplicate

Data Collection Survey on Possibilities of Educational Support with ICT and Japanese Companies Promotion in Mongolia - JICA (Japan International Cooperation Agency, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:239E56EY 2339240:RC54QSKZ 2405685:4MTLKFBX 2405685:JEGDNZCT
Keywords: ___working_potential_duplicate

Scaling Access & Impact: Realizing the Power of EdTech - Pouezevara, Sarah; Valdivia, Ignacio Jara; Michalec, Mike; Amalia, Talitha; Fleischmann, Sybille (Omidyar Network, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:GZZQHMNZ 2405685:CAXD8U9H

Capturing Cost Data - World Bank; International Rescue Committee (World Bank, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:IJ5E95SQ 2405685:4DU2PHIC 2405685:ZSZN39Y5
Keywords: ⛔ No DOI found

Developing BacaBicara: An Indonesian lipreading system as an independent communication learning for the deaf and hard-of-hearing - Muljono, Muljono; Saraswati, Galuh Wilujeng; Winarsih, Nurul Anisa Sri; Rokhman, Nur; Supriyanto, Catur; Pujiono, Pujiono (International Journal of Emerging Technologies in Learning (iJET), 2019)
Deaf and hard-of-hearing people have limitations in communication, espe-cially on aspects of language, intelligence, and social adjustment. To com-municate, deaf people use sign language or lipreading. For normal people, it is very difficult to use sign language. They have to memorize many hand signs. Therefore, lipreading is a necessary for communication between nor-mal and deaf people. In Indonesia, there is still few education media for deaf people to learn lipreading. To overcome this challenge, we develop a lipread-ing educational media to help deaf and hard-of-hearing to learn Bahasa In-donesia, called BacaBicara. User-Centered Design (UCD) is implemented to design the application and to analyze the constraints and conceptual models for the needs of users. This conceptual model uses the picture, lipreading video, text, and sign language to help the users understand the contents. The High fidelity prototype was implemented for evaluating usability testing. Based on the evaluation of the application, the results show that the proto-type matches the usability goals and the user experience.
Publisher: International Association of Online Engineering (IAOE) KerkoCite.ItemAlsoKnownAs: 10.3991/ijet.v14i04.9578 2339240:4NLP496M 2405685:NPDHNIHF

Developing BacaBicara: An Indonesian lipreading system as an independent communication learning for the deaf and hard-of-hearing - Muljono, Muljono; Saraswati, Galuh Wilujeng; Winarsih, Nurul Anisa Sri; Rokhman, Nur; Supriyanto, Catur; Pujiono, Pujiono (International Journal of Emerging Technologies in Learning (iJET), 2019)
Deaf and hard-of-hearing people have limitations in communication, espe-cially on aspects of language, intelligence, and social adjustment. To com-municate, deaf people use sign language or lipreading. For normal people, it is very difficult to use sign language. They have to memorize many hand signs. Therefore, lipreading is a necessary for communication between nor-mal and deaf people. In Indonesia, there is still few education media for deaf people to learn lipreading. To overcome this challenge, we develop a lipread-ing educational media to help deaf and hard-of-hearing to learn Bahasa In-donesia, called BacaBicara. User-Centered Design (UCD) is implemented to design the application and to analyze the constraints and conceptual models for the needs of users. This conceptual model uses the picture, lipreading video, text, and sign language to help the users understand the contents. The High fidelity prototype was implemented for evaluating usability testing. Based on the evaluation of the application, the results show that the proto-type matches the usability goals and the user experience.
3 citations (Crossref) [2024-02-28] Number: 04 KerkoCite.ItemAlsoKnownAs: 10.3991/ijet.v14i04.9578 2339240:GSBL5SJE 2405685:BJEAPNI2
Keywords: Deaf and hard of hearing; Interaction; lipreading; user-centered design prototype; ⛔ No INSPIRE recid found

3 examples of mother tongue education to improve learning | Blog | Global Partnership for Education - Global Partnership for Education (Education for All blog, 2019)
GPE supports mother tongue education as a key component of the foundation of learning. On International Mother Tongue Day we review how three partner countries—Eritrea, The Gambia and Uzbekistan—with help from GPE, are implementing mother tongue programs.
KerkoCite.ItemAlsoKnownAs: 2339240:BDTJKNV3 2405685:NKEBMREJ

Top 10 Facts About Life Expectancy in Vietnam - Hiday, Haley (The Borgen Project, 2019)
Although it is true that the life expectancy rates tend to be relatively high in Vietnam, the most common causes of death, although preventable or treatable, have often been somewhat ignored by the country’s health officials and the general public. To get a better understanding of how these health oversights can and are being corrected, the list below states the top 10 facts about life expectancy in Vietnam as well as the efforts being made to enhance rates.
KerkoCite.ItemAlsoKnownAs: 2339240:SXP9VDNE 2405685:WZV8MQ2R

Integrating 21st century skills into education systems: From rhetoric to reality - Vivekanandan, Ramya (Brookings, 2019)
While many countries espouse the importance of 21st century skills in their education sector plans, few of them make concrete moves to address these skills in their implementation.
KerkoCite.ItemAlsoKnownAs: 2339240:8LX2V72P 2405685:DY54PT9Y

Social support networks, instant messaging, and gender equity in refugee education - Dahya, Negin; Dryden-Peterson, Sarah; Douhaibi, Dacia; Arvisais, Olivier (Information, Communication and Society, 2019)
This paper addresses the role of instant messaging chat groups to support teacher training and gender equity initiatives in Kenyan refugee camps. Our findings are based on survey data with refugee teachers in Dadaab and Kakuma refugee camps (n = 203), group interviews with refugee teachers in Kakuma (n = 21), and interviews with international instructors of teacher training programs in Nairobi, Toronto, and Vancouver (n = 14). In our analysis, we apply amplification theory, feminist science and technology studies paradigms, and considerations of transnational approaches to understand the use of instant messaging among refugee teacher communities. Our framework explores how social and cultural norms are amplified through transnational text and instant messaging related to teacher training and in support of gender equity. Peer-to-peer group chats draw on transnational learning opportunities and expand these engagements through group chats between men and women refugee teachers across camps as well as through community engagement about gender equity initiatives in education. International instructors identify both value and hesitation in navigating the quantity and content of these communications, such as learning more about refugee teachers’ daily lives in the camps and concern about following and managing the amount of communication that can ensue over chat groups. Our work has practical implications for transnational teacher training programs in refugee camps, illuminates how mobile technology and chat groups allow women and men in the community to engage and support girls’ education, and questions how text messaging affects the lived and day-to-day experiences of women refugee teachers
Publisher: Informa UK Limited KerkoCite.ItemAlsoKnownAs: 10.1080/1369118X.2019.1575447 2339240:FBD2EJ6I 2405685:ZMB7IUBX

Digital School Census in 10 Weeks? How it was done in Sierra Leone - Namit, Kariba; Mai, Thanh Thi (World Bank Blogs, 2019)
Note: This blog is specifically about Sierra Leone’s successful transition to a digital school census but has broader implications for other countries who plan to adopt digital tools at a wider scale to collect data and monitor education and healthcare facilities in their countries. In April of last year, the new Minister of Finance of Sierra Leone approached the World Bank with a strong commitment to prioritize education and an intriguing request.
Library Catalog: blogs.worldbank.org KerkoCite.ItemAlsoKnownAs: 2339240:PP5768J6 2339240:TGTJZWCC 2405685:EPMH5GMB 2405685:EY9VEBRN 2405685:KXNLTUXL 2405685:NUSFD2XU 2405685:PLIT3YBG 2405685:TIEFATQQ 4803016:S4RTD2LL

Digital School Census in 10 Weeks? How it was done in Sierra Leone - Namit, Kariba; Mai, Thanh Thi (World Bank Blogs, 2019)
Note: This blog is specifically about Sierra Leone’s successful transition to a digital school census but has broader implications for other countries who plan to adopt digital tools at a wider scale to collect data and monitor education and healthcare facilities in their countries. In April of last year, the new Minister of Finance of Sierra Leone approached the World Bank with a strong commitment to prioritize education and an intriguing request.
KerkoCite.ItemAlsoKnownAs: 2405685:BFZ3FTAT 2486141:G289KIHC

The True Cost of Freemiums in Edtech - Levine, Elliott (EdTech Digest, 2019)
An industry veteran has some on-point advice about what you pay for and what you get. GUEST COLUMN | by Elliott Levine They say, “the best things in life are free,” but that is not always the case. With education technology (edtech), sometimes the cost of “free” ends up being unreasonably high in the long […]
KerkoCite.ItemAlsoKnownAs: 2339240:I9AWBSIU 2405685:SXL6X7IC

Design principles for systematic search systems: A holistic synthesis of a rigorous multi-cycle design science research journey - Sturm, Benjamin; Sunyaev, Ali (Business & Information Systems Engineering, 2019)
Rigorous systematic literature searches are often described as complex, error-prone and time-consuming because of a prevailing lack of adequate technological assistance. Nonetheless, one of the first steps when conducting a rigorous literature review is finding an appropriate literature sample. The quality of this literature sample is an important factor for the overall quality of the literature review. This article investigates how to design innovative IT systems that effectively facilitate systematic literature searches. Applying the design science research paradigm, the research method consists of multiple design cycles of artifact development, evaluation, and refinement. In doing so, six design principles are derived that intend to increase the comprehensiveness, precision, and reproducibility of systematic literature searches. The results could be helpful for research and practice. The derived design knowledge builds a foundation for future research on systematic search systems and enables new methodological contributions. The results could also guide the development of innovative search systems and features that, eventually, increase the quality and efficiency of information accumulation in different contexts.
KerkoCite.ItemAlsoKnownAs: 10.1007/s12599-018-0569-6 2405685:6ZC2C36J 2486141:I75MLBTJ 2486141:UNR5E4GB
Keywords: Design principles; Design science research; Information retrieval; Literature review; Systematic literature searches; Systematic search systems; _Added-ailr-2024

Investigating The Benefits Of Incorporating Technology In Instructional Curriculum: Pre-Service Teachers' Perspectives From Ghana - Wiafe, Bernard; Akaadom, Bernard (International Journal of Advanced Research, 2019)
The use of technology has gained worldwide recognition in all professions. Teachers have resorted to several technology tools to enhance the work they do in the classroom and to facilitate the understanding of what they teach their students to enhance easy recall and for students to remember what they learn in class. The use of technology tools in the classroom in Ghana has not received much attention from teachers because of challenges with respect to technological infrastructural development. However, with the inclusion of technology in the teacher colleges of education curriculum, new teachers are being trained to incorporate technology into classroom instruction to change the face of teaching and make learners more eager to learn by bringing the understanding of concepts much more clearly to students. The study adopted a mixed method approach to bring to light, the perspectives of teacher trainees and tutors in colleges on the benefits both the teacher and the learner stand to gain in using technologies to deliver instruction in the classroom. It came to light that although there are challenges pre-service teachers tend to face in terms of access to such technologies, they still do their best to include technologies in their lessons whenever possible. This is because of the fact that learners tend to do well on instruction received on lessons delivered using technology as compared to lessons delivered without using technology based on their experience in using both approaches in the classroom. Keywords: Technology, instruction, benefits, curriculum.
KerkoCite.ItemAlsoKnownAs: 2339240:CALRBHZL 2405685:35ERS5DI
Keywords: ⛔ No DOI found

ASEAN Enabling Masterplan 2025 - Association of Southeast Asian Nations (ASEAN) (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:TF42GDC9 2405685:TGPS2FI5

Equivalent Years of Schooling: A Metric to Communicate Learning Gains in Concrete Terms - Evans, David K; Yuan, Fei (World Bank, 2019)
In the past decade, hundreds of impact evaluation studies have measured the learning outcomes of education interventions in developing countries. The impact magnitudes are often reported in terms of "standard deviations," making them difficult to communicate to policy makers beyond education specialists. This paper proposes two approaches to demonstrate the effectiveness of learning interventions, one in "equivalent years of schooling" and another in the net present value of potential increased lifetime earnings. The results show that in a sample of low- and middle-income countries, one standard deviation gain in literacy skill is associated with between 4.7 and 6.8 additional years of schooling, depending on the estimation method. In other words, over the course of a business-as-usual school year, students learn between 0.15 and 0.21 standard deviation of literacy ability. Using that metric to translate the impact of interventions, a median structured pedagogy intervention increases learning by the equivalent of between 0.6 and 0.9 year of business-as-usual schooling. The results further show that even modest gains in standard deviations of learning – if sustained over time – may have sizeable impacts on individual earnings and poverty reduction, and that conversion into a non-education metric should help policy makers and non-specialists better understand the potential benefits of increased learning.
Accepted: 2019-02-21T21:57:06Z KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-8752 2339240:G8VXLD8Z 2339240:YC4YK2TQ 2405685:HU5C56PD 2405685:KL7YY8E7 2405685:VQUG747J 2534379:G8AZFHFY
Keywords: Education; Impact Evaluation; Learning Outcomes; Lifetime Earnings; Net Present Value; Poverty Reduction; Years of Schooling; ___working_potential_duplicate

Equivalent Years of Schooling: A Metric to Communicate Learning Gains in Concrete Terms - Evans, David K.; Yuan, Fei (2019)
In the past decade, hundreds of impact evaluation studies have measured the learning outcomes of education interventions in developing countries. The impact magnitudes are often reported in terms of "standard deviations," making them difficult to communicate to policy makers beyond education specialists. This paper proposes two approaches to demonstrate the effectiveness of learning interventions, one in "equivalent years of schooling" and another in the net present value of potential increased lifetime earnings. The results show that in a sample of low- and middle-income countries, one standard deviation gain in literacy skill is associated with between 4.7 and 6.8 additional years of schooling, depending on the estimation method. In other words, over the course of a business-as-usual school year, students learn between 0.15 and 0.21 standard deviation of literacy ability. Using that metric to translate the impact of interventions, a median structured pedagogy intervention increases learning by the equivalent of between 0.6 and 0.9 year of business-as-usual schooling. The results further show that even modest gains in standard deviations of learning – if sustained over time – may have sizeable impacts on individual earnings and poverty reduction, and that conversion into a non-education metric should help policy makers and non-specialists better understand the potential benefits of increased learning.
Publisher: World Bank, Washington, DC KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-8752 2339240:5JI69878 2405685:7CTP3XVS

75 Digital Tools and Apps Teachers Can Use to Support Formative Assessment in the Classroom (Teach. Learn. Grow., 2019)
We’ve compiled an extensive list of 75 digital tools, apps, and platforms that can help teachers use formative assessment to elicit evidence of student learning. #education #teachers
Library Catalog: www.nwea.org Section: Formative Assessment KerkoCite.ItemAlsoKnownAs: 2339240:H4U5K8J7 2405685:WU8SHHQ8 WU8SHHQ8

UNICEF and Telenor Group extend global partnership to reduce inequalities among children - Telenor (Telenor Group, 2019)
(FORNEBU, 31 January 2019) – UNICEF and Telenor Group today announced an agreement to extend their long-running global partnership for another three years – through 2021. Launched in 2014, the partnership delivers large-scale global projects which leverage Telenor’s digital platforms to reduce inequalities and enhance children and young people’s skills for the digital future.
KerkoCite.ItemAlsoKnownAs: 2339240:5M2TEFLZ 2405685:MIYADBNX

Wikipedia:Text of Creative Commons Attribution-ShareAlike 3.0 Unported License - Wikipedia (Wikipedia, 2019)
Page Version ID: 880226358 KerkoCite.ItemAlsoKnownAs: 2339240:JSYRJYYQ 2405685:8BQ6B427

How solar mini-grids can bring cheap, green electricity to rural Africa - Zajicek, Charlie (odi.org, 2019)
Well-suited to small, remote communities, renewable energy mini-grids can be the most cost-effective option for rural electrification in Africa.
KerkoCite.ItemAlsoKnownAs: 2405685:4VUP32WG 2534378:IT6G3AEW

The erasures of racism in education and international development: re-reading the ‘global learning crisis’ - Sriprakash, Arathi; Tikly, Leon; Walker, Sharon (Compare: A Journal of Comparative and International Education, 2019)
(2019). The erasures of racism in education and international development: re-reading the ‘global learning crisis’. Compare: A Journal of Comparative and International Education. Ahead of Print.
KerkoCite.ItemAlsoKnownAs: 2405685:SP8G9VKP
Keywords: ⛔ No DOI found

The Impact of Information Provision on Human Capital Accumulation and Child Labor in Peru - Neilson, Christopher; Gallego, Francisco; Molina, Oswaldo (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:4INGTTXL 2405685:XJZXU5HI

Investigating the barriers to change management in public sector educational institutions - Al-Alawi, Adel Ismail; Abdulmohsen, Muna; Al-Malki, Fatema Mohamed; Mehrotra, Arpita (International Journal of Educational Management, 2019)
Purpose – The purpose of this paper is to explore barriers to the change management in the public sector of educational institutions such as public schools of the Ministry of Education in the GCC countries. The exploration of the research is based on the ADKAR change management model that consists of five key elements, which are awareness, desire, knowledge, ability and reinforcement. The ADKAR model was used for many reasons, among these reasons is that it allows management to separate the change process into parts, pinpointing where change is failing and addressing that impact point.
KerkoCite.ItemAlsoKnownAs: 10.1108/ijem-03-2018-0115 2339240:VAJE86HZ 2405685:LD8TF3AS

Electronic learning and its benefits in education - Abed, Enaam Karim (EURASIA Journal of Mathematics, Science and Technology Education, 2019)
The concept of Electronical Learning was emerged which is a method of education in the delivery of information to the learner, depends on the latest technologies of the mathematics, the global network of information and multimedia, the fields of dialogue, discussion and virtual classes. But the field of electronic learning and its solutions will not be successful if there are lack of basic elements of the current traditional education. The latter accomplishes many tasks indirectly or invisible to the passers-by, where the students’ time and attendance of schools is an important thing inculcates educational values indirectly and promotes joint work as a team. A variety of services, such as obtaining a Master’s degree online directly, or awarding technical certificates to programmers, IT professionals and other great features, as they do the necessary procedures and provide the required standards for the introduction of recognized programs for distance study.
KerkoCite.ItemAlsoKnownAs: 10.29333/ejmste/102668 10/gmfk2w 2339240:G2W9IBG6 2405685:ZVV7W9M3

Young children’s use of technological devices: Parents’ views - Jabbar, Sinaria Abdel; Al-Shboul, Muhannad; Tannous, Adel; Banat, Sanaa; Aldreabi, Hanadi (Modern Applied Science, 2019)
This paper presents parents’ views of their young children’s access and use of technological devices, the duration spent on technological devices and the benefits and risks associated with that. 500 parents completed a questionnaire and findings suggest that parents hold positive beliefs about technology with smartphones being the most used among their children and the most effective device, while e-reading was the least used. Findings indicated that parents believe technology benefits their children in developing intellectually, socially, physically and emotionally respectively, thus it enhances children’s educational development through educational activities while they interact with peers at the same time; physical development was number 1 risk on children which was associated to health and mental development. Recommendations were given at the end of the paper to examine in depth how technological devices can used in educational settings in favour of children.
KerkoCite.ItemAlsoKnownAs: 10.5539/mas.v13n2p66 2339240:JWDGJFNE 2405685:LP38ELVY

Experimental Impacts of the “Quality Preschool for Ghana” Interventions on Teacher Professional Well-being, Classroom Quality, and Children’s School Readiness - Wolf, Sharon; Aber, J. Lawrence; Behrman, Jere R.; Tsinigo, Edward (Journal of Research on Educational Effectiveness, 2019)
We assessed the impacts of a teacher professional development program for public and private kindergartens in the Greater Accra Region of Ghana. We examined impacts on teacher professional well-being, classroom quality, and children’s readiness during one school year. This cluster-randomized trial included 240 schools (teachers N ¼ 444; children N ¼ 3,345, Mage ¼ 5.2) randomly assigned to one of three conditions: teacher training (TT), teacher training plus parental-awareness meetings (TTPA), and controls. The programs incorporated workshops and in-classroom coaching for teachers and video-based discussion groups for parents. Moderate impacts were found on some dimensions of professional well-being (reduced burnout in the TT and TTPA conditions, reduced turnover in the TT condition), classroom quality (increased emotional support/behavior management in the TT and TTPA conditions, support for student expression in the TT condition), and small impacts on multiple domains of children’s school readiness (in the TT condition). The parental-awareness meetings had counteracting effects on child school readiness outcomes. Implications for policy and practice are discussed for Ghana and for early childhood education in low- and middle-income countries.
shortDOI: 10/ggjrcj KerkoCite.ItemAlsoKnownAs: 10.1080/19345747.2018.1517199 10/ggjrcj 2339240:S3WAE3PS 2405685:H52RQ6MY 2405685:JXYTEU3W
Keywords: Ghana; ___working_potential_duplicate; classroom quality; early childhood education; kindergarten; school readiness; teacher training and coaching

Gender Equity and Fee-Free Basic Education in Tanzania - Al-Samarrai, Samer; Tamagnan, Marie Evane (2019)
Tanzania has registered improvements in education outcomes over the last ten years. The implementation of the Fee-Free Basic Education Program (FBEP) is a key element of the government’s overall strategy to improve education outcomes and accelerate growth. Tackling gender disparities in basic education will be critical to the success of FBEP. In recent years, Tanzania has eliminated many of the gender gaps associated with education access. However, large gender gaps in learning outcomes start in primary and get wider over the course of secondary school. The aim of this note is to identify the underlying causes of gender disparities in secondary education and identify promising policy options to tackle them. It shows that addressing gender disparities in education is crucial to the success of FBEP and more broadly to national development goals. This note is part of a series that looks at the implications of Tanzania’s Fee-Free Basic Education Program (FBEP). Its focus is primarily on secondary education because separate analytical work on early childhood is currently being undertaken and a separate note is analyzing the trends and determinants of learning outcomes in primary education. This note is arranged as follows: Section 2 briefly outlines the benefits of extending access to basic education; Section 3 describes the characteristics of gender disparities in secondary education; Section 4 identifies the factors that drive gender differences in outcomes, and Section 5 reviews the evidence on interventions capable of narrowing gender disparities. The final section concludes by arguing that narrowing gender differences in education outcomes needs a multidimensional approach.
Publisher: World Bank Group KerkoCite.ItemAlsoKnownAs: 2339240:VSAIL8UH 2405685:QLV2EITH
Keywords: ⛔ No DOI found

A digital platform for supervised self-directed learning in emergencies: the case of the Syrian crisis - Almasri, Nada; Tahat, Luay; Skaf, Sawsan; Masri, Aman Al (Technology, Pedagogy and Education, 2019)
The well-known Syrian crisis has made it very challenging for thousands of Syrian children to have access to education. In this article, the authors propose a framework for designing a digital education platform to allow children inside Syria as well as in the refugee camps in bordering countries to have access to education. The authors start by looking at the efforts performed in the field of education in conflict-affected regions, and they extract from them the lessons learned and recommendations. They provide four main characteristics of war impacting children’s education: (1) insecurity, (2) instability, (3) lack of resources, and (4) lack of adult supervision. They then use these four characteristics, along with the extracted recommendations, as the grounds for drafting three design considerations for the implementation of a digital education platform. The three design considerations are: supervised self-directed learning method, context-aware education and children-oriented design. Finally, the authors use these design considerations to provide design recommendations for the four main elements of a digital education platform: hardware, software, curriculum and supporting services. They conclude by discussing the validity of the digital platform, its implementation feasibility, and challenges facing the implementation.
shortDOI: 10/ggtbq4 KerkoCite.ItemAlsoKnownAs: 10.1080/1475939x.2019.1568293 10/ggtbq4 2339240:EQIPQ7IH 2405685:ZYQY3IXK
Keywords: Google Scholar/ "refugee education" ICT; RER theme_pedagogies and modalities

Pakistan Demographic and Health Survey 2017-18 - NIPS/Pakistan, National Institute of Population Studies-; ICF (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RTFLL9BG 2405685:3GGE62IJ
Keywords: ⛔ No DOI found

Behavioral Insights for Public Policy: Concepts and Cases - Ruggeri, Kai; Jarke, Hannes; Berkessel, Jana; Benzerga, Amel; Hlavova, Renata; Immonen, Johanna; Kunz, Marvin; Ojinaga Alfageme, Olatz; Paul, Alessandro; Plohl, Nejc; Prinz, Gerhard; Steinnes, Kamilla; et al. (2019)
https://www.routledge.com/Behavioral-Insights-for-Public-Policy-Concepts-and-Cases/Ruggeri/p/book/9781138484238 The first decades of the 21st century have offered a remarkable shift in how policies are made as well as who designs them. Until this period, advisory boards for local, regional, and national policy strategies largely comprised economists, lawyers, and financial experts. These panels made recommendations based on standing theory and, in some cases, subject-matter expertise, such as energy or healthcare. What has changed is how the behavioral sciences, largely psychology, have been embraced within these groups, thanks largely to extensive evidence from empirical research in how populations save, spend, eat, exercise, and work. While the application to policy may have contemporary versions, the behavioral side of economic theory itself is not new. Relevant insights on this go at least as far back as the 18th century with Daniel Bernoulli and Adam Smith, and continued steadily over the next two centuries with significant works from the likes of Wilhelm Wundt, Herbert Simon, and Roald Coase, among many others. However, how it came to be is perhaps more critical than merely who drove it. In each of these waves, a major shift in thinking was often preceded by empirical study that either attempted to explain how humans apply logic, or by surprising deviations from what appears to be rational. This textbook covers a range of topics from the origins of policy through to how recent advances in theory and practice have shifted our thinking on outcomes for society. Each section, including the fundamentals of behavioral sciences, policy development and evaluation, and all of the domains – economic, health, energy, education, workplace – cover examples of how behavioral insights are being used to address some of the most critical challenges we face. The cases and concepts presented in this book demonstrate the considerable value, both realized and potential, in studying as well as implementing behavioral insights into a variety of policy domains. We are still very much in the early days of this field, which means that these are merely fundamentals for educating and inspiring future generations of researchers, policymakers, and government leaders. As progress continues, how ultimate goals relevant to society are defined and targeted will become an increasingly important refrain amongst those involved in developing them. In these ways, we can consistently align our approaches with the most critical matters of local, national, and global communities: our safety, our stability, and our well-being.
KerkoCite.ItemAlsoKnownAs: 10.4324/9781351052542 2339240:PQJRBDLC 2405685:7ZNIPA98

Global Education Monitoring Report – Gender Report: Building bridges for gender equality - UNESCO (Paris, UNESCO, 2019)
KerkoCite.ItemAlsoKnownAs: 10.54676/QTBO2301 2339240:VB5GA7BS 2405685:2JY7UCMS

Thespians in print: Gender portrayal in Pakistani English print media - Yasmin, Musarat; Masso, Isamar Carrilo; Bukhari, Nadeem Haider; Aboubakar, Muhammad (Cogent Arts & Humanities, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1080/23311983.2019.1661647 2339240:KJSMZJ7H 2405685:RCU62CCF

Learning Motivations, Learning Outcomes and Gender in Vietnam - Azubuike, Obiageri Bridget; Little, Angela W (2019)
This working paper uses the 2016-17 Young Lives school survey data in Vietnam to examine learning outcomes and learning motivations for boys and girls in Grade 10. It examines how differences in learning motivations impact on learning outcomes and future expectations, and also examines the determinants of these differences and their relationships with student’s background and prior learning attainment.
KerkoCite.ItemAlsoKnownAs: 2339240:WQ43I24R 2405685:CBI3IUSP

Bangladesh Education Sector Public Expenditure Review - Bhatta, Saurav Dev; Genoni, Maria Eugenia; Sharma, Uttam; Khaltarkhuu, Buyant Erdene; Maratou-Kolias, Laura; Asaduzzaman, T. M. (World Bank, 2019)
Adequate investment in human capital development is critical for enabling Bangladesh to reach its goal of becoming an upper middle-income country. Bangladesh, currently a lower-middle country with an annual per capita gross national income (GNI) of USD 1,470 (WDI 2019), aims to attain upper-middle income status by 2021 and eliminate poverty by 2030. Recognizing the importance of investing in education for building its human capital base, the government of Bangladesh (GoB) has been allocating a large portion of the national budget to the education sector each year during the past two decades. Effective utilization and equitable distribution of allocated public spending is important for ensuring adequate progress in education outcomes. This report analyzes major spending and outcomes trends in the overall education sector in recent years, with a focus on primary and secondary education. Responding to the recommendation of the 2015 Bangladesh Public Expenditure Review Update for more analytical work on public spending in different sectors, including education, the current study analyzes the trends in major education expenditures, access to education, quality of education, and disparities in education outcomes in the past two decades. It also looks at the composition of education expenditure, consistency between budget allocations and actual expenditures, equity in education spending, and potential links between spending and key educational outcomes. Because of data limitations, this report focuses mainly on primary and secondary education. It is expected that this analysis will add to the literature on investments in the Bangladesh education sector and inform discussions on identifying policy priorities and making resource allocation decisions in the sector.
Accepted: 2021-07-19T16:19:39Z KerkoCite.ItemAlsoKnownAs: 2339240:W64P6523 2405685:HJVFISKT 4656463:CYJBRSJM
Keywords: Education Budget; Education Expenditure; Education Outcomes; Equity in Education; Public Expenditure Review

Sustaining learner participation and progression through networked schooling: a systemic approach for Mobile Out of School Children - Dyer, C.; Echessa, E. (International Journal of Educational Development, 2019)
Despite repeated calls for education systems to respond flexibly to enable all children to participate in formal education, limited progress has been made for those we term Mobile Out of School Children (MOOSCs). Livelihood-related mobility often precipitates a process of learner drop out during the year. Retention of such children, and reducing the risk of their relapsing into MOOSC status, requires a re-framing of ‘school’ as a spatially dispersed system, or network, to accommodate learner movement. Networked schooling for children in mobile pastoralist communities in Ethiopia embeds formal education within mobile pastoralists’ resource management practices and orientates service provision accordingly. Although it is resource-intensive, networked schooling enables the requisite flexibility to support retention of pastoralist and other mobile learners. It of significant interest to global effort towards leaving none behind, particularly in the global drylands and other contexts where climate change is making learner mobility increasingly complex, and the need for a systemic response ever more pressing.
shortDOI: 10/ggjq9n KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2018.11.002 10/ggjq9n 2339240:2ZQYMQNZ 2405685:5RL4Q5RD

General Education Sector Strategic Plan 2018/19 - 2022/23 - Federal Ministry of Education (Government of the Republic of Sudan, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:3HQC3SI7 2405685:GYTUPSBC

Employment Structure and the Rise of the Modern Tax System - Jensen, Anders (National Bureau of Economic Research, 2019)
This paper studies how the transition from self-employment to employee-jobs over the long run of development explains growth in income tax capacity. I construct a new database which covers 100 household surveys across countries at different income levels and 140 years of historical data within the US (1870-2010). Using these data, I first establish four new stylized facts: 1) within country, the share of employees increases over the income distribution, and increases at all levels of income as a country develops; 2) the income tax exemption threshold moves down the income distribution as a country develops, tracking employee growth; 3) the employee share above the tax exemption threshold is maximized and remains constantly high; 4) movements in the tax exemption threshold account for the observed variation in tax collection across development. These findings are consistent with a model where a high employee share is a necessary condition for effective taxation and where the rise in income covered by information trails through increases in employee shares drives expansion of the income tax base. To provide a causal estimate of the impact of employee share on the exemption threshold, I study a state-led US development program implemented in the 1950s-60s which shifted up the level of employee share. The identification strategy exploits within-state changes in court-litigation status which generates quasi-experimental variation in the effective implementation date of the program. I find that the exogenous increase in employee share is associated with an expansion of the state income tax base and an increase in state income tax revenue.
KerkoCite.ItemAlsoKnownAs: 10.3386/w25502 2339240:BWCVJY8N 2405685:AQK6W3IH 4656463:PRFXGI88

Accelerated Education Programme Youth Education Programme: NRC Education Scale-up and Quality Fund, EdTech for Rapid Response in Acute Emergencies Project - Kipruto, Amos; Denny, Kathleen (Norwegian Refugee Council, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:3FEKJXY2 4042040:B3V7LHH4

The impacts of interactive smartboards on learning achievement in Senegalese primary schools - Lehrer, Kim; Mawoyo, Monica; Butcher, Neil; Mbaye, Samba (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RZW67P62 2405685:AQH9MLLA 6018420:TL8K8IWF

The Net Neutrality Situation in the EU Evaluation of the First Two Years of Enforcement - Lohninger, Thomas; Gollatz, Benedikt; Hoffmann, Cornelia; Steinhammer, Erwin; Deffaa, Ludger; Al-Awadi, Ali; Czák, Andreas (Epicenter Works, 2019)
EdTechHub.ItemAlsoKnownAs: 2405685:I33D3ZVM

Uganda Impact Study Report - Pouezevara, Sarah; Brunette, Tracy; Jordan, Rachel; Nakyejwe, Deborah (RTI International, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:8WCG9GLK 2405685:39FUDM2P

Elimika (Kenya Education Cloud) (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:D4BCHAZW 2405685:ISBJKG3V

Elimu Tanzania (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:CSDTPS7N 2405685:TB4RPQES

Ghana Investment Fund for Electronic Communications (2019)
Library Catalog: gifec.gov.gh KerkoCite.ItemAlsoKnownAs: 2405685:3CSLWUJY

Ghana Mulitple Indicator Cluster Survey 2017/2018 (The Government of Ghana, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:H645IUG5

Kenya Publishers Association (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:9A5R6KAC

KitKit School (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:CPQVK55T 2405685:J4ZAF7FX

Leveraging Community and Government Resources for Gender and Educational Equity in India: A Case Study of Educate Girls | Educate a Child (educate a child, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:NHVZMVIL 2405685:QLKRXATW

Ministry of Information, Communications and Technology, Innovation and Youth Affairs (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:WL8CUUV2

Scaling Access & Impact: Realizing the Power of EdTech. Executive Summary (Omidyar Network, 2019)
Publisher: Omiyad Network KerkoCite.ItemAlsoKnownAs: 2339240:6TRLF7J9 2405685:KKINUTFX

Telkom Kenya Limited (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:N3EXUGKG

Futures of Education in Bangladesh: Envisioning 2041 - a2i (Government of People's Republic of Bangladesh, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:WBR2EN8Q 2405685:HTABJ4F4

Constructivist Assistive Technology in a Mathematics Classroom for the Deaf: Going Digital at a Rural Namibian Primary School - Abiatal, Loide K.S.; Howard, Grant R. (Proceedings of the South African Institute of Computer Scientists and Information Technologists 2019, 2019)
Within the context of almost nine million children with hearing disabilities in Sub-Saharan Africa, their education is an important topic. The problem was the lack of conclusive research about the effects of digital assistive technologies for educating deaf learners in Sub-Saharan African countries, such as Namibia. The question was could a digital assistive technology improve the mathematics achievement of deaf children? The research objective was to gather scientific evidence by conducting a quantitative experiment with constructivist digital assistive technology and qualitative interviews with the teachers involved. The findings from the experiment suggest that the constructivist digital assistive technology may have had a positive effect on the mathematics achievement of the learners, which was supported by the findings from the interviews. This makes an original contribution to the domain and offers an intervention that was feasible, practical and potentially effective for improving the teaching and learning of mathematics for deaf learners.
KerkoCite.ItemAlsoKnownAs: 10.1145/3351108.3351136 2339240:9RXUDFHE 2405685:QSKYPSUP
Keywords: Constructivism; Constructivist assistive technology; Deaf learners; Digital assistive technology; Experiment; Hearing disability; Interviews; Mathematics education; Namibia; Primary school education; Sub-Saharan Africa; Teaching and learning

Lean Data Initiative - Acumen (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:GWCPJ9JE 2405685:F8558KAX

Appraisal on perceived multimedia technologies as modern pedagogical tools for strategic improvement on teaching and learning - Adekunle, Salako E.; Adewale, Olumide S.; Boyinbode, Olutayo K. (International Journal of Modern Education and Computer Science, 2019)
shortDOI: 10/ggjpd6 KerkoCite.ItemAlsoKnownAs: 10.5815/ijmecs.2019.08.02 10/ggjpd6 2339240:KAJ9HGXU 2405685:D32JUS5T

The Importance of Dynamic Geometry Computer Software on Learners’ Performance in Geometry - Adelabu, Folake Modupe; Makgato, Moses; Ramaligela, Manto Sylvia (The Electronic Journal of e-Learning, 2019)
The use of dynamic geometry computer software (DGCS) is important in educational environment, and it is more advantageous for learning mathematics comprehensively. This study examined the importance of dynamic geometry computer software on learners’ performance in geometry. A quasi experimental, non-equivalent control group was used. The instrument used in this study was geometry achievement mathematics test (GMAT) that comprised 15 multiple choices items. The GMAT was administered to 87 grade nine learners in two secondary schools in Tshwane south district, Gauteng Province South Africa. One school was used as experimental group and the second school was used as the control group. Data analysis employed the use of the statistical t-test independent sample. The result of the study shows that using DGCS is important in geometry whereby it improves the performance of learners. In addition, the results show that the software affects the female learners’ mathematics performances more positively than the male learners. Hence, the results of this study showed that there is great potential in using the DGCS (GeoGebra) to teach secondary schools mathematics. The study recommends that the use of technology in teaching and learning of mathematics should be a priority in the schools.
KerkoCite.ItemAlsoKnownAs: 2339240:FJ8S99TD 2405685:AB8PMF73
Keywords: ⛔ No DOI found

Magufuli asks Tanzania's teachers, parents to cane students - AfricaNews (Africanews, 2019)
Critics, including the local government minister, had said the official violated the students’ human rights because they had not been given a fair trial, and only teachers or headmasters are authori
KerkoCite.ItemAlsoKnownAs: 2339240:9F7R53TR 2405685:P4Y87VSG

Teachers’ Perception on Using Kio-Kit to Enhance Teaching and Learning STEM Subjects in Zanzibar - Ahmada, Raya Idrissa; Abdulla, Ali Abdulla; Yunus, Said Ali Said; Ismail, Maryam Jaffar (Sustainable ICT, Education and Learning, 2019)
In the current situation, teachers are encouraged to use interactive, student-centered approaches than using traditional approaches that mainly focus on ‘chalk and talk’. Student-centered approaches, also learner-centered, involve methods of teaching that shift the focus of instruction from the teacher to the student. When these approaches are powered by technology, they can doubly enhance teaching and learning. The most current technology that gains popularity in Africa in teaching and learning process is the Kio-Kit technology which promised to improve the quality of teaching and learning. It is a digital education toolbox which contains different forms of digital contents to help students in their learning process. The box contains 40 Kio tablets in which students use them to access the contents available in the Kio-Kit box. This paper aims to discuss the perception of using this type of technology from school teachers who have been trained intensively to use them to enhance the teaching and learning of STEM subjects. During the exploration, we confirmed that Kio-Kit technology enhances teaching and learning and helps the students gain necessary skills for the 21st century digital era. The results also reveal STEM teachers’ readiness to use the Kio-Kit technology in the classroom. Further, the paper describes the challenges encountered during the exploration of Kio-Kit in classroom and some suggestions are proposed.
shortDOI: 10/ghgn5v KerkoCite.ItemAlsoKnownAs: 10/ghgn5v 2339240:GGJVI64G 2405685:AUHLLX5M
Keywords: Digital classroom; ICT; Kio-Kits; STEM for Success; Student-centered learning; Zanzibar

Learning Equity Requires More than Equality: Learning Goals and Achievement Gaps between the Rich and the Poor in Five Developing Countries - Working Paper 504 - Akmal, Maryam; Pritchett, Lant (RISE Programme Working Paper, 2019)
Achieving some absolute standard of learning for all children is a key element of global equity in education. Using the Annual Status of Education Report (ASER) data from India and Pakistan, and Uwezo data from Kenya, Tanzania, and Uganda that test all children of given ages, whether in school or not, on simple measures of learning in math, reading (local language), and English, we quantify the role of achieving equality between the richest 20% and the poorest 40% in terms of grade attainment and learning achievement toward accomplishing the global equity goal of universal numeracy and literacy for all children.
KerkoCite.ItemAlsoKnownAs: 2339240:HR2A7JWR 2405685:5DCJE3IG

Gender equity and fee-free basic education in Tanzania - Al-Samarrai, Samer; Tamagnan, Marie Evane (Education Global Practice, Africa Region, World Ban, 2019)
Samer Al-Samarrai, Marie Evane Tamagnan1 Introduced in 2016, the Fee-Free Basic Education Program (FBEP) is the government’s flagship policy to expand equitable access to basic education. Evidence shows that policies of this kind increase educational access and lead to significant economic and social benefits. In Ghana, children that received fee-free education were much more likely to complete secondary school and had much higher earnings than children that were not part of the program. In Tanzania, similar benefits to FBEP are possible since the labor market returns to secondary schooling are high.
KerkoCite.ItemAlsoKnownAs: 2339240:UENQDWLH 2405685:M2GTQWNU

Gender equity and fee-free basic education in Tanzania - Al-Samarrai, Samer; Tamagnan, Marie Evane (Education Global Practice, Africa Region, World Ban, 2019)
Samer Al-Samarrai, Marie Evane Tamagnan1 Introduced in 2016, the Fee-Free Basic Education Program (FBEP) is the government’s flagship policy to expand equitable access to basic education. Evidence shows that policies of this kind increase educational access and lead to significant economic and social benefits. In Ghana, children that received fee-free education were much more likely to complete secondary school and had much higher earnings than children that were not part of the program. In Tanzania, similar benefits to FBEP are possible since the labor market returns to secondary schooling are high.
KerkoCite.ItemAlsoKnownAs: 2339240:UENQDWLH 2405685:M2GTQWNU

Effectiveness of Gamification of Web-Based Learning in Improving Academic Achievement and Creative Thinking among Primary School Students - Aljraiwi, Seham (International Journal of Education and Practice, 2019)
Gamification is one of the most significant modern trends in educational technology. The present study aims to identify the effectiveness of gamification of web-based learning on academic achievement and creative thinking among primary school students. A learning environment was designed based on gamification of web-based learning. A quasi-experimental approach was utilized to identify the effect of the independent variable, gamification, on the dependent variables, academic achievement and creative thinking among participants. An academic achievement test and the Torrance test of creative thinking were applied to the participants. Results revealed that there was a statistically significant difference between the means of scores of the experimental and control groups in the post-test academic achievement test and the Torrance test of creative thinking in favor of the experimental group. This suggests a high level of academic achievement and creative thinking after using gamification. The study recommends training in-service teachers in the use of gamification for web-based teaching of English.
Publisher: Conscientia Beam KerkoCite.ItemAlsoKnownAs: 10.18488/journal.61.2019.73.242.257 2339240:D8I68N8K 2405685:ZF63RKCS
Keywords: Academic Achievement; Achievement Tests; Control Groups; Creative Thinking; Creativity Tests; Educational Games; Elementary School Students; English (Second Language); Experimental Groups; Inservice Teacher Education; Instructional Effectiveness; Scores; Second Language Instruction; Web Based Instruction

Examination of factors influencing the use of mobile learning system: An empirical study - Almaiah, Mohammed Amin; Alismaiel, Omar Abdulwahab (Education and Information Technologies, 2019)
Past studies have placed little emphasis on quality factors as the detebile learning application provides me a promptrminants of mobile learning adoption. Thus, this study’s purpose is to integrate the Technology Acceptance Model (TAM) with the updated DeLone and McLean’s model (DL&ML) to examine whether quality factors (including system quality, information quality, and service quality) and individual beliefs (including perceived usefulness and perceived ease of use) are the antecedents to students’ satisfaction and their intention to use, leading to enhancing their actual usage of mobile learning system. A total of 400 questionnaires were distributed. The results showed that quality factors (including system quality, information quality, and service quality) had significant effects on students’ satisfaction and their intention to use mobile learning; besides, perceived usefulness has significantly strong impacts on intention to use mobile learning, and satisfaction and intention to use both have significant effects on actual use of mobile learning. This study opens future work for using the identified quality factors as guidelines for researchers and designers to design and develop mobile learning applications.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-018-9810-7 10/gjvp3d 2339240:HV3VGLYU 2405685:X9ZLVTQE

A digital platform for supervised self-directed learning in emergencies: The case of the Syrian crisis - Almasri, Nada; Tahat, Luay; Skaf, Sawsan; Masri, Aman Al (Technology, Pedagogy and Education, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2019.1568293 2339240:RBETEGPM 2405685:AP7RBDHC

Report of the Special Rapporteur on extreme poverty and human rights - Alston, Philip (United Nations General Assembly, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:7DQX9NKE 2405685:M7L4IXDW

A Software Based on Eye Gaze to Evaluate Mathematics in Children with Cerebral Palsy in Inclusive Education - Alvarado-Cando, Omar; Belén Jara, G.; Barzallo, Paúl; Torres-Salamea, Hugo (Advances in Usability, User Experience and Assistive Technology, 2019)
The government of Ecuador has promoted inclusive education in public and private education centers, ensuring that all children can access education and not be discriminated by their disability. Teachers are responsible for planning, support and reorganized the curriculum according to the needs of each child included. The inclusion process for children with cerebral palsy (CP) and speech difficulties have been a little difficult because they cannot communicate properly with the teachers and the evaluation process is not clear and objective. In this paper, through the use of eye tracking technology provide by Irisbond, we present an educational software to evaluate mathematics in children with CP. The software performs the questions in written and audible way, and it allows the students to select and/or match the correct answer; children with CP from 5 to 7 years tested the program and they got a better rating than not using it.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-319-94947-5_89 2339240:Z2PVFKUK 2405685:IETJ528E
Keywords: Assistive technology; Cerebral palsy; Eye gazed; Inclusive education

The Charisma Machine - Ames, Morgan (MIT Press, 2019)
A fascinating examination of technological utopianism and its complicated consequences.In The Charisma Machine, Morgan Ames chronicles the life and legacy of...
KerkoCite.ItemAlsoKnownAs: 2339240:EBLRH5VE 2405685:TCF8RZEN

Personal Data Broker: A Solution to Assure Data Privacy in EdTech - Amo, Daniel; Fonseca, David; Alier, Marc; García-Peñalvo, Francisco José; Casañ, María José; Alsina, María (Learning and Collaboration Technologies. Designing Learning Experiences, 2019)
Educational technologies (Edtech) collect private and personal data from students. This is a growing trend in both new and already available Edtech. There are different stakeholders in the analysis of the collected students’ data. Teachers use educational analytics to enhance the learning environment, principals use academic analytics for decision making in the leadership of the educational institution and Edtech providers uses students’ data interactions to improve their services and tools. There are some issues in this new context. Edtech have been feeding their analytical algorithms from student’s data, both private and personal, even from minors. This draws a critical problem about data privacy fragility in Edtech. Moreover, this is a sensitive issue that generates fears and angst in the use of educational data analytics in Edtech, such as learning management systems (LMS). Current laws, regulations, policies, principles and good practices are not enough to prevent private data leakage, security breaches, misuses or trading. For instance, data privacy agreements in LMS are deterrent but not an ultimate solution due do not act in real time. There is a need for automated real-time law enforcement to avoid the fragility of data privacy. In this work, we take a step further in the automation of data privacy agreement in LMS. We expose which technology and architecture are suitable for data privacy agreement automation, a partial implementation of the design in Moodle and ongoing work.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-21814-0_1 2339240:7MD56SEP 2405685:9F2LYDQZ
Keywords: Academic analytics; Blockchain; Data privacy; Digital identity; Educational data mining; Learning Analytics; Moodle; Smart contracts

Delay in teachers’ salaries sparks unrest in Liberia - Andalou Agency (2019)
Students took to streets, demanding release of payments to their teachers and return to class work - Anadolu Agency
Library Catalog: www.aa.com.tr KerkoCite.ItemAlsoKnownAs: 2405685:LT97PP6U

Willingness and ability of LCPS to pay Ilm: A for products and services - AOE Research; Qazilbash, Zulfiqar (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:AUXHQ47E 2405685:2686V5Z6

Teachers resistance towards change in Punjab public schools: implications for school effectiveness - Arif, Seema; Riasat, Lubna (2019)
Teachers’ resistance to change has become a perennial phenomenon which educational sector had to deal with because without the active involvement and commitment of teachers, change and reform policies are prone to failure. The urge to explore the reasons behind teachers’ resistance towards any change and need to modify some policies to minimize this factor, motivated the researcher to conduct this research. The aim of present descriptive research is to identify reasons for teacher’s resistance towards reform agenda introduced by previous government of Punjab (2013-18). Using simple random sampling 28 public schools of tehsil Model Town district of Lahore were taken as sample of the study; each school was taken as cluster and all teachers were approached to fill the questionnaire, however, final data constituted only 295 questionnaires. Self-developed questionnaire, comprising 36 items further categorized into eight factors was used as tool. Both descriptive (means & Standard Deviation) and inferential (correlation & regression) were applied. The research has concluded that role of school principal and management’s implementation strategy have strong link with positive attitude of teacher towards adapting for change. Hence, it is important that principals must manage doubts and fears of teachers about change to counteract resistance and negative attitude towards change.
KerkoCite.ItemAlsoKnownAs: 2339240:22MLNCBI 2339240:ZT6ANWQL 2405685:2SZTZHC5 2405685:TI453NL5
Keywords: ⛔ No DOI found

Learner access to resources for eLearning and preference for eLearning delivery mode in distance education programs in Ghana - Arthur-Nyarko, Emmanuel; Kariuki, Moses Githua (International Journal of Educational Technology, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:XYCPC7IU 2405685:83GZ8QYZ
Keywords: ⛔ No DOI found

Academy for Education Planning and Management and Annual Status of Education Report - ASER (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BTUDKTRJ 2405685:EHRF5EK8 2405685:K5DECGEM

Annual Status of Education Report - ASER (ASER, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:GM46AP95 2405685:B3TPJ3NB

Annual Status of Education Report - ASER Pakistan (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:DJW3TIQC

School Education in Pakistan: A Sector Assessment - Asian Development Bank (Asian Development Bank, 2019)
Edition: 0 ISBN: 9789292615291 9789292615284 shortDOI: 10/ghgnf7 KerkoCite.ItemAlsoKnownAs: 10.22617/TCS190039 10/ghgnf7 2339240:MAX5I4DD 2339240:VDACLSSI 2405685:8VW9ZAMB 2405685:B4FE433S 2405685:MTCNL9CE

Improving School Performance through School Ranking: The Double-Edged Sword of Accountability - Atuhurra, Julius; Kaffenburger, Michelle (RISE Programme, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:K8SQNYUB 2405685:AN2ZBCLR 4656463:A4BQU8V8

The impact of parental involvement and education on academic achievement in elementary school - Avnet, M.; Makara, D.; Larwin, K.H.; Erickson, M. (International Journal of Evaluation and Research in Education (IJERE), 2019)
KerkoCite.ItemAlsoKnownAs: 10.11591/ijere.v8i3.20249 2339240:VDHHAICS 2405685:BASYVF4K

How Can Schools Support Parents’ Engagement in their Children’s Learning? Evidence from Research and Practice - Axford, Nick; Berry, Vashti; Lloyd, Jenny; Moore, Darren; Rogers, Morwenna; Hurst, Alison; Blockley, Kelly; Durkin, Hannah; Minton, Jacqueline (EEF, 2019)
The EEF is an independent charity dedicated to breaking the link between family income and educational achievement.
KerkoCite.ItemAlsoKnownAs: 2339240:MK49B6CM 2405685:BLGCB3CD

Teaching linear algebra supported by GeoGebra visualization environment - Aytekin, Cahit; Kiymaz, Yasemin (Acta Didactica Napocensia, 2019)
Linear algebra differs from other mathematics courses because of the special difficulties that students have in understanding the concepts. Teaching without concretizing the concepts of Linear Algebra encouraged students to memorize definitions of concepts and rules has been articulated. Many researches show that technology-supported teaching is effective in concretizing abstract concepts. In this study, it was examined how pre-service mathematics teachers relate the definitions of concepts (linear combination, linear dependency/independency and spanning) and their visual equivalents in R[superscript 2] and R[superscript 3]. The study was conducted with four students who attended the Linear Algebra-2 course in the Elementary Mathematics Teaching, Faculty of Education of a state university in Turkey. The study was conducted by the teaching experiment method. Interviews were conducted using activities prepared in the GeoGebra program. It was observed that the participants used these concepts in very flexible way and they established a relationship between visualization and definitions in a very short time compared to the time spent during an educational period.
Publisher: Babes-Bolyai University, Kogainiceanu 1, Cluj-Napoca, 400084 Romania Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2396823562?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.24193/adn.12.2.7 2339240:BJHHRSRN 2405685:SNEABJDN 2534378:G2ILAXW6 2534378:J8FUJBYM
Keywords: Algebra; Computer Software; Definitions; ERIC; Current Index to Journals in Education (CIJE); Educational Technology; Foreign Countries; Higher Education; Mathematics Instruction; Mathematics Teachers; Postsecondary Education; Preservice Teachers; Teaching Methods; Technology Uses in Education; Turkey; Visualization; __:import:01; __:match:final; __:matched; __:study_id:2099267; __finaldtb

BAG - BAG Innovation Ltd (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:IJ3HHEHB 2405685:V9GV6AZN

Preparing teacher education students to integrate mobile learning into elementary education - Bai, Hua (TechTrends, 2019)
The wide adoption of mobile technology has greatly influenced K-12 education. In teacher education programs, it is necessary for educators to train teacher education students to use mobile technology for educational purpose. This paper reports an exploratory effort in preparing elementary education students for mobile learning. The participants’ perceptions of mobile learning and intended use of mobile technology were examined through the analyses of their online discussion posts, responses to survey items and their projects. Their perceived benefits of mobile learning, limitations of mobile technology, their intended implementation of mobile learning and the challenges they anticipated were reported. Implications and recommendations were discussed regarding the knowledge of mobile apps, pedagogical practices and some non-instructional issues.
Extra URL: http://link.springer.com/10.1007/s11528-019-00424-z KerkoCite.ItemAlsoKnownAs: 10.1007/s11528-019-00424-z 2405685:FGVRJWT3 2534378:9U8QNM9N

Reimagining digital literacies from a feminist perspective in a postcolonial context - Bali, Maha (Media and Communication, 2019)
Publisher: PRT shortDOI: 10/ghd7tr KerkoCite.ItemAlsoKnownAs: 10.17645/mac.v7i2.1935 10/ghd7tr 2129771:YNKMTYRY 2405685:WRQ65HUV 2486141:KHXAW3EG

Using Information Communication Technologies (ICT) to Implement Universal Design for Learning (UDL) - Banes, David; Hayes, Anne; Kurz, Christopher; Kulshalnagar, Raja (University Research Co., LLC, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QM93JBAC 2405685:QDLCLTE4

Using information communications technologies (ICT) to implement universal design for learning - Banes, David; Hayes, Anne; Kurz, Christopher; Kushalnagar, Raja (USAID, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:UPJYRCHC 2405685:HNQV5VIQ 2405685:LDR4KKFM

Progotir Pathey, Bangladesh Multiple Indicator Cluster Survey 2019, Survey Findings Report - Bangladesh Bureau of Statistics (BBS); UNICEF Bangladesh (Bangladesh Bureau of Statistics (BBS), 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:GI5823C2 2339240:N5JK4A3G 2405685:2RPSQCKH 2405685:78ADZUUD

Un potencial con barreras: La participación de las mujeres en el área de Ciencia y Tecnología en Argentina | Publications - Basco, Ana Inés; Lavena, Cecilia (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:VWA7ATK4 2405685:ATMQ6L3D

Engaging Teachers with Technology Increased Achievement, Bypassing Teachers Did Not - Beg, Sabrin A.; Lucas, Adrienne M.; Halim, Waqas; Saif, Umar (National Bureau of Economic Research, 2019)
Founded in 1920, the NBER is a private, non-profit, non-partisan organization dedicated to conducting economic research and to disseminating research findings among academics, public policy makers, and business professionals.
KerkoCite.ItemAlsoKnownAs: 10.3386/w25704 2339240:TBHVAYN6 2339240:ZM4QJ97Y 2405685:85UPRNLV 2405685:P6CAARB6
Keywords: ___working_potential_duplicate

Beyond the Basics: Improving Post-Primary Content Delivery through Classroom Technology - Beg, Sabrin; Lucas, Adrienne M; Halim, Waqas; Saif, Umer (2019)
Using an RCT in middle schools in Pakistan, we test the eﬀect of a governmentimplemented in-class technology and brief teacher training intervention on student achievement in grade level mathematics and science. After only 4 months of exposure, student achievement increased by 0.2-0.3 standard deviations on math and science tests, 52 to 120 percent more than the control group, and students were more likely to pass the provincially standardized high stakes exams. Increased eﬀorts by both students and teachers indicate a complementarity between technology and other inputs in education production. At a scale of 100 schools, this program is extremely cost-eﬀective.
KerkoCite.ItemAlsoKnownAs: 10.3386/w25704 2339240:N3IQ9VDH 2405685:56WJPPUE

Government Policy for the Internet Must Be Rights-Based and User-Centred | United Nations - Ben-Hassine, Wafa (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RGPAFMXP 2405685:KE3RRNLQ

Research commentary: Data-driven computationally intensive theory development - Berente, N.; Seidel, S; Safadi, H. (Information Systems Research, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1287/isre.2018.0774 2405685:YYPVZ3MY 2486141:Q2QSCZPT
Keywords: _Added-ailr-2024

How behavioral science can empower parents to improve children's educational outcomes - Bergman, Peter (Behavioral Science & Policy, 2019)
Parents powerfully influence their children’s educational outcomes. Yet psychological and informational barriers impede parents’ ability to engage with their children in ways that improve outcomes: parents tend to have inflated perceptions of their children’s performance, which can deter them from taking helpful steps to effectively support their learning, and parenting is complex. Limited cognitive bandwidth for coping with complexities can steer parents’ attention away from actions that have long-term benefits for their children and toward actions yielding immediate returns. Poor school-to-parent communication and poverty exacerbate all of these problems. In this article, the author demonstrates how providing timely, actionable information to parents can lower these barriers and help parents engage with their children more productively from kindergarten through high school. Moreover, providing this information can improve educational outcomes at low cost.
KerkoCite.ItemAlsoKnownAs: 10.1353/bsp.2019.0004 2339240:EFP32JJ7 2405685:W5PIX5JE

Teachers' Preferences for Proximity and the Implications for Staffing Schools: Evidence from Peru - Bertoni, Eleonora; Elacqua, Gregory; Hincapie, Diana; Méndez, Carolina; Paredes, Diana (Inter-American Development Bank, 2019)
KerkoCite.ItemAlsoKnownAs: 10.18235/0001977 2129771:L9UR6285 2339240:92L8XSSF 2339240:YW9P92JU 2405685:7YJITWWI 2405685:JVM5XA6B 2405685:NTU6WXZ3 4556019:SVTALQW6
Keywords: C:Peru; _C:Peru PER

Causes of Girls Drop out from Primary Schools in Tehsil Bahrain District Swat, KPK Pakistan - Bibi, Aqsa; Ahmad, Waqar (Asian Journal of Contemporary Education, 2019)
Getting education is very important for both boys and girls. However, there are female children who do not complete school cycle and leave school before its completion which is one of the concerning issues for the Ministry of Education in Pakistan. To know why these girls drop out of school, the study provides some brief information on it. To get information on the above issue, structured interviews were used. The study was conducted in 4 Girls primary schools of Tehsil Bahrain district SWAT. Data was collected from sample of 80 respondents, in which (11 dropout girls from Govt Girls Primary School Madyan Swat, 16 from Govt Girls Primary School Ayeen Swat, 22 dropout girls from Girls Primary School Darolai Swat, 3 dropout girls from Girls Primary School Jail Bahrain Swat. 20 mothers of the dropout students and 8 teachers. After collecting information, some of the main causes for the dropout were found as work to earn some money for support of family (poverty), moving from one place to another, culture of the village, punishment, teachers' behavior, long distance from house to school and lack of text books and facilities. By looking to the findings of the study, there is a need of other researches in the area.
Publisher: AESS Publications KerkoCite.ItemAlsoKnownAs: 10.18488/journal.137.2019.31.44.58 2339240:2CGD2B4A 2405685:8LQ6V9XE
Keywords: Child Labor; Cultural Influences; Dropout Research; Dropouts; Elementary School Students; Females; Foreign Countries; Individual Characteristics; Poverty; Student Attitudes

Theorising Effective Uses of Digital Technology with Activity Theory - Blayone, Todd J. B. (Technology, Pedagogy and Education, 2019)
Effective uses of digital technologies are vital to full inclusion in a network society. Digital-abilities researchers have produced several major frameworks, but these have generally not incorporated socio-contextual perspectives. To explore this lacuna, and engage in a reflective act of theorisation, activity theory is used to conceptualise four sub-systems of digitally mediated action. Eschewing technological determinism, humans are positioned as active agents capable of identifying, taking up, modifying and even subverting established technology uses in pursuit of meaningful objectives. At the same time, attention is given to contextual conditions shaping diverse activity systems supported by assemblages of humans and machines. Having theorised effective digital-technology uses through the lens of activity theory, the author reflects on this conceptual apparatus itself. In so doing, activity theory is characterised as a fertile, if complex and contested, future-oriented tradition that challenges individual-social dichotomies and addresses both humans and machines as mediators of activity, development and learning.
Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2019.1645728 2339240:5T4VKUGM 2405685:KTIRVW7U
Keywords: Automation; Computer Use; Cultural Influences; Educational Technology; Group Activities; Information Technology; Man Machine Systems; Social Theories; Technology Uses in Education

Why is School-based Management (SBM) in Cambodia? - Bo, Chankoulika (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:3666J784 2405685:ELI6T2YQ

What works now? : evidence-informed policy and practice - Boaz, Annette; Davies, Huw; Fraser, Alec; Nutley, Sandra (Policy Press, 2019)
Building substantially on the earlier, landmark text, What Works? (Policy Press, 2000), this book brings together key thinkers and researchers to provide a contemporary review of the aspirations and realities of evidence-informed policy and practice. The text is clearly structured and provides sector-by-sector analysis of evidence use in policy-making and service delivery. It considers some cross-cutting themes, including a section of international commentaries, and concludes by looking at lessons from the past and prospects for the future.
KerkoCite.ItemAlsoKnownAs: 2339240:2S6VILZT 2405685:8BD4NMZZ

wwwlitbaskets.io, an IT artifact supporting exploratory literature searches for Information Systems research - Boell, SK; Wang, B (Proceedings of the Pacific Asia conference on information systems (eds KK Wei, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:EDNQS3TE 2486141:V87EDIZ4
Keywords: _Added-ailr-2024; ⛔ No DOI found

CASEL's framework for systemic social and emotional learning - Borowski, T. (Establishing Practical Social-Emotional Competence Assessment Work Group, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:Z2WGRMIS 2405685:ARDRR5TA

From Distance Education to Open and Distance Learning: A Holistic Evaluation of History, Definitions, and Theories - Bozkurt, Aras; Bozkurt, Aras (Handbook of Research on Learning in the Age of Transhumanism, 2019)
As pragmatist, interdisciplinary fields, distance education (DE) and open and distance learning (ODL) transform and adapt themselves according to changing paradigms. In this regard, the purpose of this study is to examine DE and ODL from different perspectives to discern their future directions. The study concludes that DE and ODL are constantly developing interdisciplinary fields where technology has become a significant catalyst and these fields become part of the mainstream education. However, mainstreaming should be evaluated with caution, and there is a need to revisit core values and fundamentals where critical pedagogy would have a pivotal role. Besides, there is no single theory that best explains these interdisciplinary fields, and therefore, there is a need to benefit from different theoretical approaches. Finally, as a result of constant changes, we should keep the definition of both DE and ODL up-to-date to better explain the needs of the global teaching and learning ecosystem.
ISBN: 9781522584315 Publisher: IGI Global shortDOI: 10/ghgn5b KerkoCite.ItemAlsoKnownAs: 10.4018/978-1-5225-8431-5.ch016 10/ghgn5b 2405685:HUJRQ23F

BRAC Education Programme Bangladesh - BRAC (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:V9ITPR43 2405685:QBPVDD4B

Mobile literacy among Syrian refugee women teachers - Bradley, Linda; Bahous, Rima; Albasa, Ali (CALL and complexity – short papers from EUROCALL 2019, 2019)
This research project investigates mobile literacy of Syrian refugee women teachers settled in Lebanon and Sweden. Our research provides input into Syrian refugee women teachers' professional aspirations and their connection to informal mobile learning. In both countries, training programs are used for these newly arrived teachers, enabling them to move forward in their careers, where digital and mobile learning play an important part. The purpose is to investigate how Syrian refugee women teachers are blending their teaching profession and vocational training with mobile literacy and digital technology. A qualitative method approach was applied, interviewing 20 refugee women in Lebanon and Sweden, all teachers from Syria. The outcomes show that the teachers are developing their vocational abilities in getting more career-oriented training in their areas of education by means of enhancing their language skills through mobile technology. [For the complete proceedings, see ED600837.]
Publisher: Research-publishing.net, La Grange des Noyes, 25110 Voillans, France KerkoCite.ItemAlsoKnownAs: 10.14705/rpnet.2019.38.986 2339240:ZAUCKJ67 2405685:45VMGDEX 2405685:8RNRFPG7 2405685:HUEZG3W8 2534378:93K5R9FV 2534378:NR6VFNNC
Keywords: Career Development; Cross Cultural Studies; ERIC; Resources in Education (RIE); Faculty Development; Females; Foreign Countries; Handheld Devices; Informal Education; Information Technology; Land Settlement; Lebanon; Literacy; Occupational Aspiration; Refugees; Second Language Instruction; Second Language Learning; Sweden; Syria; Teacher Attitudes; Telecommunications; Videoconferencing; __:import:01; __:match:final; __:matched; __:study_id:2095768; ___working_potential_duplicate; __finaldtb

Academic staff perspectives on technology for assessment (TfA) in higher education: A systematic literature review - Brady, Mairead; Devitt, Ann; Kiersey, Rachel A. (British Journal of Educational Technology, 2019)
This paper presents a systematic literature review of academic staff experiences and perceptions of adopting Technology for Assessment OF/FOR/AS Learning in Higher Education. This paper is a qualitative synthesis of 65 peer-reviewed journal articles published between 2012 and 2017 reporting on the use of technology for assessment (TfA). The results suggest that there are some efficiencies for staff in implementing TfA but this can come with a cost at the set-up and maintenance phases. Furthermore, results indicated that assessment design is not of foremost concern to academic staff when introducing TfA, but that a wide variety of pressures and both educational and operational drivers are present. There were inconclusive findings in relation to understandings of appropriate institutional environments and supports for TfA to flourish in higher education. There is a need for empirical research, particularly longitudinal investigations, of academic experiences of implementations of TfA to investigate sustainability of adoption. The imperative of exploring the academic staff perspective as the instigator and manager of both the technology and the student learning experience requires deep consideration as TfA adoption progresses.
shortDOI: 10/gf5f7m KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12742 10/gf5f7m 2339240:BGFA2SDN 2405685:DBQ25LCM

Keeping the learning going: using mobile technology to enhance learning transfer - Brion, Corinne (Educational Research for Policy and Practice, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1007/s10671-018-09243-0 2405685:VFBUV8DG

Child Online Safety Universal Declaration - Broadband Commission (Broadband Commission, 2019)
There are more than 2 billion children under the age of 18, with the majority living in the developing countries in Sub Saharan Africa, Asia and Latin America and the Caribbean. Many children have access to and are being impacted by the Internet. They may also be exploited by its use in unthinkable ways, and … Child Online Safety Declaration Read More »
KerkoCite.ItemAlsoKnownAs: 2339240:NW5QXBCI 2405685:BQBQG5BV

Research to Investigate Low Learning Achievement in Early Grade Numeracy (Standards 1–4) in Malawi: The victory of form over substance - Brombacher, Arnout (HEART, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:M7DRE98S 2405685:AIUSUUNA

The impact of mother tongue reading instruction in twelve Ugandan languages and the role of language complexity, socioeconomic factors, and program implementation - Brunette, Tracy; Piper, Benjamin; Jordan, Rachel; King, Simon; Nabacwa, Rehemah (Comparative Education Review, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1086/705426 2405685:N6LYI2SD 4042040:KKJT92BH

Factors That Influence Teachers' Pedagogical Use of ICT in Secondary Schools: A Case of Ghana - Buabeng-Andoh, Charles (Contemporary Educational Technology, 2019)
Technology is perceived as a vital driving force for contemporary education. The Government of Ghana acknowledges the relevance of Information and Communication Technology (ICT) in education, and it is financing ICT in secondary schools. However, most instructors are unwilling to integrate ICT into their teaching. Therefore, the purpose of this study was to investigate the factors that influence secondary school teachers' ICT usage in schools. The participants were 376 teachers randomly selected from 24 public and private schools. The data collected from the participants were analyzed by using descriptive statistics and analysis of variance. The results showed that teachers' use of ICT was still confined to basic and traditional activities such as search for information, class presentation etc. Internal and external factors were found to influence teachers' ICT usage. Also, female teachers reported that they use ICT more than male teachers. In general, this study has contributed to the literature regarding teachers' pedagogical use of ICT in secondary schools and also their gender differences in the use of ICT.
Publisher: Contemporary Educational Technology KerkoCite.ItemAlsoKnownAs: 2339240:BKXQRZLF 2405685:CJMLD46D
Keywords: Access to Computers; Competence; Computer Uses in Education; Foreign Countries; Gender Differences; Influence of Technology; Information Technology; Instructional Leadership; Pedagogical Content Knowledge; Private Schools; Public Schools; Rural Schools; Secondary School Teachers; Secondary Schools; Self Efficacy; Teacher Attitudes; Technological Literacy; Technology Integration; Training; Urban Schools; ⛔ No DOI found

Expanding School Time and the Value of Computer-Assisted Learning: Evidence from a Randomized Controlled Trial in El Salvador - Buchel, Konstantin; Jakob, Martina; Kuhnhanss, Christoph; Steﬀen, Daniel; Brunetti, Aymo (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:9YIYHWW9 2405685:BNSIAB6T
Keywords: ⛔ No DOI found

Information and communications technologies in secondary education in sub-Saharan Africa: Policies, practices, trends, and recommendations - Burns, Mary; Santally, Mohammad Issack (Mastercard Foundation, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BIW2Z8U5 2405685:PF2YUZR3

Educating 21st Century Children: Emotional Well-Being in the Digital Age - Burns, Tracey; Gottschalk, Francesca (OECD Publishing, 2019)
What is the nature of childhood today? On a number of measures, modern children’s lives have clearly improved thanks to better public safety and support for their physical and mental health. New technologies help children to learn, socialise and unwind, and older, better-educated parents are increasingly playing an active role in their children's education. At the same time, we are more connected than ever before, and many children have access to tablets and smartphones before they learn to walk and talk. Twenty-first century children are more likely to be only children, increasingly pushed to do more by “helicopter parents” who hover over their children to protect them from potential harm. In addition to limitless online opportunities, the omnipresent nature of the digital world brings new risks, like cyber-bullying, that follow children from the schoolyard into their homes. This report examines modern childhood, looking specifically at the intersection between emotional well-being and new technologies. It explores how parenting and friendships have changed in the digital age. It examines children as digital citizens, and how best to take advantage of online opportunities while minimising the risks. The volume ends with a look at how to foster digital literacy and resilience, highlighting the role of partnerships, policy and protection.
KerkoCite.ItemAlsoKnownAs: 2339240:QCFAWB6K 2405685:EUL4UHAW

Broadening borders to build better schools: virtual professional learning communities - Carpenter, Daniel; Munshower, Paul (The International Journal of Educational Management, 2019)
PurposeThe purpose of this paper is to explore how rural teachers provided a PLC by leveraging virtual technologies to connect educators of like subject disciplines from several schools, foreign and domestic.Design/methodology/approachA phenomenological case study-based approach was leveraged to investigate established vPLCs at schools (Creswell, 2013; Stake, 2010). Qualitative data were collected from multiple sources to obtain rural teacher perceptions on the impact vPLCs had on their practice (Creswell, 2013).FindingsTeacher collaborative teams build relationships comparable to teams that met face to face as part of a similar PLC and PD experience. Participant reflections in this investigation showed that rural educators favored face-to-face meetings; however, vPLCs provided similar teacher experiences to that of the face-to-face PBL model. Results indicated that educators recognized virtual collaboration just as valuable a tool for enabling PLCs than face-to-face collaborations while still offering similarities to improved teacher practice.Research limitations/implicationsThe research was limited to teachers in rural settings in the USA (Texas) and in the Dominican Republic. The research was limited to teacher perceptions of change, and observed changes as part of their participation in a research-based virtual PLC model. The research was limited to the school setting over an academic year.Practical implicationsThe findings from this study have practical implications for rural teachers and school implementation of a professional learning community model.Originality/valueThe promise provided by this study is that vPLCs may provide opportunity for rural schools to provide a job-embedded professional development model (Croft et al., 2010) for otherwise isolated teachers (Barrett et al., 2015).
Place: Bradford Publisher: Emerald Group Publishing Limited Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2338030077?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1108/IJEM-09-2018-0296 2339240:ITBNKNJS 2405685:493XEK9T 2405685:BXCJZXC3 2534378:9DM4HQE9 2534378:BDJAHBNX 2534378:EEJ2GZ6E
Keywords: Collaboration; Communities of Practice; Computer Mediated Communication; ERIC; Current Index to Journals in Education (CIJE); Education; Educational technology; Faculty Development; Learning; Meetings; Preferences; Professional development; Professional learning communities; Rural Schools; Rural schools; School districts; Teacher Attitudes; Teacher Collaboration; Teacher collaboration; Teachers; Teaching; Virtual professional learning communities; __:import:01; __:match:final; __:matched; __:study_id:2095794; __finaldtb

Multilingual literacy transfer in rural South Africa: A technology-based impact study - Castillo, N.; Wagner, D.A. (International Review of Education, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1007/s11159-019-09779-0 2339240:KIHKDCTG 2405685:SIG5VBIC

Government Design Principles - Central Digital and Data Office (GOV.UK, 2019)
The UK government's design principles and examples of how they've been used.
KerkoCite.ItemAlsoKnownAs: 2339240:HEJIHY8U 2405685:R8NQTVRI

Meeting them where they are: The use of Twitter in youth civic education - Chapman, A L (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:CU7ZJ7CJ

Teacher education for realities of 21st century learners in rural South Africa - Chigona, A.; Chigona, W. (Human learning in the digital era, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:ALK9J264 2405685:FW9G3E5R

Educate! RCT 4-Year Follow-On (Interpretation Memo) - Chioda, L; Gertler, L; Gertler, P (2019)
Follow-up to a Randomized Controlled Trial which measured impact on students 4 years after completing the Educate! programme
KerkoCite.ItemAlsoKnownAs: 2339240:6FACMQ2Z 2405685:YKS9CJL2

Can Public Rankings Improve School Performance? Evidence from a Nationwide Reform in Tanzania - Cilliers, Jacobus; Mbiti, Isaac; Zeitlin, Andrew (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BKU3WJ9A 2405685:A72EGY39 4656463:UPYF75H3

Can Public Rankings Improve School Performance? Evidence from a Nationwide Reform in Tanzania - Cilliers, Jacobus; Mbiti, Isaac; Zeitlin, Andrew (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BKU3WJ9A 2405685:A72EGY39 4656463:UPYF75H3

Can public rankings improve school performance? Evidence from a nationwide reform in Tanzania - Cilliers, Jacobus; Mbiti, Isaac; Zeitlin, Andrew (Research on Improving Systems of Education (RISE), 2019)
KerkoCite.ItemAlsoKnownAs: 10.35489/BSG-RISE-WP_2019/027 2339240:8NZV7LWT 2405685:PDZ4MDGU

Can Public Rankings Improve School Performance? Evidence from a Nationwide Reform in Tanzania - Cilliers, Jacobus; Mbiti, Isaac; Zeitlin, Andrew (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BKU3WJ9A 2405685:A72EGY39 4656463:UPYF75H3

Language data for Nigeria - CLEAR Global (2019)
Find information about languages in Nigeria, thanks to our language data, including interactive and static language maps for Nigeria.
KerkoCite.ItemAlsoKnownAs: 2405685:XYMKEPWU 4042040:JHQCMKE9

Payment by results in international development: Evidence from the first decade - Clist, Paul (Development Policy Review, 2019)
Donors would be sensible to limit themselves to either ‘small PbR’ (where the costs of PbR are minimised) or genuine ‘big PbR’ (where projects seek to maximise PBR’s benefits). The current evidence shows that projects outside these two categories are worse than traditional forms of aid. Evidence for ‘small PbR’ is mixed, while there is no evidence for ‘big PbR’ as it has yet to be tried.
KerkoCite.ItemAlsoKnownAs: 10.1111/dpr.12405 2339240:7FJCYSTU 2405685:XNFE2NTT 4656463:IMJ7GRVC

FRAMEWORK FOR STAKEHOLDER INCLUSION IN THE TECHNOLOGY PLANNING PROCESS - CoAction Learning Lab (Penn State COACTION LEARNING LAB, 2019)
zotzenLib.CopiedFrom: 2339240:7JSJ8J8R KerkoCite.ItemAlsoKnownAs: 2339240:7JSJ8J8R 2405685:T8SP8NAM

Great Teaching Toolkit: Evidence Review - Coe, Rob; Rauch, C.J.; Kime, Stuart; Singleton, Dan (Evidence Based Education, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:4IL87MTM
Keywords: C:England/International

Transforming Teacher Education and Learning in Ghana: The Impact of a Continuous Professional Development on Physics Teaching at the Colleges of Education - Coffie, Isaac Sonful (International journal of Research and Scientific Innovation, 2019)
The colleges of education in Ghana have been involved in a continuous professional development for over four years with support of Transforming Teacher Education and Learning (T-TEL). The main purpose of this research was to assess the perceived impact of the continuous professional programme on physics teaching at the colleges of education. Descriptive cross sectional survey was used for the study. An online survey was conducted which was completed by 85 physics tutors. The survey data were analysed using means and standard deviations and ANOVA. It was found that the professional development is perceived by the physics tutors to have great impact on their teaching practice. It was also found out that there was no statistical significant difference in the perceived impact of the professional development based on tutors’ experience. It was concluded that if the student teachers who are being trained by these tutors will learn these ideas from their tutors and practice them, teaching at the basic schools will be more interactive, students-centered and gender responsive.
EdTechHub.ItemAlsoKnownAs: 2405685:IPJBNU3S
Keywords: ⛔ No DOI found

Blockchain Goes to School - Cognizant (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:HRWJ4MFX 2405685:RDV6F68H

Second Quarter Statistics Report for the Financial Year 2019/2020 - Communications Authority of Kenya (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:3QABM8GW

Human development report 2019: beyond income, beyond averages, beyond today: inequalities in human development in the 21st century - Conceição, Pedro; United Nations Development Programme (2019)
OCLC: 1130905759 KerkoCite.ItemAlsoKnownAs: 2339240:EFRSRANV 2405685:SNQDEQWB 2405685:VXDMBKGS

Innovative Delivery of Education in Bangladesh Using Mobile Technology - Cristol, Dean; Abdulbaki, Anwar; Tuhin, Salah Uddin; Al-Sabbagh, Samah; Majareh, Maryam; Gimbert, Belinda (2019)
Given the increasing use and accessibility of mobile technology, a pilot study, “Innovative Delivery of Education in Bangladesh Using Mobile Technology” was carried out using mobile learning devices to both increase and enrich the delivery of educational services in a remote Bangladesh district. The APTUS system was used to allow learners’ connection to digital learning platforms and content without electricity or internet access. The researchers maintained that mobile learning associated with Project Based Learning can effect student learning in five ways: (1) contingent learning, changing experience students have by responding to the environment; (2) situated learning, in which learning occurs in the conditions applicable to the learning; (3) authentic learning connected to immediate learning goals; (4) context-aware learning, in which the environment and history affect learning; and (5) personalized learning. The results from this pilot research study provides evidence of the students achievement growth overtime and motivated to learn higher-order thinking technology enhanced skills when practical applications are supplemented with technology tools such as tablets. Students reported a heightened interest in science as a result of the project. Teachers maintained that their teaching skills were enhanced by the project and able to apply practical applications to teach science rather than lecturing and rote learning. Parents attributed the project for their children being more motivated to learn science inside and outside of the classroom. The study appears to have a positive impact on the three groups of the participants and should be scaled up to benefit more learning communities, especially in remote areas of Bangladesh.
KerkoCite.ItemAlsoKnownAs: 2339240:UXGNF73S 2405685:MVSQSM9B
Keywords: ⛔ No DOI found

Mobile learning and student cognition: A systematic review of PK-12 research using Bloom’s Taxonomy - Crompton, Helen; Burke, Diane; Lin, Yi-Ching (British Journal of Educational Technology, 2019)
The rise of mobile learning in schools during the past decade has led to promises about the power of mobile learning to extend and enhance student cognitive engagement. The purpose of this study was to examine trends to determine the cognitive level students are involved in within mobile learning activities. This systematic review involved an aggregated and configurative synthesis of PK-12 mobile learning studies from 2010 to 16 and used Bloom’s Taxonomy as a theoretical framework for categorizing the cognitive level of student activities. Major new findings include that students are involved in activities at all six levels of Bloom’s Taxonomy. This study shows that over 60% of researchers are developing activities that require high levels of cognitive processing, a large increase from past studies. Nonetheless, 40% are integrating mobile devices in ways that keep students working with minimal cognitive processing. In both elementary and secondary studies, there was a 40/60% split in the use of lower versus high level thinking opportunities. New findings show that mobile devices were integrated into science, mathematics, social studies, literacy, art and special education. Studies in science settings were the majority of the studies (40%), followed by literacy (24%).
shortDOI: 10/gf5f7g KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12674 10/gf5f7g 2339240:ITSJB3B5 2339240:KIEJIK2D 2405685:J23Q8BH4
Keywords: Reviewed

Meeting the data challenge in education. A knowledge and innovation exchange (KIX) discussion paper | Documents | Global Partnership for Education - Crouch, L (GPE, 2019)
The purpose of this paper is to describe the current landscape in education data systems and spark discussion and debate around potential areas for KIX investment.
Publisher: GPE KerkoCite.ItemAlsoKnownAs: 2339240:JCMTRFJJ 2405685:EPWQ79FB

Meeting the data challenge in education: A knowledge and innovation exchange - Crouch, Luis (Global Partnership for Education, 2019)
The purpose of this paper is to describe the current landscape in education data systems and spark discussion and debate around potential areas for KIX investment.
KerkoCite.ItemAlsoKnownAs: 2339240:3KBXHSD9 2339240:PYIIMTJL 2405685:FK24U2VZ 2405685:NNIMTDB4 2405685:PCB2NZJ6 2534378:K8UUXZMX
Keywords: ___working_potential_duplicate

Technology use to support employment-related outcomes for people with intellectual and developmental disability: An updated meta-analysis - Damianidou, Despoina; Arthur-Kelly, Michael; Lyons, Gordon; Wehmeyer, Michael L. (International Journal of Developmental Disabilities, 2019)
The aim of this study is to update and extend an original meta-analysis which included papers published up to and including 2003 and investigated the impact of technology use on employment-related outcomes for people with intellectual and developmental disability. Following on from the original meta-analysis, this study is a meta-analysis of pertinent single-subject experimental design studies conducted from 2004 to 2016 and employs the same metric methods as the original contribution. The results are generally consistent with those of the original meta-analysis, namely, applied cognitive technology effectively supports employment-related outcomes for people with intellectual and developmental disability. Nevertheless, significant differences in the intervention effects were found (a) between groups of individuals with varying levels of disability, and (b) between interventions utilizing technology with and without universal design features. In line with the original contribution, applied cognitive technology seems to support people with intellectual and developmental disabilities to better achieve employment-related outcomes. More research is needed though to explore the impact of different types of technology on employment-related outcomes.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/20473869.2018.1439819 KerkoCite.ItemAlsoKnownAs: 10.1080/20473869.2018.1439819 2339240:Q5FSHPVP 2405685:HCJKEZX4

Creativity level of hearing impaired and hearing students of Federal College of Education - Daramola, Dorcas Sola; Bello, Muhinat Bolanle; Yusuf, Abdul Raheem; Amali, Ismaila Oteikwu O. (International Journal of Instruction, 2019)
This study investigated creativity Level of Hearing Impaired and Hearing Students of Federal College of Education in Oyo. Specifically, the study investigated the creativity level of hearing and hearing-impaired students. Also, a relationship between gender and onset of hearing loss and students’ creativity level were found out. A descriptive survey design was adopted for this study. A purposive sampling technique was used to sample a total of 248 second year students Nigerian Certification in Education (NCE II) of the School of Education who participated in the study. A researcher-designed questionnaire with a reliability coefficient of 0.76 was used to collect data for the study. The Findings showed that the creativity level of hearing-impaired students is significantly higher compared to their hearing peer. It was revealed that female hearing impaired students significantly show a higher level of creativity than their male peer. Also, post-lingual hearing-impaired students are significantly higher in creativity level than their pre-lingua peers. Based on these findings, it was recommended that mainstreaming approach of providing education services adopted by Federal College of Education in Oyo should be strengthened and adopted in all institution where hearing and hearingimpaired attend.
7 citations (Crossref) [2024-04-17] KerkoCite.ItemAlsoKnownAs: 10.29333/iji.2019.12195a 2339240:C9TNMLH5 2405685:SFTIE96U
Keywords: ⛔ No INSPIRE recid found

Assessment of the Impact of the Jovem de Futuro Program on Learning - de Barros, Ricardo Paes; de Carvalho, Mirela; Franco, Samuel; Garcia, Beatriz; Henriques, Ricardo; Machado, Laura (World Bank, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:2GLYDRF3 2405685:67VRVQEZ

No lost generation: Supporting the school participation of displaced Syrian children in Lebanon - de Hoop, Jacobus; Morey, Mitchell; Seidenfeld, David (Journal of Development Studies, 2019)
This study documents the impact of a cash transfer programme–known as the No Lost Generation Programme (NLG) and locally as Min Ila (‘from to’)–on the school participation of displaced Syrian children in Lebanon. An initiative of the government of Lebanon, the United Nations Children’s Fund (UNICEF), and the World Food Programme (WFP), the programme provided cash for the benefit of children enrolled in afternoon shifts at public primary schools. It was designed to cover the cost of commuting to school and to compensate households for income forgone because children were attending school instead of working. Commuting costs and forgone income are two critical barriers to child school participation. The analysis relies on a geographical regression discontinuity design to identify the impact halfway through the first year of programme operation, the 2016/2017 school year. The analysis finds substantive impacts on school attendance among enrolled children, which increased by 0.5 days to 0.7 days per week, an improvement of about 20 per cent relative to the control group. School enrolment among Syrian children rose rapidly across all Lebanon’s governorates during the period of the evaluation, resulting in supply-side capacity constraints that appear to have dampened positive enrolment impacts.
Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.1080/00220388.2019.1687875 2405685:6254DV2I

Scaling Education Innovations in Complex Emergencies: Evidence From the Humanitarian Education Accelerator - De Hoop, Thomas; Ring, Hannah; Coombes, Andrea; Rothbard, Victoria; Holla, Chinmaya; Hunt, Kelsey; Seidenfeld, David; Connolly, Helen (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:6RQFWXFN 2405685:IVXZWTVS

Education Statistical Abstract 2016-2018 (Unpublished) - Department of Planning, Policy and Research (The Ministry of Education and Vocational Training, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:8VVC4TYA 2405685:EE4V6GP2

Research into Digital Accessibility and Literacy among School Teachers in Punjab: Research Report - DevTrio Consultants (British Council, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:C7T2UTEY

Blended learning to improve quality of primary education among underprivileged school children in India - Dey, P.; Bandyopadhyay, S. (Educ Inf Technol, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-018-9832-1 2339240:GQ3CAK7A 2405685:5J63UE5Q
Keywords: ⛔ No INSPIRE recid found

Realising the potential of technology in education: A strategy for education providers and the technology industry - DfE (Department for Education) (Department for Education, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:5UWKJNTD 2405685:R2I7U6ZD

DFID ethical guidance for research, evaluation and monitoring activities - DFID (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:DYKR49HK 2129771:MLJ8DYDF 2129771:XH8PYE58 2339240:NSUHFAGV 2405685:KMWTSU7N 2405685:WIMGWF8H
Keywords: ⛔ No DOI found

VfM Guidance: The 4th E Equity External Version - DFID (Department for International Development, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:HMCK3CL2 2405685:44MY29ZM

Understanding the Allocation of Public Personnel Across Government Health Facilities in Ghana - Diop, Binta Zahra; Awoonor-Williams, Koku; Ofosu, Anthony; Williams, Martin J (2019)
In order to deliver public services, governments must allocate scarce human and ﬁnancial resources across their territories, yet there is little systematic evidence on the productivity of these inputs or allocative eﬃciency with which governments allocate them. We study this by leveraging a unique panel dataset of service delivery, health outcomes, and human and ﬁnancial inputs in the universe of over 5,000 public health facilities in Ghana. Our research design allows us to estimate the marginal returns to health personnel and inputs, while controlling for unobserved heterogeneity across facilities. We document the roles and current distribution of the diﬀerent types of health workers and facilities within the health system, and investigate the relationship between patient volume and the number of health workers in a facility. We discuss implications for optimal staﬃng allocations and further research.
KerkoCite.ItemAlsoKnownAs: 2339240:HZJI434B 2405685:FWKIXDSV 4656463:5KM5I7B7
Keywords: ⛔ No DOI found

Bangladesh Primary Education Annual Sector Performance Report 2019 - Directorate of Primary Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:YZZV53KC 2405685:BZR78EKI

Government of Sierra Leone Education Data Hub - Directorate of Science, Technology and Innovation (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:8BAXTEYI 2405685:46EQS5JF

Sierra Leone National Innovation and Digital Strategy (2019-2029). Digitization for all: Identity, Economy, and Governance - Directorate of Science, Technology & Innovation (Government of Sierra Leone, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:Q6QR6YET 2339240:Q8HXYPXT 2339240:ZAK6UTWJ 2405685:65CSGZUZ 2405685:ALD9DQ6P 2405685:GWCHFY72 2405685:XG7MKFV5

Transforming the Education Workforce: Learning teams for a learning generation - Education Commission (Education Commission, 2019)
The Education Commission's vision to strengthen, diversify, and transform the education workforce to deliver inclusive, quality education for all.
KerkoCite.ItemAlsoKnownAs: 2339240:HFEU63QF 2339240:KAFI2DU8 2339240:Y46JESVZ 2405685:7JBG673D 2405685:AG66GV8B 2405685:J99WFZ9L 2405685:MF5UMTVS 2405685:PBVSSI2T 2405685:RZINF2DS 2534378:UMCUKS9F
Keywords: C: International; ___working_potential_duplicate

Abracadabra (ABRA) - Education Endowment Foundation (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:YLWE42F5

A Rapid Evidence Assessment of the effectiveness of educational interventions to support children and young people with multi-sensory impairment. - Ellis, L; Douglas, G; Hewett, R; McLinden, T; Terlektsi, E; Wotten, AM; Ware, J; Williams, L (Welsh Government, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:5DZTY8BD 2405685:2FIF7LND

KitKit School Impact Summary 2016–2019 - Enuma, Inc. (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RKCPRAQV 2405685:W4BKKGG8

Digital Skills and Online Learning in Ukraine: Digital Factsheet December 2019 - European Training Foundation (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:UNAKY926 2405685:DK62F737

ICT in girl-child education, a key factor for national development in Nigeria - Ezzeh, Peace Oguguo; Okoh, Kate Chinwe (South Eastern Journal of research and sustainable development (SEJRSD), 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:46IKDKTG 2405685:9DS3MGJB
Keywords: Equity through Access; System Readiness; ⛔ No DOI found; ⛔ No INSPIRE recid found

Use of ICT by Biology Teachers in the Secondary Schools: Bangladesh Perspective - Farhana, Z; Chowdhury, S (Journal of Culture, Society and Development, 2019)
Information and communication technologies (ICT) have changed the pedagogy in education offering more student-centered learning incidents. The purpose of this study was to evaluate the use of ICT by the biology teachers in teaching-learning process of secondary schools in Bangladesh. A total of 50 biology teachers from several secondary schools of Bangladesh participated in the study. It was found that teachers have better access to computer than the average populace of Bangladesh. They have working knowledge on Microsoft Office Word, Excel, Power Point, and different web browsers. A good number of the teachers use computer for preparing their lectures, use internet for accessing educational materials, takes classes with multimedia with the support of ICT. However, about 17% to 25% were found to be not using these ICT means. Many teachers opined that they have less number of computers in the school to prepare for class work. They also assessed that hardware troubleshooting, software malfunction and unexpected power failure as challenges for using ICT. This paper recommends to provide continuous in-servicing training on ICT, interest free loan to teachers for purchasing laptop computer and to ensure technical support to overcome software and hardware problems in the schools.
KerkoCite.ItemAlsoKnownAs: 10.7176/jcsd/45-05 10/gj37jj 2339240:R2I6C4KK 2405685:8YK9A8A2

National Digital Economy Policy and Strategy (2020-2030) - Federal Ministry of Communications and Digital Economy (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:3QAF4JC5 2405685:LIDB763M

National Implementation Guidelines for ICT in Education - Federal Ministry of Education (Federal Republic of Nigeria, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:YDFAS5EL

National Policy on ICT in Education - Federal Ministry of Education (Federal Republic of Nigeria, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:MDRRF95U

National Policy on Information and Communication Technologies (ICT) in Education - Federal Ministry of Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:VMGSJVIK 2405685:DF87HNJG

Mobile Solutions Technical Assistance and Research (mSTAR) - FHI360 (2019)
The FHI 360 Mobile Solutions Technical Assistance and Research (mSTAR) project, funded by the U.S. Agency for International Development (USAID), increased access to and use of mobile and digital technologies by low-income individuals, civil society, local government institutions and private-sector stakeholders.
Library Catalog: www.fhi360.org EdTechHub.ItemAlsoKnownAs: 2405685:XJSKZQMC

A cognitive assessment tool designed for data collection in the field in low-and middle-income countries - Ford, Cassie B.; Kim, Ha Yeon; Brown, Lindsay; Aber, J. Lawrence; Sheridan, Margaret A. (Research in Comparative and International Education, 2019)
The Rapid Assessment of Cognitive and Emotional Regulation (RACER) is a tablet-based assessment tool for children that measures executive function (EF) skills. Instructions that are brief and visually presented; game-like tasks are designed to easily engage children regardless of literacy level and variable test administration settings. RACER measures inhibitory control and working memory. This study presents the theoretical rationale and empirical evidence for tablet-based assessments of EF, the process of administering the RACER assessments. The current sample consists of students in Lebanon (N=1900) and Niger (N=850). The results indicate that individual differences in EF can be assessed by the RACER tablet tasks. Specifically, we demonstrate that EF scores are associated in expected ways with age and that tasks function similarly to what has been observed in high-income countries. The feasibility and utility for researchers, practitioners, and clinicians, of this cognitive assessment tool is discussed.
shortDOI: 10/ggcdmq KerkoCite.ItemAlsoKnownAs: 10.1177/1745499919829217 10/ggcdmq 2339240:LIPC5YY2 2339240:TL333DE5 2339240:XVBLDC46 2339240:Z5BEQNRN 2405685:3PXAARND 2405685:JSZ4DA4J 2405685:K8AE89HH

Playing Every Day on Sesame Street - Foulds, Kim; Bucuvalas, Abby (American Journal of Play, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:87NLH2N4 2405685:CNFZA5YN
Keywords: ⛔ No DOI found

Rethinking research partnerships: Evidence and the politics of participation in research partnerships for international development - Fransman, Jude; Newman, Kate (Journal of International Development, 2019)
This article responds to the drive for research partnerships between academics and practitioners, arguing that while potential benefits are clear, these are frequently not actualized resulting in partnerships that are ineffectual or worse, exacerbate damaging or inequitable assumptions and practices. In order to understand/improve partnerships, a systematic analysis of the interrelationship between what counts as evidence and dynamics of participation is proposed. Drawing on data from a seminar series and iterative analysis of seven case studies of partnerships between Higher Education Institutions and International Non-Governmental Organisations, the article concludes by suggesting substantial shifts in the theory and practice of partnerships. © 2019 The Authors Journal of International Development Published by John Wiley & Sons Ltd
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/jid.3417
Keywords: INGOs; evidence; higher education; knowledge and power; participation; research partnerships

Liberia: Framework and Strategy Drawn up at UNESCO-MOE ICT in Education Policy Workshop - Front Page Africa (2019)
MONROVIA – UNESCO Liberia over the weekend ended a two-day workshop in Monrovia on ICT in Education, with participants building a consensus on a framework and strategy for a draft national policy on ICT in Education in country. The workshop is part of a UNESCO-CFIT project sponsored by the People’s Republic of China in collaboration […]
Library Catalog: frontpageafricaonline.com KerkoCite.ItemAlsoKnownAs: 2339240:KFUWVVA9 2405685:3L33SBJW

Funda Wande - YouTube - Funda Wande (2019)
Funda Wande is a not-for-profit organisation that aims to ensure that all learners in South Africa can read for meaning in their home language by the age of 10. We develop video and print materials to train teachers how to teach reading for meaning in Grades R–3. All our materials are freely available and are Creative Commons licensed, so anyone can use them. www.fundawande.org
KerkoCite.ItemAlsoKnownAs: 2339240:LECWHUV3 2405685:49D5RUBG

Cameras in the classroom: Facial recognition technology in schools - Galligan, Claire (University of Michigan, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F3637ZJ8 2405685:XVF9F5NU

GDPR Definitions - GDPR (GDPR-Text.com | GDPR Text, Translation and Commentary, 2019)
For the purposes of this Regulation:...
KerkoCite.ItemAlsoKnownAs: 2339240:ERWQGLKM 2405685:VNDD6W74

Gender differences in computer and information literacy: An in-depth analysis of data from ICILS - Gebhardt, Eveline; Thomson, Sue; Ainley, John; Hillman, Kylie (Springer Nature, 2019)
This open access book presents a systematic investigation into internationally comparable data gathered in ICILS 2013. It identifies differences in female and male students’ use of, perceptions about, and proficiency in using computer technologies. Teachers’ use of computers, and their perceptions regarding the benefits of computer use in education, are also analyzed by gender. When computer technology was first introduced in schools, there was a prevailing belief that information and communication technologies were ‘boys’ toys’; boys were assumed to have more positive attitudes toward using computer technologies. As computer technologies have become more established throughout societies, gender gaps in students’ computer and information literacy appear to be closing, although studies into gender differences remain sparse. The IEA’s International Computer and Information Literacy Study (ICILS) is designed to discover how well students are prepared for study, work, and life in the digital age. Despite popular beliefs, a critical finding of ICILS 2013 was that internationally girls tended to score more highly than boys, so why are girls still not entering technology-based careers to the same extent as boys? Readers will learn how male and female students differ in their computer literacy (both general and specialized) and use of computer technology, and how the perceptions held about those technologies vary by gender.
Accepted: 2020-03-18 13:36:15 Journal Abbreviation: An In-depth Analysis of Data from ICILS KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-26203-7 2339240:WGHTZ8T5 2405685:7BDLRHWK

Completed results of the 2019 Viet Nam population and housing census - General Statistics Office of Vietnam (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QS7WZ2JG 2405685:WTG9SX44
Keywords: ⛔ No INSPIRE recid found

Complexity leadership theory:: a framework for leading in Australian early childhood education settings - Gibbs, Leanne; Press, Frances; Wong, Sandie (Leadership in Early Education in Times of Change, 2019)
This conceptual and theoretical chapter focuses upon the challenges and opportunities of leading in Australian early childhood education (ECE). Leading and leadership in ECE is enacted within a complex landscape comprising complicated legislation, a volatile workforce, comprehensive standards of practice and a diversity of children and families. In that context, the chapter highlights the perceptions that reinforce the challenges of leading in ECE and goes on to discuss an alternative theoretical framework; -complexity leadership theory and complex adaptive systems theory. This framework is proposed as a way of thinking about the emergence of leadership in an environment where educators can
KerkoCite.ItemAlsoKnownAs: 10.2307/j.ctvmd84fc.16 2339240:QSK8QXYM 2405685:EVWY4XH8

The State of ICT in Mozambique 2018 - Gillwald, Alison; Mothobi, Onkokame; Rademan, Broc (Research ICT Africa, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:V2EULQWJ 2405685:H466JLKG
Keywords: ⛔ No INSPIRE recid found

Effect of re-entry policy implementation on readmitted girls’ academic performance in mathematics in selected secondary schools of Mufulira District in Zambia - Gladys, Nsalamba; Alex, Simpande (International Journal of Data Science and Analysis, 2019)
Zambia is one of the countries in the Sub-Sahara Africa that has an established Re-Entry Policy. The policy was declared in 1997 and allows pregnant school girls to go to school. The aim is to create academically healthy learning institutions in which both girls and boys are free. As per findings of this research, the Re-Entry Policy has helped reduce gender discrepancies in terms of equity in education. Sad though, the paper has reviewed that most reentered girls fail mathematics, a thing that disadvantages them because mathematics is used as criteria of purity for admission into university and well-paid jobs. As such, the purpose of this study was to investigate the effect of Re-Entry Policy implementation on readmitted girl’s performance in mathematics. In order to achieve this aim, a qualitative research approach guided by some research questions and objectives was undertaken. Data relating to the research was collected through interview guides and questionnaires, and analyzed using narrative techniques. Furthermore, purposive sampling technique was used because the study targeted a specific group of people and characteristics. The conclusion made through the findings of this paper were that the perceived poor performance in mathematics by reentered girls is a ‘socio construct’ and not solely due to the Re-Entry Policy. This implies that the implementation of the policy is what is key; hence, the variations in performance for reentered girls in individual schools.
KerkoCite.ItemAlsoKnownAs: 10.11648/j.ijdsa.20190505.11 2339240:4IEBB4NH 2405685:B89SQIGF

Curriculum Leadership - Glatthorn, A; Boschee, F; Whitehead, B; Boschee, B (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QDYREIE8 2405685:MK6VHNE4

Achieving gender equality in and through education - Global Partnership for Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:PJLSZJIL 2405685:MYN2NRGK

Pakistan (Balochistan): Using technology to bring education to the most remote areas - Global Partnership for Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:X8TQADM6 2405685:8C795EZ9

Inclusive data charter - Global Partnership for Sustainable Development Data (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:JR7S3TSD 2405685:2LBXPGMA

What’s most broken? A tool to assist data-driven iterative improvement of an intelligent tutoring system - Goswami, Mononito; Mian, Shiven; Mostow, Jack (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
Number: 01 KerkoCite.ItemAlsoKnownAs: 10.1609/aaai.v33i01.33019941 2339240:3SW7MPDM 2405685:YURLY5VP

The Personal Data Protection Bill - Government of India (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:6FDVNC76 2405685:VDBFPWZS

The County Allocation of Revenue Bill, 2019 - Government of Kenya (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:HBM87LKU

National ICT Policy (2019-2024) - Government of Liberia (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:742YQUUN

Pakistan Economic Survey 2018–19 - Government of Pakistan. Economic Adviser's Wing, Finance Division (Government of Pakistan, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:KNTFZ89B
Keywords: auto_merged

Sierra Leone’s Medium-Term National Development Plan 2019-2023: Education for Development. - Government of Sierra Leone (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RPKBXC8H 2405685:XNWLCKWJ

ESSP Contract 2019: Example partnership contract - Government of Sindh (Government of Sindh, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:JUWLIC7T 2405685:IHHEEJET 4656463:WIQKWWML

School Education Sector Plan and Roadmap for Sindh - Government of Sindh (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:BWRZQRFU

School Education Sector Plan and Roadmap for Sindh (2019–2024) - Government of Sindh. School Education & Literacy Department (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:HIXLP8XY 2405685:EQ4B5935 2405685:EV5Y3ETE
Keywords: ___working_potential_duplicate

Plan national stratégique de développement (PNSD) 2019-2023 - Government of the Democratic Republic of the Congo (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:NI3KENSY 2405685:CJFUL356

Punjab Education Sector Plan 2019/20–2023/2024 - Government of the Punjab (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:ATSY7HWB
Keywords: ___working_potential_duplicate; auto_merged

Punjab Education Sector Plan (2019-2024) - Government of the Punjab (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:6NJ2RV3L

Education Amendment Act - Government of Zimbabwe (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:AGMIFLQB

Meeting the data challenge in education. A knowledge and innovation exchange (KIX) discussion paper | Documents | Global Partnership for Education - GPE (GPE, 2019)
The purpose of this paper is to describe the current landscape in education data systems and spark discussion and debate around potential areas for KIX investment.
KerkoCite.ItemAlsoKnownAs: 2339240:QLLLFLC4 2405685:XMDKWKPS 4656463:8GKMQBH2

Using technology to bring education to the most remote areas - GPE (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:ACEKM42F 2405685:DG7BRX4X

Using technology to bring education to the most remote areas - GPE (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:ACEKM42F 2405685:DG7BRX4X

Outcomes of the Education Data Solutions Roundtable - GPE and Education Data Solutions Roundtable (2019)
This document’s intent is to support developing country partners by offering concrete, actionable recommendations for improving their education sector data production, flows, reporting and usage.
KerkoCite.ItemAlsoKnownAs: 2339240:9XIDS2VQ 2405685:QQHWSN5A 4656463:59CUBSHX

Technology acceptance model in educational context: A systematic literature review - Granić, Andrina; Marangunić, Nikola (British Journal of Educational Technology, 2019)
A respectable amount of work dealing with Technology Acceptance Model (TAM) clearly indicates a popularity of TAM in the field of technology acceptance in general. Nevertheless, there is still a gap in existing knowledge regarding representative academic literature that underlie research on TAM in educational context. The main objective of this systematic literature review is to provide an overview of the current state of research efforts on TAM application in the field of learning and teaching for a variety of learning domains, learning technologies and types of users. Through systematic search by the use of EBSCO Discovery Service, the review has identified 71 relevant studies ranged between 2003 and 2018. The main findings indicate that TAM and its many different versions represent a credible model for facilitating assessment of diverse learning technologies. TAM's core variables, perceived ease of use and perceived usefulness, have been proven to be antecedent factors affecting acceptance of learning with technology. The paper identifies some gaps in current work and suggests areas for further investigation. The results of this systematic review provide a better understanding of TAM acceptance studies in educational context and create a firm foundation for advancing knowledge in the field. Practitioner Notes What is already known about this topic Technology acceptance research in teaching and learning context has become an attractive trend. A number of reviews and meta-analysis focused on specific topics related to technology acceptance in education have been conducted. The Technology Acceptance Model (TAM) is the key model in understanding predictors of human behaviour towards potential acceptance or rejection of the technology. What this paper adds The state of current research on Technology Acceptance Model application in educational context lacks comprehensive reviews addressing variety of learning domains, learning technologies and types of users. The paper presents systematic review of relevant academic literature on Technology Acceptance Model (TAM) in the field of learning and teaching. The paper provides empirical evidence on the predictive validity of the models based on TAM presented in selected literature. The findings revealed that TAM, along with its many different versions called TAM++, is a leading scientific paradigm and credible model for facilitating assessment of diverse technological deployments in educational context. TAM's core variables, perceived ease of use and perceived usefulness, have been proven to be antecedent factors that have affected acceptance of learning with technology. Implications for practice and/or policy The systematic review adds to the body of knowledge and creates a firm foundation for advancing knowledge in the field. By following the most common research objectives and/or by filling current gaps in applied research methods, chosen sample groups and types of result analysis, an own study could be conducted. Future research may well focus on identifying additional external factors that could further explain acceptance and usage of various learning technologies.
shortDOI: 10/gf5f7d KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12864 10/gf5f7d 2339240:UDAZ2J5E 2405685:2JHVIT8F

Facilitating innovation with technology: Key actors in educational ecosystems - Gu, Xiaoqing; Crook, Charles; Spector, Mike (British Journal of Educational Technology, 2019)
shortDOI: 10/ggfwhs KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12786 10/ggfwhs 2339240:39M39SXM 2339240:EFRE7X2P 2405685:442VMQ2C 2405685:DBTEPLR6

Measuring early learning and development across cultures: Invariance of the IDELA across five countries - Halpin, Peter F.; Wolf, Sharon; Yoshikawa, Hirokazu; Rojas, Natalia; Kabay, Sarah; Pisani, Lauren; Dowd, Amy Jo (Developmental Psychology, 2019)
Relatively little research has addressed whether conceptual frameworks of early learning generalize across different national contexts. This article reports on a cross-country measurement invariance analysis of the International Development and Early Learning Assessment (IDELA). The IDELA is a direct assessment tool for 3- to 6-year-old children, intended to measure Early Literacy, Early Numeracy, Motor, and Social-Emotional development. Its generalizability is evaluated using samples from 5 countries: Afghanistan (N = 2,629); Bolivia (N = 480); Ethiopia (N = 682); Uganda (N = 504); and Vietnam (N = 675). The 4-domain model of the IDELA was supported in each country, although the domains were highly correlated. Measurement invariance analysis revealed that most IDELA items do not provide a basis for comparing children’s development over the 5 countries. This research supports the use of the IDELA for program evaluation and within-country monitoring purposes, but cautions against its use for international comparisons. (PsycINFO Database Record (c) 2019 APA, all rights reserved)
Place: US Publisher: American Psychological Association KerkoCite.ItemAlsoKnownAs: 10.1037/dev0000626 2339240:U6QIJ4Q9 2405685:GH3YI788
Keywords: Countries; Cross Cultural Differences; Early Childhood Development; Emotional Development; Generalization (Learning); Learning; Literacy; Mathematical Ability; Measurement; Motor Development; Psychosocial Development; Test Construction

What is an ecological approach and how can it assist in understanding ICT take-up? - Hammond, Michael (British Journal of Educational Technology, 2019)
This paper argues that ecological frameworks offer a powerful way of explaining the take-up of information and communication technology (ICT) in schools. Past research has focused on teachers and their willingness and readiness to use ICT but this has not satisfactorily explained the use (or non-use) of ICT. Gaps in this research can be addressed by an ecological approach which shifts attention from the teacher to the context in which ICT is expected to be used. Such an approach, following Bronfenbrenner and others, looks at the relationship of individuals to the system in which they act, a relationship which is seen as interdependent. An ecological perspective explains how take-up of ICT is influenced by the degree to which different levels of a system, eg, micro, meso, exo and macro levels, are aligned. It is recommended that researchers and policy makers should pay greater attention to context when advocating the use of ICT.
shortDOI: 10/ggf5gb KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12889 10/ggf5gb 2339240:2JN64RFF 2339240:KIW5RY6Y 2339240:M2AJGK69 2339240:XRN7BCP5 2405685:2DYHWMKY 2405685:9NRLBU5A 2405685:GY9VCUGX 2405685:P9WACL45

Systems Leadership for Learning - Haßler, Björn (Open Development & Education, 2019)
EdTechHub.Copy: 2129771:H3CR3Q8S shortDOI: 10/gg26c7 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.2626704 10.5281/zenodo.3595400 10/gg26c7 2129771:H3CR3Q8S 2339240:EXPQPHYQ 2405685:F7MH9IWP
Keywords: _DOILIVE; _not_EdTechHub; _yl:a; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Berufsbildung in Sub-Sahara Afrika: Stand der Forschung - Haßler, Björn; Stock, Inka; Schaffer, Jens; Winkler, Enno; Kagambèga, Assèta; Haseloff, Gesine; Marsden, Melissa; Watson, Joe; Gordon, Rebecca; Damani, Kalifa (VET Repository, Bundesinstitut für Berufsbildung, Bonn, Germany, 2019)
urn:nbn:de:0035-vetrepository-775510-9 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3334690 2317526:XAXNF68P 2339240:GVETNP2S 2405685:6QK46DKT 2405685:946X9BZX
Keywords: _DOILIVE; _not_EdTechHub; _yl:c; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Software review: COCI, the OpenCitations Index of Crossref open DOI-to-DOI citations - Heibi, Ivan; Peroni, Silvio; Shotton, David (Scientometrics, 2019)
Abstract In this paper, we present COCI, the OpenCitations Index of Crossref open DOI-to-DOI citations ( http://opencitations.net/index/coci ). COCI is the first open citation index created by OpenCitations, in which we have applied the concept of citations as first-class data entities, and it contains more than 445 million DOI-to-DOI citation links derived from the data available in Crossref. These citations are described using the resource description framework by means of the newly extended version of the OpenCitations Data Model (OCDM). We introduce the workflow we have developed for creating these data, and also show the additional services that facilitate the access to and querying of these data via different access points: a SPARQL endpoint, a REST API, bulk downloads, Web interfaces, and direct access to the citations via HTTP content negotiation. Finally, we present statistics regarding the use of COCI citation data, and we introduce several projects that have already started to use COCI data for different purposes.
KerkoCite.ItemAlsoKnownAs: 10.1007/s11192-019-03217-6 2405685:PITG898L

Where is the “theory” within the field of educational technology research? - Hew, Khe Foon; Lan, Min; Tang, Ying; Jia, Chengyuan; Lo, Chung Kwan (British Journal of Educational Technology, 2019)
Critics often characterise the study of educational technology as under-theorised. To test this assertion and to determine the extent of this criticism, the present paper reports an in-depth analysis of the 503 most recent empirical articles published in three selected education-technology-related journals (Computers & Education; Learning, Media and Technology; and British Journal of Educational Technology). These journals were selected because they publish studies related to all education settings rather than focusing on only a certain segment such as higher education; they have broad geographical catchment; and they were the most highly ranked journals in terms of their 2017 journal citation impact factor. The present paper examines how explicitly existing theory was identified in previous research, how theories were applied and how often these theories were advanced in education technology research. In the majority of cases, explicit engagement with theory was absent. Many studies either were wholly bereft of theories or made vague use of theory. Where theory was explicit, the articles were more likely to use theory to conceptualise the research, to inform the data collection or analysis process and to discuss the results. Very few articles reported findings that help us to learn something new about a particular theory (ie, little evidence of theory advancement).
shortDOI: 10/ggfwht KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12770 10/ggfwht 2339240:CK56VJL5 2339240:UB5ENBCI 2405685:WFXYS36Q 2405685:Z25HD3K7

School factors related to the emotional wellbeing and resettlement outcomes of students from refugee backgrounds: Protocol for a systematic review - Horswood, Deserae; Baker, Jess; Fazel, Mina; Rees, Susan; Heslop, Linda; Silove, Derrick (Systematic Reviews, 2019)
Background: Schools can play a vital role in the resettlement of refugee children and their families. Yet, the body of research examining school environmental factors that support the mental health and acculturation of refugee children is methodologically heterogeneous, investigates numerous and disparate school factors, and is often "hidden" in broader qualitative studies. This limits the capacity to apply the findings in a practical manner. Methods: Based on PRISMA statement principles, we review the relevant literature to investigate the relationship between school climate and the emotional wellbeing and resettlement outcomes of refugee students. Six electronic databases will be systematically searched: MEDLINE, PsycINFO, Embase, CINAL, Web of Science, and ERIC, supplemented by a systematic review of the grey literature, relevant international websites, and sequential, site-specific internet searches. Finally, subject area experts will be consulted and backward and forward citation searches of included articles will be completed. Two independent reviewers will screen identified articles against eligibility criteria and extract data for included studies. Quality of included studies will be assessed using the Mixed Methods Appraisal Tool (MMAT) for mixed studies reviews. Data will be synthesised using a convergent qualitative narrative approach. Discussion: Given the centrality of school in the daily lives of resettled refugee children, it is vital to assess the impact of school climate on the psychosocial wellbeing and resettlement trajectories of this population. This review will identify evidence-based school factors which support good mental health and resettlement outcomes for refugee students and make recommendations for translation of this knowledge into the school environment.
Publisher: Systematic Reviews KerkoCite.ItemAlsoKnownAs: 10.1186/s13643-019-1016-6 2405685:X7EVBRYF
Keywords: Acculturation; Mental health; Refugee; Resettlement; School; Systematic review

The Politics of Learning Reforms in Bangladesh Naomi , Mirza M. Hassan, Muhammad Ashikur Rahman, Khondoker Shakhawat Ali, and Md. Sajidul Islam Introduction - Hossain, N; Hassan, M; Rahman, M; Ali, K; Islam, Md (The politics of education in developing countries: from schooling to learning, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:4KSRXN8F 2405685:APF6QN7D
Keywords: Developing countries; Education; Education and state; Political aspects

What Do We Mean by Blended Learning? - Hrastinski, Stefan (TechTrends, 2019)
The term blended learning is used frequently, but there is ambiguity about what is meant. What do we mean by blended learning? What, how and why are we blending? In this paper different definitions, models and conceptualizations of blended learning and their implications are discussed. Inclusive definitions and models, and diverse conceptualizations, mean that essentially all types of education that include some aspect of face-to-face learning and online learning is described as blended learning in the literature. Blended learning has become an umbrella term. Blended learning is also used to describe other blends, such as combining different instructional methods, pedagogical approaches and technologies, although these blends are not aligned with influential blended learning definitions. Since blended learning has many meanings, it is important that researchers and practitioners carefully explain what blended learning means to them. It is also suggested that alternative, more descriptive terms, could be used as a complement or replacement to blended learning.
shortDOI: 10/ggkdqc KerkoCite.ItemAlsoKnownAs: 10.1007/s11528-019-00375-5 10/ggkdqc 2405685:QXWVB278

Reexamining the impact of self-determination theory on learning outcomes in the online learning environment - Hsu, Hui-Ching Kayla; Wang, Cong Vivi; Levesque-Bristol, Chantal (Education and information technologies, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-019-09863-w 2339240:2XB7RW54 2405685:YKVJG2Z5

Effects of gesture-based match-to-sample instruction via virtual reality technology for Chinese students with autism spectrum disorders - Hu, Xiaoyi; Han, Zhuo Rachel (International Journal of Developmental Disabilities, 2019)
Effective strategies to address academic performance are critical to students with disabilities in inclusive settings. The purpose of this study was to investigate the effectiveness of using gesture-based instruction via Leap Motion-aided virtual reality (VR) technology to teach matching skills to school-aged students with autism spectrum disorder (ASD) in China. Three participants with ASD from general education schools participated in this study. A multiple probe design across participants was used. The results indicated that all participants acquired the target match-to-sample skills and maintained the acquired skills at a high level for up to 12 weeks. Results of this study provide important implications to special education and general education teachers working with students with ASD.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/20473869.2019.1602350 KerkoCite.ItemAlsoKnownAs: 10.1080/20473869.2019.1602350 2339240:XFCC6MFH 2405685:2Q77DSNT
Keywords: China; autism spectrum disorders; computer-assisted instruction; gesture-based; match-to-sample; virtual reality technology

Country Profile: Lebanon - Huawei (Global Connectivity Index, 2019)
Select and compare the status of your nation's digital transformation against up to 3 nations around the world
KerkoCite.ItemAlsoKnownAs: 2339240:RCNK4LTR 2405685:6F99JY9Y

Gender Inequality Index (GII): Human Development Reports - Human Development Report (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:5RBLVQAF 2405685:SADRRVDB

Formation de formateurs au numérique éducatif de 4 pays (Burkina, Comores, Mali et Tchad) - IFADEM (Initiative francophone pour la formation à distance des maîtres, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:2GY6RDDF

Pakistani Teacher-Educator Professional Learning through an International Blended Course - Impedovo, Maria Antonietta; Malik, Sufiana Khatoon (Open Praxis, 2019)
International teacher-educator learning supports a more complex vision of teacher professionalism for both developed and developing countries. The aim of this paper is the analysis of Pakistani teacher-educator professional learning after attending an international blended course, considering the impact of online and face-to-face participation and the main competencies involved in their professional learning. The blended learning course attended by the Pakistani Teacher-educators is part of an international project between Europe and Asia. The analysis is carried out using written traces in the online platform; 47 questionnaires at the end of the face-to-face training sessions in Pakistan and 10 deep-interviews with Pakistani educators; the written traces, open questions, and deep-interviews were qualitatively analyzed. Additionally, the educators' technological, pedagogical and instructional design and interpersonal and intercultural skills were also analysed. The paper considers how international learning could affect the professional learning of teacher-educators in Global South and the centrality of the design of innovative learning courses for today's environment of international globalization.
Publisher: International Council for Open and Distance Education KerkoCite.ItemAlsoKnownAs: 10.5944/openpraxis.11.2.928 2339240:YNGS2RBD 2405685:DLCJJKLI
Keywords: Blended Learning; Cultural Awareness; Faculty Development; Foreign Countries; Instructional Design; International Education; Interpersonal Competence; Professionalism; Skill Development; Teacher Educator Education; Teacher Educators; Teaching Skills; Technological Literacy

Teacher career reforms: Learning from experience - International Institute for Educational Planning (International Institute for Educational Planning, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:5CH6SQ4J 2405685:UMUSCXUL

Measuring digital development: Facts and figures 2019 - International Telecommunication Union (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:9SG4ANLJ 2405685:AT4EB7GV

Building a globalised research system – the case of Bangladesh - Irfanullah, H (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:FYJUZ95H 2405685:CJIZGFZR

What can we learn from EMIS diagnostics? | Blog | Global Partnership for Education - Irving, Margaret; Percier, Marc-Antoine (2019)
Millions of dollars are invested in strengthening education management information systems, but many countries still struggle with data-related issues. How can countries make their systems more effective? An EMIS diagnostic is the first step.
KerkoCite.ItemAlsoKnownAs: 2339240:CJ2XAYYS 2339240:YV5QAT6M 2405685:2NUN9HSN 2405685:TQ6BQSYH 4656463:34BSI83K

Will Technology Transform Education for the Better? - J-PAL Evidence Review (Abdul Latif Jameel Poverty Action Lab, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:EP4SDEQI 2405685:9N96VS8X

Developing critical and theoretical approaches to educational technology research and practice - Jameson, Jill (British Journal of Educational Technology, 2019)
shortDOI: 10/gf62hg KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12775 10/gf62hg 2339240:2GDQTIZA 2339240:HWDKX456 2339240:RNTYTJ85 2405685:3X4HSMHB 2405685:UG65PX2M 2405685:UPPL58ZU

Decolonisation in Universities: The politics of knowledge - Jansen, Jonathan (Wits University Press, 2019)
Shortly after the giant bronze statue of Cecil John Rhodes came down at the University of Cape Town, student protestors called for the decolonisation of universities. It was a word hardly heard in South Africa’s struggle lexicon and many asked: What exactly is decolonisation? This book brings together some of the most innovative thinking on curriculum theory to address this important question. In the process, several critical questions are raised: Is decolonisation simply a slogan for addressing other pressing concerns on campuses and in society? What is the colonial legacy with respect to curricula and can it be undone? How is the project of curricula decolonisation similar to or different from the quest for post-colonial knowledge, indigenous knowledge or a critical theory of knowledge? What does decolonisation mean in a digital age where relationships between knowledge and power are shifting? Strong conceptual analyses are combined with case studies of attempts to ‘do decolonisation’ in settings as diverse as South Africa, Uganda, Tanzania and Mauritius. This comparative perspective enables reasonable judgments to be made about the prospects for institutional take-up within the curriculum of century-old universities. Decolonisation in Universities is essential reading for undergraduate teaching, postgraduate research and advanced scholarship in the field of curriculum studies.Shortly after the giant bronze statue of Cecil John Rhodes came down at the University of Cape Town, student protestors called for the decolonisation of universities. It was a word hardly heard in South Africa’s struggle lexicon and many asked: What exactly is decolonisation? This edited volume brings together the most innovative thinking on curriculum theory to address this important question. In the process, several critical questions are raised: Is decolonisation simply a slogan for addressing other pressing concerns on campuses and in society? What is the colonial legacy with respect to curriculum and can it be undone? How is the project of curriculum decolonisation similar to or different from the quest for postcolonial knowledge, indigenous knowledge or a critical theory of knowledge? What does decolonisation mean in a digital age where relationships between knowledge and power are shifting? The book combines strong conceptual analyses with novel case studies of attempts to ‘do decolonisation’ in settings as diverse as South Africa, Uganda, Tanzania and Mauritius. Such a comparative perspective enables reasonable judgements to be made about the prospects for institutional take-up within the curriculum of century-old universities.
KerkoCite.ItemAlsoKnownAs: 2405685:ZNXFPM2C

From Theory to Practice: Open Government Data, Accountability, and Service Delivery - Jelenic, Michael Christopher (2019)
KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-8873 2339240:LXXRK6IW 2405685:QEFZPG9K

A systematic literature review of the use of Semantic Web technologies in formal education - Jensen, Jesper (British Journal of Educational Technology, 2019)
This paper presents a systematic literature review of research focused on use of Semantic Web technologies in formal educational contexts. Through systematic search, the review has identified 199 research articles, which are examined with the intention of identifying prevalent themes within the body of research within the field of formal educational use of Semantic Web technologies. The themes identified by the review are: (1) Semantic Web ontologies; (2) Efficient distribution, accessibility, retrieval, reuse and combination of educational resources; (3) Linked Data; (4) Semantic Web enhanced virtual learning environments and personalization of learning environments; (5) Semantic Web learning objects; (6) Evaluation, feedback and assessment; (7) Semantic Web services; (8) Pedagogical tools for teachers and students. Furthermore, this review seeks to examine how these themes and the use of Semantic Web technologies in formal education reflects on the ongoing discussion of how pedagogy and technology should interact. The outset of this discussion is a previous study by Dirckinck-Holmfeld, which establishes that there is a tendency to emphasize technology over pedagogy in educational design and development.
shortDOI: 10/gf5f68 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12570 10/gf5f68 2339240:PJ8XJQ83 2405685:IC2U23KL
Keywords: Reviewed

SiLearn: an intelligent sign vocabulary learning tool - Jestin, Joy; Kannan, Balakrishnan; Sreeraj, M (Journal of Enabling Technologies, 2019)
Purpose Vocabulary learning is a difficult task for children without hearing ability. Absence of enough learning centers and effective learning tools aggravate the problem. Modern technology can be utilized fruitfully to find solutions to the learning difficulties experienced by the deaf. The purpose of this paper is to present SiLearn – a novel technology based tool for teaching/learning sign vocabulary.Design/methodology/approach The proposed mobile application can act as a visual dictionary for deaf people. SiLearn is equipped with features that can automatically detect both text and physical objects and convert them to their corresponding signs. For testing the effectiveness of the proposed mobile application quantitative analyses were done. Quantitative analysis is based on testing a class of 28 students belonging to St Clare Oral School for the Deaf, Kerala, India. This group consisted of 17 boys and 11 girls. Analysis was also done through questionnaire. Questionnaires were given to teachers, parents of deaf students learning sign language and other sign language learners.Findings Results indicate that as SiLearn is very effective in sign vocabulary development. It can enhance vocabulary learning rate considerably.Originality/value This is the first time that artificial intelligence (AI) based techniques are used for early stage sign language learning. SiLearn can equally be used by children, parents and teachers for learning sign language.
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/JET-03-2019-0014 2339240:3TIFN8RY 2339240:XBVND93J 2405685:KRCC2J5F 2405685:XGY53UE5
Keywords: Assistive technology; CALL; Deaf education; Learning technology; Mobile-assisted language learning; Sign language

The automation of management and business science - Johnson, C.D.; Bauer, BC; Niederman, F. (Academy of Management Perspectives, 2019)
KerkoCite.ItemAlsoKnownAs: 10.5465/amp.2017.0159 2405685:ITCCF5GH 2486141:RS9IM5JJ
Keywords: _Added-ailr-2024

Supporting Open Data Kit - Joseph, Dan (Missing Maps, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:6ATM7QAX 2486141:IECBUB9S

Technology and Teacher Professional Development (TPD): the Process and Content of Microlearning in a School-Based Integrated In-Service Teacher Education (INSET) Project - Junaid, Muhammad Ibn; Ogange, Betty; Allela, Melisa (Commonwealth of Learning (COL), 2019)
Continuing teacher professional development for all teachers across the entire school system poses a challenge in many contexts, especially in developing countries. Teachers from schools located in remote rural areas usually have fewer professional development opportunities due to the lack of accessibility either to their schools or to professional development resources. On-site school-based professional development is a viable option if innovative design is adapted to generate microlearning resources that teachers can easily access and share. This paper reports on a technology enabled school-based integrated INSET project coordinated by the Freetown Teachers College (FTC) in 12 junior secondary schools (JSS) in Sierra Leone under the COL’s Teacher Futures Programme. The project represents an innovation in TPD and is different from the general type of face-to-face and exclusively paper-based in-service teacher training programme common in Sierra Leone. Under the new project a multimodal approach is used where the FTC mentors and the communities of learners (JSS teachers) are presented with both print and microlearning resources and also provided access to an eLearning platform and the use of mobile phones as the main vehicles of delivery. Microlearning is an emergent learning strategy known for its quick response in bridging skills and knowledge gaps. In the context of the INSET Project, it involves a weekly dose of pedagogical content knowledge and skills, including modelling of classroom best practices which teachers can adapt and use. The project design and methods are briefly described, but the main focus of the paper is on the microlearning component of this project and discusses the use of mobile technology in the delivery and implementation of TPD in the 12 project schools. The emphasis is on the methodological and management challenges that arise in creating and nurturing communities of practice (CoPs) in a school-based setting and how these are addressed by the various schools involved.
KerkoCite.ItemAlsoKnownAs: 2405685:AALEIRC2

Kaduna State Education Sector Strategic Plan 2019–2029 - Kaduna State Ministry of Education, Science, and Technology (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:TCQAI8WV 2405685:GBMN8DMP

A Typology of Learning Profiles: Tools for Analysing the Dynamics of Learning - Kaffenberger, Michelle (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:B9IPCUC4 2339240:WMRDN7LF 2405685:NX2PDMMP

Developing TPACK in science and mathematics teacher education in Tanzania: A proof of concept study - Kafyulilo, Ayoub; Fisser, Petra (Collaborative Curriculum Design for Sustainable Innovation and Teacher Learning, 2019)
Since 1997, the government of Tanzania has made several attempts at introducing technology into education. However, despite these efforts technology has not become integrated into educational practice. A main reason is that teachers do not embrace the use of technology in their teaching. This study was initiated to design, implement and evaluate a professional development arrangement aimed at promoting teachers’ use of technology in their teaching practice. The study started with a ‘proof of concept’ study. Based on experiences in Ghana and Kuwait, a professional development arrangement was developed that incorporated ‘learning technology by design’ to prepare pre-service science and math teachers for using technology in their teaching. The experiences from this study informed the design of a professional development arrangement for practicing science teachers. The iterative design, implementation and evaluation of the professional development arrangements will be presented and discussed.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-20062-6_8 2339240:MQPLNUJN 2405685:Z8QTSILA

What is Agile Methodology: A primer on moving fast. How high-functioning teams build software - Kaiser, C. (AngelList, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:G9GN46C3 2405685:4GB5HGKS

Investigating ICTs for Education in Marginalized Communities - Kamal, Mehruz; Diksha, Diksha (2019)
The Agenda for Sustainable Development is a universal agenda to eliminate poverty through sustainable development by 2030. When it was adopted in 2015, the international community recognized that education was essential for the success of all seventeen of its goals. Ambitions for education are captured in Sustainable Development Goal 4, which aims to “ensure inclusive and equitable quality education and promote lifelong learning opportunities for all.” The United Nations has explicitly stated the importance of using ICTs in achieving educational opportunities. Since then, very few studies have tackled the issue. The findings so far, do not provide detailed guidance on the impact of ICTs in this domain. The purpose of this study is to contribute to this gap by integrating research in the fields of Information Systems, Development studies, and Psychology to understand the factors for facilitating educational objectives through ICTs within marginalized communities.
KerkoCite.ItemAlsoKnownAs: 2339240:AS7RGTC4 2405685:VHKEV9JL
Keywords: Google Scholar/ "education technology" refugees; RER theme_pedagogies and modalities; ⛔ No DOI found

‘When Will You Start Teaching the REAL Curriculum?’ - Karim, Azmina; Hussain, Faheem (Information and Communication Technologies for Development. Strengthening Southern-Driven Cooperation as a Catalyst for ICT4D, 2019)
This paper explores key problems faced by different humanitarian agencies in educating Rohingya refugees from Myanmar seeking asylum in Bangladesh. The first half this research provides an overview of the challenges faced by different refugee communities globally in the Education sector, followed by the relevant ICT interventions. Then, based on our interviews and focus group discussions with Rohingya refugees, we highlight the roadblocks faced by them while accessing education services in their camps. Absence of coherent curriculum, challenges with language, lack of qualified teachers, and non-acceptance of ICTs as primary education tools for children are identified as some of the key challenges faced by Rohingyas. Based on our research, we recommend that enabling policies and an inclusive hybrid knowledge network, emboldened by pre and in-service teacher training, inclusive religious education, standardized curriculum, and tangible employment opportunities can pave the path for a better and an educated future for the persecuted Rohingyas.
shortDOI: 10/ggtbq5 KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-18400-1_55 10/ggtbq5 2339240:6N8GWXWK 2405685:4FDS64G6
Keywords: Google Scholar/ "refugee education" ICT; RER theme_durable solutions

2019 State of Edtech Privacy Report - Kelly, G; Graham, J; Bronfman, J (2019)
Millions of educators use edtech apps and services in their classrooms daily, but findings suggest that many products don't do enough to protect kids' privacy. While the 2019 State of EdTech Privacy Report reveals incremental improvements in overall privacy practices since 2018, it also sheds light on key areas where the industry must improve, from targeted advertising to data sharing.
KerkoCite.ItemAlsoKnownAs: 2339240:325E5IJ9 2339240:ZEVH9ICL 2405685:EQXUN3BS 2405685:XT3RC4DY

Digital Economy Blueprint - Kenya Digital Economy (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:6CTY84PQ

Guidelines on Parental Empowerment and Engagement - Kenya Institute of Curriculum Development (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:URALQWKL 2405685:VVJU6RCE

2019 Kenya Population and Housing Census Volume IV: Distribution of Population by Socio-Economic Characteristics - Kenya National Bureau of Statistics (Kenya National Bureau of Statistics, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:NZQXRK6V 2405685:J4ZWA4L5

Kenya Population and Housing Census Results - Kenya National Bureau of Statistics (Kenya National Bureau of Statistics, 2019)
The total enumerated population was 47,564,296 Of which 23,548,056 were Males, 24,014,716 were Females and 1,524 were Intersex Females accounted for 50.5% of the total population The population has grown to 47.6 Million in 2019 from 37.7 Million in 2009 The intercensal growth rate has declined to 2.2% in 2019, from 2.9% in 2009 Average …
Library Catalog: www.knbs.or.ke Section: 2019 Census KerkoCite.ItemAlsoKnownAs: 2405685:5MHY2Y9G

C-DELTA: Preparing students as digital leaders in Bangladesh - Khan, S (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:395TDINJ 2405685:SUZI34L7
Keywords: ⛔ No DOI found

Evaluating the Readiness to Implement an E-Learning Technology to Support Education - Kimwise, Alone; Benjamin, Mudaheranwa; Mugabirwe, Beatrice (2019)
The study sought thought to establish the preparedness of refugees in settlements to embrace E-learning and Multimedia Technology as useful tool for supporting education and learning especially in mathematics, and basic health education when implemented. The study which covered Nakivale refugee settlement adopted the cross-sectional survey research design. A questionnaire was administered to learners of senior one, primary six and an interview guide to teachers. The findings showed that majority of the respondents said that they did not have access to ICTs, Majority of the respondents were Ugandan origin and overall the respondents had low experience in performing computer functions. The findings gave a big view of the limited practical implication concerning the readiness to E-learning and Multimedia Technology adoption to support education and learning in schools in Uganda.
KerkoCite.ItemAlsoKnownAs: 2339240:D4EIRAJZ 2405685:JVK2DS76
Keywords: RER theme_pedagogies and modalities; ⛔ No DOI found

Independent Learning with Technology – Impact of Global Learning XPRIZE - King, Simon (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:CBGZBPNS 2405685:WTUJTG7M
Keywords: ⛔ No DOI found

Using technology to facilitate educational attainment: Reviewing the past and looking to the future - Kishore, Diwakar; Shah, Dhwani (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:CFVSJSDI 2405685:A2RQMCL7
Keywords: Potential Usefulness: H; ⛔ No DOI found

Teaching game and simulation based probability - Koparan, Timur (International Journal of Assessment Tools in Education, 2019)
Technology and games are the areas where learners are most interested in today's world. If these two can be brought together within the framework of learning objectives, they can be an advantage for teachers and students. This study aims to investigate the learning environment supported by game and simulation. The games were used to evaluate the basic probability knowledge of the prospective teachers, to demonstrate the role of problem solving in the formation of the mathematical knowledge, and to enable discussing mathematical ideas in a worksheet. Simulations were used for visualization and a large number of experiments. The sampling of the study, by which case study research is adopted, is comprised of 40 prospective teachers at a state university in Turkey. The data were collected by introducing nine open-ended questions by means of games, worksheets and simulation activities. The questions asked relevant to the games include making predictions about the fairness of the games, playing the games in small numbers and in big numbers and the observation of the scores, calculation of the winning probabilities of the gamers both experimentally and theoretically, and their comparisons. The process of finding out the probability information underlying the games by the prospective teachers was analyzed qualitatively by means of worksheets, simulations and in-class observation, and the ways of thinking, intuitions, estimations, strategies, and opinions about the learning situation of the participants were tried to be determined. The results obtained put forward that the learning situation that was set up simultaneously contributed to the knowledge of probability and probability teaching of the prospective teachers; and that the candidates' opinions about the learning situation are positive.
Publisher: International Journal of Assessment Tools in Education, Pamukkale University, Faculty of Education, Kinikli Campus, Denizli 20070, Turkey Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2396851044?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.21449/ijate.566563 2339240:WFPXES63 2405685:IJR2IERE 2534378:6GQZL9UT 2534378:RAGWXRWA
Keywords: Computer Simulation; ERIC; Current Index to Journals in Education (CIJE); Educational Environment; Foreign Countries; Higher Education; Instructional Effectiveness; Knowledge Level; Mathematics Skills; Postsecondary Education; Prediction; Preservice Teacher Education; Preservice Teachers; Probability; Problem Solving; Student Attitudes; Turkey; __:import:01; __:match:final; __:matched; __:study_id:2098269; __finaldtb

The digital gender gap - Kuroda, Reiko; Lopez, Mariana; Sasaki, Janelle; Settecase, Michelle (GSMA, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:AZ4M7W6W 2405685:HJNK96RX

Should students use digital scratchpads? Impact of using a digital assistive tool on arithmetic problem-solving - Kwak, Minji; Gweon, Gahgene (Artificial Intelligence in Education, 2019)
An excessive cognitive load may reduce a student’s problem-solving performance by preventing effective learning. Using an assistive tool, such as a notepad, can reduce such extraneous cognitive while solving a problem, thereby improving a student’s performance. In this paper, we collected game log data from an educational game, called “Double digit”, which has a digital scratchpad as an assistive tool that can be used to reduce student’s cognitive load. We examine whether a correlation exists between the amount of “digital scratchpad usage” and a student’s “game performance”. Game log data, which consisted of 1,440,000 actions, was collected from 418 students in kindergarten to grade 2. Our data analysis using person-correlation shows a significant positive relationship between digital scratchpad usage and game performance for all three game difficulty levels. Interestingly, the correlation increases as the game difficulty level increases. This suggests that as game level difficulty increases, which requires a higher cognitive load of a student, students who used the digital scratchpad had higher game performance.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-23207-8_29 2339240:8N9UGXQP 2405685:GVNM84AF
Keywords: Arithmetic addition; Cognitive load; Digital assistive tool; Digital scratchpad; Game performance

Evaluation of technology use in education: Findings from a critical analysis of systematic literature reviews - Lai, Jennifer W. M.; Bower, Matt (Journal of Computer Assisted Learning, 2019)
Because the educational technology research literature is so broad, it is difficult for researchers to acquire an accurate sense of the issues and trends across the entire field. There has not been any recent effort to synthesize or critically analyse the systematic reviews in the area of educational technology. This study analysed 73 systematic literature reviews, including meta-analyses, focused on the evaluation of technology in educational contexts, in order to holistically understand the impact of learning technology use across different aspects of evaluation. Among these reviews, the most common theme examined was learning outcomes (89%), followed by affective elements (45%), behaviours (25%), technological elements (21%) and teaching/pedagogical aspects (19%). Most of the reviews found that the use of technology improved learning outcomes and affective perceptions. Approaches involving interaction, gamification, constructivism, student-centred learning and feedback were most effective. The analysis highlighted the need for more reviews focusing on multiple aspects of learning technology evaluation, on school level education and on the use of technology in naturalistic (non-interventional) settings. Critical reflections are also cast on the methods used to conduct systematic reviews in the educational technology field.
shortDOI: 10/ggfw5z KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12412 10/ggfw5z 2339240:JWK8KI8H 2339240:ZML7IW3X 2405685:7X5M3UH2 2405685:A32JUJ96
Keywords: evaluation; learning technology; meta-review; systematic review; tertiary review

The legacy of colonial language policies and their impact on student learning: Evidence from an Experimental Program in Cameroon - Laitin, David D.; Ramachandran, Rajesh; Walter, Stephen L. (Economic Development and Cultural Change, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1086/700617 2405685:5JH99UHL 4042040:FGB9E6BX

The politics of the education budget: Financing mass secondary education in Tanzania (2004–2012) - Languille, Sonia (International Journal of Educational Development, 2019)
This article examines the budget dimension of the rapid expansion of secondary education in Tanzania since 2004. It aims to illuminate important challenges associated with the current international call for universal secondary education and for domestic revenue mobilization to fill the significant financial gap to achieve SDG 4 by 2030. The article sheds light on critical political factors that shaped Tanzania’s education budget allocation, a topic scarcely scholarly investigated. In light of the analysis, the article concludes that tax justice, at global and national level, needs to guide any ambitious agenda for action to finance quality education for all.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2019.02.003 2339240:AMBHFVJQ 2405685:9BXZPI9L
Keywords: Budget; Financing; Political economy; Secondary education; Tanzania

Understanding the elephant: the discourse approach to boundary identification and corpus construction for theory review articles - Larsen, K.; Hovorka, D.; Dennis, A.R. (Journal of the Association for Information Systems, 2019)
KerkoCite.ItemAlsoKnownAs: 10.17705/1jais.00556 2405685:QNI8K9ZN 2486141:G3PRNUG5
Keywords: _Added-ailr-2024

Learning from What Works: RBF in Education - Lee, Jessica; Medina, Octavio (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:99ZH7LFR 2405685:RTB9AMYG 4656463:L2JHG9SK

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.edurev.2019.03.005 2339240:T6FJICU7 2405685:NECFNMUF
Keywords: Important; Read

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.edurev.2019.03.005 2405685:UXEQSP6H 2534378:R7UFM8RT
Keywords: Important; Read

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.edurev.2019.03.005 2339240:T6FJICU7 2405685:NECFNMUF
Keywords: Important; Read

Global Kids Online: Comparative report - Livingstone, Sonia; Kardefeld-Winther, Daniel; Saeed, Marium (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:D5J8ZAAR 2405685:JWM3JX3Z

Making government as a platform real - Loosemore, Tom (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:M95LD3KM 2405685:3L2FR4LM 4656463:W3T7J3V6

Matuto, Magbasa, Maglaro: Learning to read braille through play - Lopez MASc, Rhianne M.; Pinder PhD, Shane D.; Davies PhD, T. Claire (Assistive Technology, 2019)
In September 2016, Digital Learning for Development and All Children Reading released a “Grand Challenge for Development” urging researchers to explore the barriers that children with sensory disabilities in the Philippines face with respect to learning how to read. We sought to address one component of this challenge; engagement of persons with visual impairment in learning how to read in braille. The primary goal of this study was to engage in the co-design process to create a device to help young children with visual impairments learn to identify letters and short words in braille as a first step to reading. Participant questionnaires identified barriers of current reading devices including: accessibility, portability, durability, usability, and function. A design was prototyped based on results from a weighted evaluation matrix and feedback from partners who taught reading to persons with visual impairments. Usability testing showed that the device was easy to use and interactive. Suggestions for improvement included adding various learning modes and reducing the size, weight, and cost of the device. Results from this study highlight advantages of engaging in the co-design process and provide important data for other researchers developing devices for persons with visual impairments.
4 citations (Crossref) [2024-02-28] Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/10400435.2019.1619633 KerkoCite.ItemAlsoKnownAs: 10.1080/10400435.2019.1619633 2339240:PK956IE5 2405685:PZV9TXSU
Keywords: co-design; communication; education; electronic aids to daily living; universal design; usability; visual impairment; ⛔ No INSPIRE recid found

Matuto, Magbasa, Maglaro: Learning to read braille through play - Lopez, Rhianne M.; Pinder, Shane D.; Davies, T. Claire (Assistive Technology, 2019)
In September 2016, Digital Learning for Development and All Children Reading released a “Grand Challenge for Development” urging researchers to explore the barriers that children with sensory disabilities in the Philippines face with respect to learning how to read. We sought to address one component of this challenge; engagement of persons with visual impairment in learning how to read in braille. The primary goal of this study was to engage in the co-design process to create a device to help young children with visual impairments learn to identify letters and short words in braille as a first step to reading.
KerkoCite.ItemAlsoKnownAs: 10.1080/10400435.2019.1619633 2339240:KXPZKZ2F 2405685:Z3DSW4V3

Does Teacher Training Actually Work? Evidence from a Large-Scale Randomized Evaluation of a National Teacher Training Program - Loyalka, Prashant; Popova, Anna; Li, Guirong; Shi, Zhaolei (American Economic Journal: Applied Economics, 2019)
shortDOI: 10/ggx3rb KerkoCite.ItemAlsoKnownAs: 10.1257/app.20170226 10/ggx3rb 2405685:JMUTWKKB
Keywords: C:China

ICTs and development in developing countries: a systematic review of reviews - Lwoga, Edda Tandi; Sangeda, Raphael Zozimus (The Electronic Journal of Information Systems in Developing Countries, 2019)
This systematic review of reviews aimed to explore the contribution of information and communication technologies (ICTs) for development in developing countries. This systematic review of reviews determines and summarizes ICTD research trends, and methodologies and conceptual frameworks used in ICTD research discuss the findings and evidence and then suggest approaches for further research. We reviewed existing systematic reviews published on ICT and development between January 1990 and July 2017. The review of reviews shows that a growing number of ICTD research works have used qualitative research approaches for data collection and analysis. We note several attempts to develop and apply models/frameworks over explanatory and predictive theories, most notably in the area of social, sociotechnical, and technical. Nevertheless, there is limited evidence on the long‐term contribution of ICT use on livelihoods, patterns of economic inequality, human freedom, and well‐being in developing countries. This review of reviews synthesizes existing systematic reviews on the contribution of ICT for development than was previously available for developing countries. This review has the potential for several stakeholders, including the public and private sector, intermediaries, and nonprofit organizations, to utilize the accumulated evidence from selected systematic reviews to enable/improve the appropriate and sustainable use of ICTs for development.
KerkoCite.ItemAlsoKnownAs: 10.1002/isd2.12060 2405685:2HFH9EJX 2534378:8P8Y85JD

Harnessing the power of data to improve education systems - Lynch, Kelley (Global Partnership for Education, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RHIT7WRY 2405685:VAZ84RH2
Keywords: ⛔ No DOI found

WhatsApp utilisation at an initial teacher preparation programme at a university of technology in South Africa - Mabaso, Nkosinomusa; Meda, Lawrence (Proceedings of Teaching and Education Conferences, 2019)
All universities in South Africa are encouraged to use a Learning Management System such as Blackboard to facilitate blended learning. Despite, the availability of Blackboard at one university of technology in the country, some lecturers and students prefer utilising WhatsApp for teaching and learning. The purpose of this study is to investigate students and lecturers’ perspectives about learning and teaching using WhatsApp at a university in South Africa. The study was done using a qualitative case study within an intepretivist paradigm. It was guided by Garrison, Anderson and Archer’s Community of Inquiry as a theoretical framework. Sixteen students and two lecturers who heavily use WhatsApp were purposively selected to participate in semi-structured interviews and focus group discussions. The study found that lecturers use WhatsApp not only for communication purposes, but to foster collaborative learning among students. Although students noted some limitations which they experience when using WhatsApp, they preferred the social media to blackboard. The study concludes that although WhatsApp is response to students’ needs, it does not adequately prepare students to graduate with digital literacy skills expected by the Department of Education in the country.
Issue: 8410560 KerkoCite.ItemAlsoKnownAs: 10.20472/TEC.2019.007.009 2339240:GPXY25VR 2405685:9J2PHTPS 2534378:37UHHTGP 2534378:H6RM7XJ8
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425972; __finaldtb

WhatsApp utilisation at an initial teacher preparation programme at a university of technology in South Africa - Mabaso, Nkosinomusa; Meda, Lawrence (Proceedings of Teaching and Education Conferences, 2019)
All universities in South Africa are encouraged to use a Learning Management System such as Blackboard to facilitate blended learning. Despite, the availability of Blackboard at one university of technology in the country, some lecturers and students prefer utilising WhatsApp for teaching and learning. The purpose of this study is to investigate students and lecturers’ perspectives about learning and teaching using WhatsApp at a university in South Africa. The study was done using a qualitative case study within an intepretivist paradigm. It was guided by Garrison, Anderson and Archer’s Community of Inquiry as a theoretical framework. Sixteen students and two lecturers who heavily use WhatsApp were purposively selected to participate in semi-structured interviews and focus group discussions. The study found that lecturers use WhatsApp not only for communication purposes, but to foster collaborative learning among students. Although students noted some limitations which they experience when using WhatsApp, they preferred the social media to blackboard. The study concludes that although WhatsApp is response to students’ needs, it does not adequately prepare students to graduate with digital literacy skills expected by the Department of Education in the country.
Issue: 8410560 KerkoCite.ItemAlsoKnownAs: 10.20472/TEC.2019.007.009 2339240:GPXY25VR 2405685:9J2PHTPS 2534378:37UHHTGP 2534378:H6RM7XJ8
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425972; __finaldtb

Participatory visual methods and school-based responses to HIV in rural South Africa: insights from youth, preservice and inservice teachers - MacEntee, Katie (Sex Education: Sexuality, Society and Learning, 2019)
This paper explores students', preservice teachers' and inservice teachers' perceptions of the contributions and challenges of using participatory visual methodologies (PVM) to enhance HIV education in rural schools. Drawing on findings from three research projects conducted in KwaZulu Natal, South Africa, four positive contributions are identified: 1) novelty, fun and engagement; 2) amplifying youth voices; 3) the facilitation of teachers' reflexive learning; and 4) the production of local resources in under-resourced schools. Challenges include: 1) limited technology access; 2) teacher discomfort; and 3) resistance to PVM integration. Teachers and young people, especially in under resourced rural settings, can benefit from integrating such methodologies into their responses to HIV and AIDS. However, sustainable integration must rely on choosing the most appropriate participatory visual methodologies given the technological resources available in school. The paper concludes with recommendations to optimise participatory visual methodologies integration into rural school-based HIV responses.
Publisher: Routledge, Available from: Taylor & Francis, Ltd. 530 Walnut Street Suite 850, Philadelphia, PA 19106 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2396852077?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/14681811.2019.1661833 2339240:6T6MGSSZ 2405685:8C828K53 2405685:CB9W5QZV 2534378:2R8BXPSR 2534378:EMFZWYAL 2534378:TQ38MU35
Keywords: Acquired Immunodeficiency Syndrome (AIDS); Children And Youth - About; Disadvantaged Schools; ERIC; Current Index to Journals in Education (CIJE); Educational Resources; Foreign Countries; HIV; Health Education; Higher Education; Media Selection; Photography; Postsecondary Education; Preservice Teachers; Rural Schools; Secondary Education; Secondary School Students; Sex Education; South Africa; Story Telling; Student Attitudes; Teacher Attitudes; Teaching Methods; Visual Aids; __:import:01; __:match:final; __:matched; __:study_id:2096729; __finaldtb; participatory visual methodology; rural education; sexual health education

"Everyone Brings Their Grain of Salt": Designing for Low-Literate Parental Engagement with a Mobile Literacy Technology in Côte d'Ivoire - Madaio, Michael A.; Tanoh, Fabrice; Seri, Axel Blahoua; Jasinska, Kaja; Ogan, Amy (Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems - CHI '19, 2019)
Significant research has demonstrated the crucial role that parents play in supporting the development of children’s literacy, but in contexts where adults may lack sufficient literacy in the target language, it is not clear how to most effectively scaffold parental support for children’s literacy. Prior work has designed technologies to teach children literacy directly, but this work has not focused on designing for low-literate parents, particularly for multilingual and developing contexts. In this paper, we describe findings from a qualitative study conducted in several regions of rural Côte d’Ivoire to understand Ivorian parents’ beliefs, desires, and preferences for French literacy. We discuss themes that emerged from these interviews, surrounding ideas of trust, collaboration, and culturally-responsive design, and we highlight implications for the design of technology to scaffold low-literate parental support for children’s literacy.
KerkoCite.ItemAlsoKnownAs: 10.1145/3290605.3300695 2339240:28K7BQND 2405685:VMXK42BU

Systems Research in Education: Designs and methods - Magrath, Bronwen; Aslam, Monazza; Johnson, David (Research in Comparative and International Education, 2019)
Publisher: SAGE Publications Sage UK: London, England KerkoCite.ItemAlsoKnownAs: 2339240:QPRI36LV 2405685:FSIPMHL2
Keywords: ___working_potential_duplicate; ❓ Multiple DOI

Implementing augmented reality (AR) on phonics-based literacy among children with autism - Mahayuddin, Zainal Rasyid; Mamat, Najmiah (International Journal on Advanced Science, Engineering and Information Technology, 2019)
11 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.18517/ijaseit.9.6.6833 2339240:XHU3472Q 2405685:C8JVKXJ9
Keywords: ⛔ No INSPIRE recid found

Ministry of Education, Science and Technology – Policy Reforms - Malawi Ministry of Education, Science and Technology (2019)
The Malawi Public Sector Reforms Management Unit exists to catalyse, drive and facilitate public sector reforms in Malawi. The reforms are implemented in Government ministries, departments and agencies (MDAs), local councils, parastatal organizations and constitutional bodies.
KerkoCite.ItemAlsoKnownAs: 2339240:CVBB75DU 2405685:Z4Z43LCT

Malawi Education Sector Analysis - Malawi Ministry of Education, Science, and Technology, Malawi (Government of Malawi, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:D5NERCHI 2405685:UKTVQWTU

Beyond disciplinary boundaries: Mapping educational science in the discourse on social media - Manca, S; Rehm, M; Brandon, D; Greenhow, Christine (Teachers College Record, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:QS2MXPFP

Subnational investment in human capital - Manuel, Marcus; Coppard, Dan; Dodd, Amy; Desai, Harsh; Watts, Richard; Christensen, Zach; Manea, Stephanie (Overseas Development Institute/ Development Initiatives, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QK4XUIPM 2405685:UICHGHVQ

CIRCL Primer: Design-Based Implementation Research. In CIRCL Primer Series. - Martin, W; Fishman, Barry; Cheng, Britte; Penuel, William (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:SC5Q93KQ 2405685:A962I7LW

Analysis of motor performance in individuals with cerebral palsy using a non-immersive virtual reality task – a pilot study - Martins, Fabiana Paula Almeida; Massetti, Thaís; Crocetta, Tania Brusque; Lopes, Priscila Bianchi; da Silva, Amanda Abreu; Figueiredo, Eliketylen Fernandes; de Abreu, Luiz Carlos; da Silva, Talita Dias; Monteiro, Carlos Bandeira de Mello (Neuropsychiatric Disease and Treatment, 2019)
Purpose To evaluate the performance improvement of individuals with hemiparesis cerebral palsy (CP) using a virtual task. Participants and methods Twenty individuals were selected and distributed into two groups. The experimental group (CP group) comprised ten individuals with a medical diagnosis of CP, and ten individuals with typical development (sex- and age-matched) composed the control group (TD group). Both groups followed the same intervention protocol, which included a virtual coincident timing task: the participants performed upper limb movements in front of a computer’s webcam and interacted with the task with the aim of virtually intercepting spheres that fell in four rows following the rhythm of a pre-selected song during an 8-minute period. To verify the influence on a real task, pre- and posttests were performed in a similar task, but with physical contact (using the spacebar on the keyboard of a computer). To analyze the data, we evaluated the variable, constant, and absolute errors during the task and in the pre- and posttests. Results The results showed that there was an improvement in performance between the pre- and posttests; that is, after practicing the task in an environment without physical contact, there was a performance improvement in posttests in the real task, but only for the CP group. Moreover, there were significant differences in precision and accuracy between the two groups, with worse performance in the CP group. Conclusion Individuals with CP presented better performance in the real task after practice in a virtual reality task, albeit with worse performance compared with individuals with TD. This is an interesting result that supports the possible use of virtual tasks for the rehabilitation of individuals with CP.
KerkoCite.ItemAlsoKnownAs: 10.2147/NDT.S184510 2339240:CI3HQJFI 2405685:P8DEJMKH

Maryville begins issuing student-owned digital diplomas - Maryville University (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:DGIEZVR3 2405685:SMRTPUUI

Raising kids with Down syndrome: Experiences of selected parents in the Philippines - Masanda, Carmi Miko P.; Masanda, Argel B. (International Journal of Science and Research, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:FZ6GIWIM 2405685:TQUTINYE
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Devising New Models for School Improvement in Developing Nations: Sierra Leone, a case study - Mason, Miriam Theresa (Durham University, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:55RYBL9Q

The Centre for Innovative Teaching and Learning Approach - Mastercard Foundation (2019)
Library Catalog: mastercardfdn.org KerkoCite.ItemAlsoKnownAs: 2405685:VLG3BPAQ

Education authority to launch free online school library - Mbwiga, Gladys (The Citizen, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:XEQDPAF9 2405685:HHEWYAFT

Investing more in education to boost the economy, graduate from least developed country and mitigate covid-19 impact - McCarthy, Rachel (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:TQN6SL5I 2405685:C4HL3EAT
Keywords: ⛔ No INSPIRE recid found

Scaling Impact; Innovation for the Public Good - McLean, Robert; Gargani, John (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:9TNQFMSL 2405685:PP5MDTME
Keywords: ⛔ No DOI found

Comprehensive Indicators of Preschool Education - MECSS (Ministry of Education, Culture, Sciences and Sports, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:EGE8WEFY 2405685:7FI7LACE

Private engagement in refugee education and the promise of digital humanitarianism - Menashy, Francine; Zakharia, Zeena (Oxford Review of Education, 2019)
This paper examines the prevalence of technological interventions in education in emergencies through a case study of private participation in Syrian refugee education in Jordan, Lebanon, and Turkey. This research is conceptually situated within critiques of ‘digital humanitarianism’, simultaneously interrogating the role of technology in humanitarian responses and the roles of private actors who promote this technology. Our study demonstrates that a pervasive optimism concerning education technology in emergencies accompanies a surge in private actor engagement in Syrian refugee education. Findings indicate that while access to technology in educational settings is important to the Syrian refugee populations, private actors’ disproportionate focus on technology is problematic, particularly when technological interventions are viewed as panaceas for refugee education; designed free from coordination; driven by profit motivations; and developed in a manner decontextualised from the learning context. This study attends to the necessity of countering the overwhelming optimism about technology as a panacea for refugee education, which fails to problematise the implications of interventions developed in the Global North for a distant ‘other’ in the Global South.
shortDOI: 10/ggs9ws KerkoCite.ItemAlsoKnownAs: 10.1080/03054985.2019.1682536 10/ggs9ws 2339240:UH2A3AGB 2405685:S8KCLCMR
Keywords: GENERAL - to be categorised; Google Scholar/ "education technology" refugees

Digital Learning Innovations for Syrian Refugees and Host Communities in Lebanon - Metni, Eliane (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:D4326RKF 2405685:4GR2F2BC

Awareness and use of a mobile phone as a potential pedagogical tool among secondary school teachers in Tanzania - Mfaume, Hamisi (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2019)
The government of Tanzania through its ICT Policy for Basic Education, has indicated a commitment to use of mobile phones among other ICTs, as a strategy to enhance the quality of education. It is from this fact that this study determined teachers’ awareness of the educational benefits of the device, their use and barriers towards their educational use. The study was qualitative in nature, using a sample of twenty one (21) teachers who were purposefully selected from three secondary schools. Data were sought through semi-structured interviews and were thematically analysed. The findings revealed that teachers are well informed of the benefits, but they hardly utilize it for educational purposes. Lack of knowledge and skills, a negative attitude, lack of awareness of the ICT policy, age and low motivation emerged as key barriers. In light of the findings, the study concluded that the government’s commitment to integrate the device in the promotion of quality education has not yet moved beyond policy statements. Thus, a concerted effort is needed to train teachers on pedagogical utilization of the device.
KerkoCite.ItemAlsoKnownAs: 2339240:NILQKHAU 2405685:RZS5MRR5 2405685:T44EMRPB 2534378:CWRHE7XH 2534378:HJAYR2JU Place: Bridgetown Publisher: University of the West Indies Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2255700979?accountid=9851
Keywords: Bali; Bangkok Thailand; Cellular telephones; Education; Educational technology; Japan; Learning; Pedagogy; Secondary school teachers; Students; Tanzania; Teaching; United Kingdom–UK; United States–US; __:import:01; __:match:final; __:matched; __:study_id:2096774; __finaldtb; ⛔ No DOI found

Harnessing the power of a mobile phone in the promotion of teacher ethics in Tanzania - Mfaume, Hamisi; Mgaya, Rose; Bilinga, Margareth (International Journal of Education and Development using ICT, 2019)
This study examined teachers’ perspectives on using a mobile phone in the promotion of teacher ethics in Tanzania. It was informed by the qualitative approach, using a sample of forty-eight (48) respondents who were drawn through purposive and convenient sampling techniques. Data were sought through Focus Group Discussions (FGDs) and were subjected to thematic data analysis. Findings indicated that a handful of respondents perceived a mobile phone as a viable tool in the promotion of teacher ethics. Moreover, ownership and accessibility, popularity and ease of use, internet coverage and connectivity, as well as the ubiquitous nature of the device were the reasons given for their perceptions. However, teachers’ lack of knowledge, attitude and beliefs, financial problems, limited network connection, and poor coordination and technical support were the anticipated challenges in using the device in the promotion of teacher ethics. Based on the noted potential of the device, the study recommends the need for Teachers’ Service Commission in Tanzania to adopt and use the device so as to ensure wider coverage of ethical information and combat unethical conduct amongst teachers.
KerkoCite.ItemAlsoKnownAs: 2339240:3XUZLE5P 2405685:ABAEIQD7
Keywords: ⛔ No DOI found

User perceptions of technology integration in schools: Evidence from Turkey’s FATIH project - Milla, Asli Cazorla; Kurt, Ozge; Mataruna-Dos-Santos, Leonardo Jose (International Journal of Education and Practice, 2019)
Publisher: Conscientia Beam KerkoCite.ItemAlsoKnownAs: 10.18488/journal.61.2019.74.430.437 2339240:FJMPPWSV 2405685:8TXBN4D9

Plan D’actions Quinquennal De Mise En Oeuvre De La Politique Nationale Genre - Ministère de la Femme, de la Protection de; l’Enfance et de la Solidarité Nationale (Republic of Chad, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:6A4TNHS7 2405685:8CAPTL9N

Plano Estratégico para a sociedade da informação - Ministério da Ciência, Tecnologia e Ensino Superior (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:UWCU8TZZ 2405685:9ACBCIQL

Annual School Census Report - Ministry of Basic and Secondary Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:3BAQ3WPG 2405685:FYWGE5WI

2019 Annual School Census Report - Ministry of Basic and Senior Secondary Education (Ministry of Basic and Senior Secondary Education, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:99GBVUWP 2339240:NBI2YGW4 2405685:PF3NKF32 2405685:QNZEXSV3 2405685:SK6ZDI63 2486141:IVGKRIEH

2019 Annual Schools Census Report - Ministry of Basic and Senior Secondary Education; Education, Ministry of Basic and Senior Secondary (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:J7MURQFH 2486141:7DDR6BUJ

Approved Basic Education Statistical Booklet 2019 - Ministry of Education (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:JFBPSH7S 2405685:GBA7WEDP

iSherig-2 Education ICT Master Plan 2019-2023 - Ministry of Education (Royal Government of Bhutan, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:Y547BCXC 2405685:KA7K5USC

Education Strategic Plan 2018–2030 - Ministry of Education, Ghana (Ministry of Education, Ghana, 2019)
Building on Ghana's achievements in expanding education, this plan puts Ghana on the road towards meeting the Sustainable Development Goals and represents a deliberate reorientation towards this aim, as it replaces the previous ESP 2010-2020.
KerkoCite.ItemAlsoKnownAs: 2339240:JHUHU9HY 2405685:R5XBKSUI

Ministry of Education Ghana - Education Strategic Plan 2018-2030 - Ministry of Education, Ghana (Ministry of Education, Ghana, 2019)
Building on Ghana's achievements in expanding education, the Education Strategic Plan sets out the vision and policies for realizing the ambition of transforming Ghana into a ‘learning nation'. It puts Ghana on the road towards meeting the Sustainable Development Goals and represents a deliberate reorientation towards this aim, as it replaces the previous ESP for 2010-2020. This plan not only sets the long-term vision but also how this will be operationalized in the medium term through the accompanying Education Sector Medium Term Development Plan 2018-2021.
KerkoCite.ItemAlsoKnownAs: 2339240:2MX8W5EJ 2339240:SDTNWRB7 2405685:G3VWFY4N 2405685:U4CHV5DB

Reform Secretariat at the Ministry of Education - Ministry of Education, Ghana, Reform Secretariat (2019)
A Reform Secretariat has been formed at the Ministry of Education to ensure that all the agencies and bodies directly...
Library Catalog: moprempeh.com Section: Education Reform EdTechHub.ItemAlsoKnownAs: 2405685:XDFEBGMW

Tawjihi Pass Rates - Ministry of Education, Jordan (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:HFZTZW9C

س للعام الدرا ي التقرير االحصائ - Ministry of Education, Jordan (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:UKI54W2G

Basic education statistical booklet - Ministry of Education, Republic of Kenya (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:894SNAXV 2405685:49X4ADMZ

Education Sector Analysis - Ministry of Education, Science, and Technology (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F2455KDU 2405685:WFQZZHPI

Education Sector Analysis - Ministry of Education, Science, and Technology (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F2455KDU 2405685:WFQZZHPI

Education Sector Analysis - Ministry of Education, Science, and Technology (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F2455KDU 2405685:WFQZZHPI

Education Sector Analysis - Ministry of Education, Science, and Technology (Government of the Republic of Malawi, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F2455KDU 2405685:WFQZZHPI

Multilingual Education Action Plan - Ministry of Education, Youth and Sports, Kingdom of Cambodia (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BPGALINX 2405685:TZ3BZAKV

Cambodia Education Roadmap 2030 (Sustainable Development Goal [SDG] 4) - Ministry of Education, Youth and Sports, Royal Government of Cambodia (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:YIQ74G47 2405685:F62E47TR

MFDP Provides Clarity on Teachers’ Salaries Payment - Ministry of Finance and Development Planning (Liberia) (2019)
Monrovia, Liberia - The Ministry of Finance and Development Planning clarifies that the government has already paid the salaries of fifteen thousand (15,000) non-MCSS teachers for the month of August, and is now processing their September pay.
Library Catalog: www.mfdp.gov.lr KerkoCite.ItemAlsoKnownAs: 2405685:REVH3VSX

National Information, Communications and Technology (ICT) Policy - Ministry of Information, Communications and Technology, Kenya (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:3MTGT25S

Sierra Leone Medium Term National Development Plan (Volume 1) - Ministry of Planning and Economic Development (Sierra Leone) (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:CZE9NFVC

National ICT Policy & Strategy 2019-2024 - Ministry of Post, Telecommunications & Technology (Federal Republic of Somalia, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:H9AW7T68 2405685:PDWDNW6T

Liberia Information and Communications Technology (ICT) Policy 2019-2024 - Ministry of Posts and Telecommunications (Government of Liberia, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:W7W8NRTC 2405685:ZVX6PFYN

ICT Policy for Primary and Secondary Education (2019 - 2023). - Ministry of Primary and Secondary Education (Zimbabwe) (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:ZK7M3DZ9

Implementing Low Cost Digital Libraries for Rural Communities by Re-functioning Obsolescent Television Sets: The Offline-pedia Project - Minniti, Sergio; Salazar, Joshua; Vega, Jorge (VIEW Journal of European Television History and Culture, 2019)
Publisher: the Netherlands Institute for Sound and Vision shortDOI: 10/ghgn5c KerkoCite.ItemAlsoKnownAs: 10/ghgn5c 2405685:M979LTFN

Considering Contextual Knowledge: The TPACK Diagram Gets an Upgrade - Mishra, Punya (2019)
zotzenLib.CopiedFrom: 2339240:TC4KJBR7 KerkoCite.ItemAlsoKnownAs: 10.1080/21532974.2019.1588611 2339240:TC4KJBR7 2405685:U6MW264I

Master plan for ICT in education in Bangladesh (2012-2021): Progress Review Report 2019 - MoE (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:JAJI53M3 2405685:QPP65VTW

Annual Primary School Census 2019 - MoPME (Directorate of Primary Education, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:9X2J5EH3 2405685:TJ73RPSY

Mining students’ data to analyse usage patterns in eLearning systems of secondary schools in Tanzania - Mtebe, Joel S; Kondoro, Aron W (Journal of Learning for Development, 2019)
The adoption and use of various eLearning systems to enhance the quality of education in secondary schools in Tanzania is becoming common. However, there is little evidence to suggest that students actually use them. Existing studies tend to focus on investigating students’ attitude towards using these systems through surveys. Nonetheless, data from surveys is normally subject to the possibility of distortion, low reliability, and rarely indicate the causal effects. This study adopted WEKA and KEEL as data mining tools to analyze students’ usage patterns and trends using 68,827 individual records from the log file of the Halostudy system implemented in secondary schools in Tanzania. The study found that the system usage is moderate and in decline. There is also variability in the usage of multimedia elements with biology having the highest number while mathematics has the lowest. Students from Dar es Salaam, Mwanza, and Arusha, in that order, had the highest system usage with the lowest being from the peripheral regions. The possible challenges limiting system usage are discussed. These findings show that data mining tools can be used to indicate usage patterns of systems implemented in sub-Saharan Africa and to help educators to find ways of maximising systems usage.
KerkoCite.ItemAlsoKnownAs: 2339240:AL8CL6D8 2405685:ECCVF4SL
Keywords: ⛔ No DOI found

Determinants of Implementation of Public Sector Projects in Kenya: A Case of Laptop Project in Public Primary Schools in Kangundo Sub-County, Machakos County - Muinde, Samuel Mutisya; Mbataru, Patrick (2019)
In One-to-one laptop programs are becoming popular across the globe. However available evidence suggests that their implementations in schools are often faced with challenges. For example, even though the government of Kenya began supplying laptops to public primary schools in 2016; reports indicate that the gadgets have not fully been put into use in many schools. Most of the empirical studies done in this area have majorly focused on the level of success and factors influencing implementation of the project and not the extent to which specific variables determine implementation of the project, thus resulting to a research gap. In order to fill this gap, study focused on the determinants of implementation of the laptop project in public primary schools in Kangundo Sub-county. The study was guided by 4 research objectives: i.) To assess the extent to which teachers’ perception determine implementation of the laptop project; ii) To establish the extent to which teachers’ capacity in ICT determine implementation of the laptop project; iii) To establish the extent to which availability of facilities determine the implementation of the laptop project; and iv) To establish the extent to which availability of digital subject content determine implementation of the laptop project. The study was premised on three (3) theories; Technology Acceptance Model, Constructivist Learning Theory and Resource Based Theory. The study adopted descriptive survey design. It targeted all the public primary schools, all teachers in lower primary and all the Ministry of Education officials heading the four zones that constitute Kangundo Sub-county. The study targeted all the 74 public primary schools which have 222 lower primary teachers, 74 head teachers and 4 MOEST officials making a total target population of 300. It adopted stratified random sampling in stratifying the schools into four zones and randomly selected 22 schools. All 22 school heads and all 66 lower primary school teachers of the participating schools were purposively sampled. Additionally, the 4 MOEST officials heading the four zones were included, making a sample of 92 participants. Tools of data collection included questionnaires for teachers and school heads, an interview guide for MOEST officials and an observation checklist. The data analysis was conducted using SPSS. Content analysis was adopted in analyzing qualitative data whereas descriptive statistics such as frequencies and percentages were used in analyzing quantitative data. Tables and figures were used to present the study results. The inferential analysis conducted shows that there was a significant relationship between independent and dependent variables. Both teachers’ capacity on ICT and availability of facilities were found to have significant effect on implementation of the laptop project while teachers’ perception and availability of digital subject content were found to have insignificant effect on the project in public primary schools in Kangundo Sub-County.
Accepted: 2020-06-30T09:17:59Z Publisher: International Academic Journal of Law and Society KerkoCite.ItemAlsoKnownAs: 2339240:2GJGUH3T 2405685:BVJFPMCV
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Developing BacaBicara: An Indonesian Lipreading System as an Independent Communication Learning for the Deaf and Hard-of-Hearing - Muljono, Muljono; Saraswati, Galuh Wilujeng; Winarsih, Nurul Anisa Sri; Rokhman, Nur; Supriyanto, Catur; Pujiono, Pujiono (International Journal of Emerging Technologies in Learning (iJET), 2019)
Deaf and hard-of-hearing people have limitations in communication, espe-cially on aspects of language, intelligence, and social adjustment. To com-municate, deaf people use sign language or lipreading. For normal people, it is very difficult to use sign language. They have to memorize many hand signs. Therefore, lipreading is a necessary for communication between nor-mal and deaf people. In Indonesia, there is still few education media for deaf people to learn lipreading. To overcome this challenge, we develop a lipread-ing educational media to help deaf and hard-of-hearing to learn Bahasa In-donesia, called BacaBicara. User-Centered Design (UCD) is implemented to design the application and to analyze the constraints and conceptual models for the needs of users. This conceptual model uses the picture, lipreading video, text, and sign language to help the users understand the contents. The High fidelity prototype was implemented for evaluating usability testing. Based on the evaluation of the application, the results show that the proto-type matches the usability goals and the user experience.
KerkoCite.ItemAlsoKnownAs: 10.3991/ijet.v14i04.9578 2339240:9IPNSKPY 2405685:QD5FWZIS
Keywords: Deaf and hard of hearing; Interaction; lipreading; user-centered design prototype

Sudan: 'Can't Wait to Learn!' - Mustafa, Iman; Amin, Ahmed (2019)
How innovative learning is empowering children in Sudan
KerkoCite.ItemAlsoKnownAs: 2339240:NHFP5HRG 2405685:NDRMWC9P

Cloud computing architecture for eLearning in secondary schools - Mwakisole, Kennedy; Kissaka, Mussa; Mtebe, Joel (The African Journal of Information Systems, 2019)
In recent years, schools have been investing heavily on information and communications technology (ICT) infrastructure to implement eLearning systems to enhance the quality of education in secondary schools in Tanzania. The majority of these systems are implemented using a traditional web-based eLearning approach on school premises which is costly and limits usage due to lack of scalability and flexibility. Consequently, many schools have started adopting cloud computing as a solution. However, this adaption depends on well-defined cloud eLearning architecture. This study proposed cloud architecture for implementing an eLearning system in secondary schools in Tanzania by adopting various layers proposed in previous studies. The effectiveness of this proposal was evaluated by comparing its performance with a similar traditional web-based eLearning system using the Moodle benchmark tool and Apache Jmeter. The study found that eLearning systems implemented in the cloud-based infrastructure had better performance metrics than web-based eLearning systems on school premises.
KerkoCite.ItemAlsoKnownAs: 2339240:H37DIS7E 2405685:QILWRT8Y
Keywords: ⛔ No DOI found

Home language, school language and children's literacy attainments: A systematic review of evidence from low- and middle-income countries - Nag, Sonali; Vagh, Shaher Banu; Dulay, Katrina May; Snowling, Margaret J. (Review of Education, 2019)
The general consensus in the field is that when the home language is different from the language of instruction in school then children's literacy attainments could slow down. In this 26-year review of the literature on children's literacy attainments in low- to middle-income countries, 40 correlational, ethnographic and intervention studies provide the data. We test the ‘home language advantage’ hypothesis where we expect children who speak the same language at home and school to show better literacy learning. We also examine other attributes in the home language and literacy environment (HLLE). Among the multivariate studies, trends differ across countries, age and grade levels, and child measures. Rather than a universal home language advantage, the evidence shows that home language advantage is context-sensitive. The correlational and ethnographic evidence point to a multiple risk factors model of home and school language disconnection; and the ethnographic and intervention studies provide complementary evidence of both feelings of unease, disempowerment and wish to help among family members, and increased confidence following guided support. Possible underlying mechanisms are examined through parallel synthesis of evidence from multiple research methods on three HLLE dimensions—books-at-home, home tutoring and adult literacy practices. The data partially corroborate findings from high-income countries (e.g. home environments impact literacy development, responsive parenting is present across families) but also bring focus on context-specific realities. Neither low-income nor low-print environments are uniform constraints because communities differ and some homes use available resources more efficiently than others.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/rev3.3130 KerkoCite.ItemAlsoKnownAs: 10.1002/rev3.3130 2405685:RIZG682H 4042040:QLFNIHUN
Keywords: home language advantage; home language and literacy environment; low-income countries

Research weaving: visualizing the future of research synthesis - Nakagawa, Shinichi; Samarasinghe, Gihan; Haddaway, Neal R.; Westgate, Martin J.; O’Dea, Rose E.; Noble, Daniel WA; Lagisz, Malgorzata (Trends in ecology & evolution, 2019)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.tree.2018.11.007 2405685:Y29WIV7Q 2486141:7IWVPGZQ 2486141:SFJ37LP4
Keywords: _Added-ailr-2024

Third submarine cable to boost Internet service - Nakhoul, Shikrallah (BusinessNews.com.lb, 2019)
The aim is to turn Lebanon into a regional hub for Internet distribution
KerkoCite.ItemAlsoKnownAs: 2339240:BZYK8W8T 2405685:IH9QDU8V

Digital literacy for children: exploring definitions and frameworks - Nascimbeni, Fabio; Vosloo, Steven (UNICEF Office of Global Insight and Policy, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:TG6T4TJF

Pakistan Demographic and Health Survey 2017-18 - National Institute of Population Studies (USAID, UKAID and UNFPA, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:ESFL9NXP 2405685:GLMJ5FAM 2405685:UQVGKUEN
Keywords: ⛔ No DOI found

Pakistan Demographic and Health Survey, 2017–18 - National Institute of Population Studies (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:436K5QBU
Keywords: auto_merged

2018 Population and Housing Census - National Statistics Office (Government of Malawi, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:UXWI3QF6 2405685:4KBEPZKW

Strengthening the Education Workforce - Naylor, Ruth; Jones, Charlotte; Boateng, Pearl (Education Commission, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:66PFUJWJ 2405685:YCU7P54S

Approximating the equilibrium effects of informed school choice - Neilson, Christopher A (Working Paper #628, Princeton University Industrial Relations Section, 2019)
This paper studies the potential small and large scale effects of a policy designed to produce more informed consumers in the market for primary education. We develop and test a personalized information provision intervention that targets families of public Pre-K students entering elementary schools in Chile. Using a randomized control trial, we ﬁnd that the intervention shifts parents’ choices toward schools with higher average test scores, higher value added, higher prices, and schools that tend to be further from their homes. Tracking students with administrative data, we ﬁnd that student academic achievement on test scores was approximately 0.2 standard deviations higher among treated families ﬁve years after the intervention. To quantitatively gauge how average treatment effects might vary in a scaled up version of this policy, we embed the randomized control trial within a structural model of school choice and competition where price and quality are chosen endogenously and schools face capacity constraints. We use the estimated model of demand and supply to simulate policy effects under different assumptions about equilibrium constraints. In counterfactual simulations, we ﬁnd that capacity constraints play an important role mitigating the policy effect but in several scenarios, the supply-side response increases quality, which contributes to an overall positive average treatment effect. Finally, we show how the estimated model can inform the design of a large scale experiment such that reduced form estimates can capture equilibrium effects and spillovers.
KerkoCite.ItemAlsoKnownAs: 2339240:2L3D59KP 2405685:SFXIW92Z
Keywords: ⛔ No DOI found

Online teacher professional development in ICT integration in Tanzania: An experience report - Ngeze, Lucian Vumilia; Iyer, Sridhar (Proceedings of the 27th International Conference on Computers in Education., 2019)
Integration of Information and Communication Technology (ICT) in teaching and learning in schools has been hindered by many barriers, including lack of in-service teacher training, teacher beliefs and lack of infrastructure. In the effort to solve the challenge of teacher training in Tanzania, few in-service teachers, based on different parameters, are selected to participate in the face to face ICT training at the specified training centre. Scaling of such teacher training initiatives has been challenging over time. To reach more school teachers, we developed a ten-day online course, run over Moodle. A total of 134 teachers from all the regions of Tanzania registered and participated. Topics were developed based on the preference of the in-service teachers. Online surveys were used to collect qualitative and quantitative data before and after the course. Teachers were active during the duration of the course and many of them applied the skills in their schools by improving their teaching strategies, use of technology tools and sharing experiences with other teachers in their schools.
KerkoCite.ItemAlsoKnownAs: 2339240:ADH54AWX 2405685:DEL3AXBD
Keywords: ⛔ No DOI found

In Ghana, Free High School Brings Opportunity and Grumbling - Nir, S.M. (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:V7XGFRLC

Mapping teacher distribution analysis with digitation technology implementation to improve education management in Bengkkulu City - Nirwana, Nirwana; Vatresia, Arie; Utama, F.P (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:WPX77ITN 2405685:92SJIVRG
Keywords: ⛔ No DOI found

Phonology-based reading instruction to improve dyslexic students’ early reading ability - Novianti, Ranti; Syihabuddin, S.; Rochyadi, Endang (Indonesian Journal of Applied Linguistics, 2019)
KerkoCite.ItemAlsoKnownAs: 10.17509/ijal.v9i2.20242 2339240:UZ7ZKRMU 2405685:TYVK43JK
Keywords: ⛔ No INSPIRE recid found

Evaluation of the extent school access programme assisted teachers to acquire ICT skills - Nwajiuba, Chinyere Augusta; Okoro, Kingsley O.; Edikpa, Edith (Asian Journal of Information Technology, 2019)
Evaluation of the Extent School Access Programme Assisted Teachers to Acquire ICT Skills
KerkoCite.ItemAlsoKnownAs: 10.36478/ajit.2019.67.71 10/ggcmnh 2339240:WURRLWAG 2405685:SUTEI49U 2534378:2TFUSAV4 2534378:ENLRRMCY
Keywords: _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Education management; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2426072; __finaldtb

Supporting teachers in taking up productive talk moves: The long road to professional learning at scale - O’Connor, Catherine; Michaels, Sarah (International Journal of Educational Research, 2019)
In this paper we describe our early, qualitative work on “teacher talk moves” such as revoicing, situated within the urban classrooms of highly skilled teachers, including their role in the work of managing multiple constraints while maintaining productive inclusivity. We then describe our attempts to discern the impact of these talk tools on student achievement in multiple classrooms, using both post-hoc controls and in vivo studies. We move on to the challenges present in disseminating this work in professional development settings; our approach includes framing talk tools as rational responses to actual classroom challenges. Finally we describe current efforts to disseminate cyber-enabled PD in science education K-12, including a central focus on academically productive talk.
shortDOI: 10/ghgn5s KerkoCite.ItemAlsoKnownAs: 10/ghgn5s 2405685:X9V64KPT 2534378:LDIGVCHK

Sierra Leone: Transforming the Country through Innovation - O'Connor, Shane; Zurutuza, Naroa (UNICEF, 2019)
Library Catalog: www.unicef.org KerkoCite.ItemAlsoKnownAs: 2405685:XYSCRRC4

Teachers’ Perception About Integration of ICT Tools in Kiswahili Language Pedagogy in Homabay County, Kenya - Ochieng, BENSON ONYANGO; Miima, FLORENCE ABUYEKA (International Journal of Arts and Commerce, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:E552R7C3 2405685:IEG3IU97

How we measure social and emotional skills - OECD - OECD (OECD Study on Social and Emotional Skills, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:D6XF5GKT 2405685:GI8HHQSN GI8HHQSN

Programme for International Student Assessment (PISA): Results from Pisa 2018 - OECD (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:6YJ7KLI5

The Path to Becoming a Data-Driven Public Sector - OECD (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:E6U46RNV 2405685:CQH4ADND

Children and parents: media use and attitudes report 2019 - Ofcom (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:7FENY3IH 2405685:R7D2BVIY
Keywords: ⛔ No DOI found

The Power of Mobile to Accelerate Digital Transformation in Pakistan - Okeleke, Kenechi (GSMA, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:52GDR44W 2405685:RL6EI64R
Keywords: ___working_potential_duplicate; auto_merged

Scaling Access and Impact: Realizing the Power of EdTech - Omidyar Network (Omidyar Network, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:CM2376RQ 2339240:DVANKZCR 2339240:I3GMH7FI 2339240:NTBHJHCH 2339240:X2A9CDQP 2405685:4E7EW2UF 2405685:5EUGCVFT 2405685:CREQEA9S 2405685:RV53FHR5 2405685:UX7HDLPW

OpenEMIS_Data_Security_Practices_en.pdf - OpenEMIS (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:3UEUQBTC 2405685:UUPHN22F

Education District Profile, 2018 (Unpublished) - Othman, Othman S. (Ministry of Education and Vocational Training, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:SGW9B7QE 2405685:P9KXFUNP

Energy poverty in the Lao PDR and its impacts on education and health - Oum, Sothea (Science Direct, 2019)
112 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.1016/j.enpol.2019.05.030 2339240:AGJJC8EN 2405685:JH73DDFC
Keywords: ⛔ No INSPIRE recid found

The EdoBest Effect - Oviawe, J; Cantrell, S; Chen, L; Buttweiler, M; Nash, S; Nwokeyi, S (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QNQSKMBY 2405685:STIWGP6K

Annual Report 2019 - Pakistan Telecommunication Authority (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:J3DYL6EV 2405685:2B6LEWB7 2405685:3DRT5K3E

Telecom Indicators | PTA - Pakistan Telecommunication Authority (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:8RXYUZE7 2405685:TEM3B6ES 2405685:VBDQ6XBI

PTA Annual Report - Pakistan Telecommunications Authority (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:8YV2FKZ7

Telecom Indicators - Pakistan Telecommunications Authority (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:XTYU35HU

The Indian state of Odisha publishes online dictionaries in 21 indigenous languages - Panigrahi, S (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:BHHGYFPQ 2405685:4LYCFA2P

Learning through play at school: a study of playful integrated pedagogies that foster childrenâs holistic skills development in the primary school classroom. - Parker, Rachel; Thomsen, Bo Stjerne (2019)
This scoping study seeks to understand the role and impact of learning through play at school. The evidence supporting learning through playâs positive impact on child development is strong. Yet many education systems have reduced opportunities for playful learning and increased emphasis on didactic and structured approaches to learning for school readiness and achievement. A re-calibration is needed, as experts have established that play supports the development of early literacy and numeracy skills while also cultivating childrenâs social, emotional, physical and creative skills. Eight pedagogical approaches are identified, namely active learning, collaborative and cooperative learning, experiential learning, guided discovery learning, inquiry-based learning, problem-based learning, project-based learning, and Montessori education. These pedagogies can altogether create learning experiences for children that are meaningful, actively engaging, iterative, socially interactive and joyful. [Abstract]
OCLC: 1090691142 KerkoCite.ItemAlsoKnownAs: 2405685:IXNY2CV5

Measuring Effectiveness of Mobile Application in Learning Basic Mathematical Concepts Using Sign Language - Parvez, Komal; Khan, Muzafar; Iqbal, Javed; Tahir, Muhammad; Alghamdi, Ahmed; Alqarni, Mohammed; Alzaidi, Amer Awad; Javaid, Nadeem (2019)
Technology plays an important role in our society, especially in the ﬁeld of education. It is quite regrettable that people, particularly the deaf, still face a lot of challenges in acquiring an education. Their learning methods are different as compared to hearing people. They use Sign Language (SL) rather than natural language to communicate and learn. They are required to put a lot of effort into learning different concepts using conventional pedagogies. Therefore, there is a dire need for some assistive technology to improve their learn-ability and understandability. In the present study, 192 deaf participants aged 5–10 years were sampled from two special child institutes. The objective of the present study was to determine the effectiveness of a mobile interface through a developed mobile application for learning basic mathematical concepts using Pakistan Sign Language (PSL). The present study bridges the gap between the technology-based method and conventional teaching methods, which are used for teaching mathematical concepts using PSL. The participants were divided into two groups, that is, one group learned through conventional methods (ﬂash cards and board) and the other group through the developed mobile application. The difference in the performance of both the groups was evaluated by conducting quizzes. The quiz results were analyzed by the Z-test and ANOVA. The ﬁndings revealed that the Experimental Group (EG) participants, who were instructed by our mobile application showed higher proﬁciency in the quizzes as compared to the Control Group (CG). EG participants performed better than CG by 12% in the quizzes. A gender based difference was also observed for the quiz scores. Male participants in category C (word problem learning) performed 2.7% better than females in the EG and 2.5% better in the CG. Moreover, a signiﬁcant difference was also observed in the time taken by participants in both groups to complete the quizzes. CG participants took 20 min longer than EG participants to complete the quizzes. The results of the ANOVA showed that the quiz scores were directly affected by the mode of teaching used for participants in both groups.
KerkoCite.ItemAlsoKnownAs: 10.3390/su11113064 2339240:PJGV4NQP 2405685:A5XR2HFD

Supporting adaptive management - Pasanen, Tiina; Barnett, Inka (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:YFAJNMFU 2405685:VGV37LM7
Keywords: ⛔ No DOI found

Managing education in the digital age: Policy brief - Pathways for Prosperity Commission (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:4JH3AW9R 2405685:25L92L73

The digital roadmap: How developing countries can get ahead - Pathways for Prosperity Commission (Pathways for Prosperity Commission, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:FD8HG5C4 2405685:I4ZZB6W6

Artificial Intelligence in Education: Challenges and opportunities for sustainable development - Pedró, Francesc; Subosa, Miguel; Rivas, Axel; Valverde, Paula (UNESCO, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:P65HBZ7C

Notes for the political economy analysis design workshop for the Strengthening the Use of Evidence for Development Impact (SEDI) project in Pakistan - Pellini, Arnaldo; Shaxson, Louise; Rocha Menocal, A (ODI, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:VYJAG3A6 2405685:EVI6J4R5

Factors that motivate teachers to use ICT in teaching: A case of Kaliua District secondary schools in Tanzania - Pima, John Marco (The International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:Q6SW4TNI 2405685:9C6V9Q5Q
Keywords: ⛔ No DOI found

Interactive apps prevent gender discrepancies in early‐grade mathematics in a low‐income country in sub‐Sahara Africa - Pitchford, Nicola J.; Chigeda, Antonie; Hubber, Paula J. (Developmental Science, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:IDAICQ4J 2405685:DUCHF4J8
Keywords: ⛔ No DOI found

Interactive apps prevent gender discrepancies in early-grade mathematics in a low-income country in sub-Sahara Africa - Pitchford, Nicola J.; Chigeda, Antonie; Hubber, Paula J. (Developmental Science, 2019)
Globally, gender differences are reported in the early acquisition of reading and mathematics as girls tend to outperform boys in reading, whereas boys tend to outperform girls in mathematics. This can have long-term impact resulting in an under-representation of girls in Science, Technology, Engineering and Mathematics subjects. Recent research suggests that sociocultural factors account for differences across genders in the acquisition of these foundational skills. In this study, we investigated whether a new technology-based intervention, that included activities accessible to both boys and girls, can reduce gender differences from emerging during the early primary school years. The novel instructional method used in this study employed apps developed by onebillion© delivered individually through touch-screen tablets. Over a series of experiments conducted in Malawi, a low-income country in sub-Sahara Africa, we found that when children were exposed to standard pedagogical practice typical gender differences emerged over the first grade (Experiment 1). In contrast, boys and girls learnt equally well with the new interactive apps designed to support the learning of mathematics (Experiment 2) and reading (Experiment 3). When implemented at the start of primary education, before significant gender discrepancies become established, this novel technology-based intervention can prevent significant gender effects for mathematics. These results demonstrate that different instructional practices influence the emergence of gender disparities in early mathematics. Digital interventions can mitigate gender differences in countries where standard pedagogical instruction typically hinders girls from acquiring early mathematical skills at the same rate as boys. A video abstract of this article can be viewed at https://www.youtube.com/watch?v=55x-6hhAY9M&feature=youtu.be
20 citations (Crossref) [2024-04-29] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/desc.12864 KerkoCite.ItemAlsoKnownAs: 10.1111/desc.12864 2339240:NRXHX74Y 2405685:Q9BQA7GE
Keywords: education; gender inequity; mathematics; reading; tablet technology; ⛔ No INSPIRE recid found

Interactive apps prevent gender discrepancies in early-grade mathematics in a low-income country in sub-Saharan Africa - Pitchford, Nicola J.; Chigeda, Antonie; Hubber, Paula J. (Developmental Science, 2019)
Globally, gender differences are reported in the early acquisition of reading and mathematics as girls tend to outperform boys in reading, whereas boys tend to outperform girls in mathematics. This can have long-term impact resulting in an under-representation of girls in Science, Technology, Engineering and Mathematics subjects. Recent research suggests that sociocultural factors account for differences across genders in the acquisition of these foundational skills. In this study, we investigated whether a new technology-based intervention, that included activities accessible to both boys and girls, can reduce gender differences from emerging during the early primary school years. The novel instructional method used in this study employed apps developed by onebillion© delivered individually through touch-screen tablets. Over a series of experiments conducted in Malawi, a low-income country in sub-Sahara Africa, we found that when children were exposed to standard pedagogical practice typical gender differences emerged over the first grade (Experiment 1). In contrast, boys and girls learnt equally well with the new interactive apps designed to support the learning of mathematics (Experiment 2) and reading (Experiment 3). When implemented at the start of primary education, before significant gender discrepancies become established, this novel technology-based intervention can prevent significant gender effects for mathematics. These results demonstrate that different instructional practices influence the emergence of gender disparities in early mathematics. Digital interventions can mitigate gender differences in countries where standard pedagogical instruction typically hinders girls from acquiring early mathematical skills at the same rate as boys. A video abstract of this article can be viewed at https://www.youtube.com/watch?v=55x-6hhAY9M&feature=youtu.be
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/desc.12864 shortDOI: 10/gf62gt KerkoCite.ItemAlsoKnownAs: 10.1111/desc.12864 10/gf62gt 2339240:EKD2MTYC 2339240:N2E537Q2 2339240:YWPSSQ8L 2405685:7V9ZSCAY 2405685:HVQMEY57 2405685:LTX7M323
Keywords: education; gender inequity; mathematics; reading; tablet technology

Left out, left behind: adolescent girls’ secondary education in crises - Plan International UK (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:ZBUBLI5A 2405685:PRP5JTIX

A spotlight on lack of evidence supporting the integration of blended learning in K-12 education: A systematic review - Poirier, Mark; Law, Jeremy M.; Veispak, Anneli (International Journal of Mobile and Blended Learning (IJMBL), 2019)
Publisher: IGI Global shortDOI: 10/ghgn4q KerkoCite.ItemAlsoKnownAs: 10/ghgn4q 2405685:VPKA2Y2U

Playbook: Government as Platform - Pope, Richard (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:R7R7PJV9 2405685:EEWJPVKT 4656463:EKD46ZDX

Approaches to teacher professional development in low-to-middle-income countries - Power, Tom (Sustainable English language teacher development at scale: Lessons from Bangladesh, 2019)
This chapter begins by situating discussion of approaches to teacher development (TD) in the context of the grand societal challenge of Education for All (UNESCO 2014), as written into the earlier Millennium Development Goals (MDGs) and now Sustainable Development Goal (SDG) 4:‘to ensure inclusive and equitable quality education for all.’ This goal cannot be met without addressing the stark and urgent need for greater numbers of teachers who are adequately equipped with the knowledge and skills to enable effective student learning. Drawing upon personal experiences of work with teachers in LMICs over nearly two decades, the chapter argues against ‘blaming teachers’ for poor student learning outcomes, and advocates instead the development of better understandings of the often challenging contexts in which teachers practise. The chapter then critically examines common approaches to TD that have often failed adequately to equip teachers for classroom practice, outlining a broadly supported agenda for reform. Recent literature has begun to identify certain characteristics of TD programmes that are increasingly associated with effective student outcomes, in what may be an emerging consensus. These characteristics are briefly outlined, before the chapter closes with lessons learned from English in Action. EIA has both contributed to and benefitted from this emerging evidence base and Chapter 5 illustrates how the implementation of EIA exemplifies such characteristics through a cohesive programme design.
Extra URL: http://oro.open.ac.uk/57052/ KerkoCite.ItemAlsoKnownAs: 2339240:D5ABKQWT 2405685:5G9NIHEU 2405685:KJGDVY5F 2405685:P8GU4VUJ 2405685:W9CSF5TT 2534378:3KFFQRC7 2534378:RSWZTN7D
Keywords: Important; Read

Evidence-based approaches to improving teachers’ skills, in schools serving poor and marginalised communities - Power, Tom; Hedges, C; McCormick, R; Rahman, S (Commonwealth of Learning (COL), 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:6ETY8HWG 2405685:26U2C9E5 2405685:FV3V5JDR 2405685:U22CW5TA 2534378:3GHKQTE7
Keywords: C:Poor and marginalised communities; ⛔ No DOI found

Randomizing Development: Method or Madness? - Pritchett, Lant (2019)
An important argument for the increased use of randomized control trial methods in development is that the evidence from these studies will encourage the uptake of effective programs and projects (both through discouraging ineffective projects and improving design of new projects) and this will lead to reduced poverty and improved human well-being. However, cross-national evidence shows that the four-fold transformation of national development, to higher productivity economies, to more responsive states, the more capable organizations and administration and to more equal social treatment produces gains in poverty and human well-being that are orders of magnitude bigger than the best that can be hoped from better programs. Arguments that RCT research is a good (much less “best”) investment depend on both believing in an implausibly low likelihood that non-RCT research can improve progress national development and believing in an implausibly large likelihood that RCT evidence improves outcomes.
KerkoCite.ItemAlsoKnownAs: 2405685:9MD7M5KH 2447227:RULPAH4C
Keywords: ⛔ No DOI found

Digital Foundations Project – Projects – The Public Private Partnership Commission - Public Private Partnership Commission (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QEY68WUZ 2405685:BBIYA6JF

Teaching technology and tolerance in tandem: Culturally responsive classroom guidance interventions - Purgason, Lucy L.; Boyles, Jessica; Greene, Cassidy (Journal of School Counseling, 2019)
Twenty-first century schools are characterized by increasing diversity and use of technology. An opportunity exists for school counselors to utilize technology to create novel and innovative classroom guidance lessons designed to facilitate cultural exploration and promote cultural understanding. This article provides a rationale for how the integration of technology in classroom guidance can be particularly beneficial to immigrant and refugee students. The purpose is to feature three technology tools for use at the elementary, middle, and high school levels. Lesson plans are provided.
ERIC Number: EJ1224480 KerkoCite.ItemAlsoKnownAs: 2339240:6KGQ5V92 2405685:JBSDPKG4 6018420:3GTI2YZT
Keywords: Computer Mediated Communication; Computer Simulation; Cultural Awareness; Culturally Relevant Education; Elementary School Students; English Language Learners; Guidance; High School Students; Immigrants; Information Technology; Intercultural Communication; Intervention; Lesson Plans; Middle School Students; Prosocial Behavior; Refugees; School Counseling; School Counselors; Teaching Methods; Technology Integration

Making sense of bitcoin, cryptocurrency and blockchain - PwC (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:P8J8VMLH 2405685:S5J77WM6

Autism identification and learning through motor gesture patterns - Rafique, Insha; Fatima, Kashmala; Dastagir, Anum; Mahmood, Sajid; Hussain, Muzammil (2019 International Conference on Innovative Computing (ICIC), 2019)
Autism Spectrum Disorder (ASD) is a mental development disorder which affects the processing of information in brain causing delays in the language and reasoning development. A person's behavior can make it distinguishable if he/she has the disorder or not through three main traits i.e. social interaction, restricted/repetitive behavior or communication skills. ASD is usually diagnosed clinically on the basis of some core symptoms and tests which are expensive and can be stressful for a child. Research has shown that Autistic people can be differentiated through the difference of force in their Motor Gestures which is related to restricted/repetitive behavior of Autistic individuals. Motor disturbance is observed in autistic patients which is a key factor for us to make its identification possible through a technical early stage approach which can be very effective. A preschool level Android touch application has been developed in which the motor patterns are observed through touch sensors and inertial sensors. Ten features were obtained as kids touched the screen for the gameplay. This touch and inertial data was then analyzed by processing them through Machine Learning (ML) algorithms to classify between Autistic and Non-Autistic group on the basis of the ten features and the motor disruption was identified. This data supports the motion disruption of movements which is identified to be as a core feature of ASD (restricted/repetitive behavior) and this demonstrates that Autism is possible to be computationally assessed through an interactive and fun gameplay on a smart device. In this way we will be able to diagnose Autism through an easy to access, learning smart phone application instead of a typical, expensive clinical diagnosis.
KerkoCite.ItemAlsoKnownAs: 10.1109/ICIC48496.2019.8966740 2339240:UCLQE3S3 2405685:8TCBSWAX
Keywords: Android touch application; Autism; Autism Spectrum Disorder; Force; Games; Machine Learning (ML) algorithms; Machine learning algorithms; Pediatrics; Tactile sensors; Variable speed drives

English language teaching in Bangladesh today: Issues, outcomes and implications - Rahman, Mohammad Mosiur; Islam, Md Shaiful; Karim, Abdul; Chowdhury, Takad Ahmed; Rahman, Muhammad Mushfiqur; Seraj, Prodhan Mahbub Ibna; Singh, Manjet Kaur Mehar (Language Testing in Asia, 2019)
Given the significance of English in the global world, English language teaching in Bangladesh has become subject to a supreme concern in maintaining economic growth and developing a skilled workforce. In this article, several barriers have been discussed based on a critical analysis of published materials. This review article covers several key issues such as the status of English in the country; English in education policies; factors affecting the implementation of communicative language teaching curriculum, method, and materials in Bangladesh; validity of the current assessment and its washback effect on English language teaching in Bangladesh; and current situation of teachers’ professional development. The article concluded with language policy and planning implications for policymakers, curriculum and material developers, public exams’ test-setters, and future English teacher training programmes, keeping the overall development of ELT in Bangladesh in mind.
KerkoCite.ItemAlsoKnownAs: 10.1186/s40468-019-0085-8 10/gg398d 2339240:6DJW9B5P 2339240:T5V5WJQJ 2405685:EH4KT3RK 2405685:VUKTNAHY

Bangladesh Tertiary Education Sector Review - Rahman, T; Nakata, S; Nagashima, Y; Rahman, M; Sharma, U; Rahman, M.A. (World Bank, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:WMUIJ9VC 2405685:VCP3HEWK

Videogame to support the teaching of reading to deaf children using gamification - Ramos-Ramirez, Rancés; Mauricio, David (Revista Ibérica de Sistemas e Tecnologias de Informação, 2019)
ISBN: 1646-9895 Publisher: Associação Ibérica de Sistemas e Tecnologias de Informacao KerkoCite.ItemAlsoKnownAs: 2339240:D2F5H3MW 2405685:HDA26ARZ
Keywords: ⛔ No DOI found

The analysis of dyscalculia students learning difficulty in inclusive education of primary school level in Tasikmalaya. - Ratnaningsih, Nani; Arhasy, Ebih; Hidayat, Edi (Journal of Education, Teaching and Learning, 2019)
Publisher: STKIP Singkawang KerkoCite.ItemAlsoKnownAs: 10.26737/jetl.v4i1.997 2339240:N5GH7SP6 2405685:2TD98A8I
Keywords: ⛔ No INSPIRE recid found

Use of learning assessment data in education policy-making | IIEP-UNESCO - Raudonyte, Ieva (UNESCO IIEP, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:VJAGTN84 2405685:GLNRL2JL

Ref 2019: Panel Criteria and Working Methods - REF (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F93TEKLT 2405685:7VLNWDHY F93TEKLT

RISE in Nigeria: Non-technical Research Overview - RISE (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:LXSP52B2

Evaluacion de Impacto. Proyecto: Rompiendo Estereotipos, STEM es para chicas - Rodriguez, Lucina; Rivera, Antonella; Orjeda Fernandez, Gisella; Caillaux Icochea, Marcela; Quiroz Zafra, Sofia (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:XFFE7CUZ 2405685:6XPUURQU

Developing Inclusive Education Policy in Sierra Leone: A Research Informed Approach - Rose, R.; Garner, P.; Farrow, B. (Inclusion, Equity and Access for Individuals with Disabilities., 2019)
https://doi.org/10.100/ 978-981-13-5962-0_21 KerkoCite.ItemAlsoKnownAs: 2405685:AMF2AQAE

National Strategic Development Plan - Royal Government of Cambodia (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RCG7YKHH 2405685:LEZSVZYV

Report on Cambodia Labour Force Survey 2019 - Royal Government of Cambodia Ministry of Planning (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:AEHIKPT2 2405685:WQTWUJH2

2Dsearch: Facilitating reproducible and valid searching in evidence synthesis - Russell-Rose, T; Shokraneh, F (BMJ Evidence-Based Medicine, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:N4IU2ZAD 2486141:NFPZ7TMZ
Keywords: ⛔ No DOI found

e-Learning Platform - Rwanda Education Board (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:TBU3AFWV 2405685:8L4ZNNUC

Welcome to RISA - Rwanda Information Society Authority (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:LEYR6F9X 2405685:AUKXWKYX

Technological Hazards in Classroom Instruction: Rebooting the School Education System in Pakistan - Saleem, Khalid; Farid, Shahid; Atiq, Hira (2019)
The classroom instruction had undergone radical changes since the introduction of computers in the 1990s for educational purposes. New techniques and methods of classroom instruction and student-teacher interaction have emerged. The use of ICTs has put forward new prospects for the teachers as well as students. But, the introduction of these media and methods has made it difficult for the teachers to collaborate efficiently with the ever-changing classroom applications. The present study is an effort to disinter the status of the use ICTs for classroom instruction. For this purpose a questionnaire consisting of most common interactive social media apps and classroom instructional materials was used to collect data from the elementary level school teachers. The analysis of data revealed that the teachers are rarely using these apps and materials during their classroom instruction. Moreover, no training had ever been arranged for the teachers to help them use these apps and materials. It is, therefore, recommended that extensive teacher training is needed to enable the teachers for the effective use of ICTs in the classroom. School education cannot be made successful unless the whole system is rebooted through effective measures and productive use of ICTs.
KerkoCite.ItemAlsoKnownAs: 2339240:23MDID4M 2405685:8JGH8ESN
Keywords: ⛔ No DOI found

Factors affecting the E-learning acceptance: A case study from UAE - Salloum, Said A.; Al-Emran, Mostafa; Shaalan, Khaled; Tarhini, Ali (Education and Information Technologies, 2019)
The main objective of this article is to study the factors that affect university students’ acceptance of E-learning systems. To achieve this objective, we have proposed a new model that aims to investigate the impact of innovativeness, quality, trust, and knowledge sharing on E-learning acceptance. Data collection has taken place through an online questionnaire survey, which was carried out at The British University in Dubai (BUiD) and University of Fujairah (UOF) in the UAE. There were 251 students participated in this study. Data were analyzed using SmartPLS and SPSS. The Structural Equation Modelling (SEM) has been used to validate the proposed model. The outcomes revealed that knowledge sharing and quality in the universities have a positive influence on E-learning acceptance among the students. Innovativeness and trust were found not to significantly affect the E-learning system acceptance. By identifying the factors that influence the E-learning acceptance, it will be more useful to provide better services for E-learning. Other implications are also presented in the study.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-018-9786-3 10/gmfk2x 2339240:MM9G52U9 2405685:SHKQ2S7Z

Learning ecologies through a lens: Ontological, methodological and applicative issues. A systematic review of the literature - Sangrá, Albert; Raffaghelli, Juliana Elisa; Guitert‐Catasús, Montse (British Journal of Educational Technology, 2019)
The concept of learning ecologies emerged in a context of educational change. While the “learning ecologies” construct has offered a broad semantic space for characterizing innovative ways of learning, it is also true that its potential to promote innovative educational interventions may have been hindered by this same broadness. Based on this assumption, in this paper the authors carried out a systematic review of the literature on learning ecologies with the aim of analysing: (1) the varying definitions given to the concept, including the ontological perspective underlying the phenomena studied; (2) the methodological approaches adopted in studying the phenomenon; and (3) the applications of the research on this topic. Throughout this analysis, the authors attempt to describe the criticalities of the existing research, as well as the potential areas of development that align well with the theoretical/ontological issues, methodological approaches and educational applications. The authors selected and analysed 85 articles, which they then classified in a set of 20 categories defined by them on a theoretical basis. Moreover, in order to triangulate the manual coding, a bibliometric map was created showing the co-citation activity of the 85 papers. The emerging picture showed significant variability in the ontological definitions and methodological approaches. In spite of this richness, few educational applications currently exist, particularly with regard to technology-enhanced learning developments. Most research is observational, devoted to describing hybrid (digital and on-site) learning activities that bridge the gap between the school and social spaces. Furthermore, many of the studies relate to the field of secondary education, with fewer studies exploring adult learning and higher education. The studies dealing with professional development relate mostly to teachers’ continuing education. The authors conclude that the concept of learning ecologies could be used to address further experimental and design-based research leading to research applications if there is proper alignment between the ontological, methodological and applicative dimensions. The main potential of this strategy lies in the possibility of supporting learners by raising their awareness of their own learning ecologies, thereby empowering them and encouraging them to engage in agentic practices. This empowerment could help maintain and build new and better learning opportunities, which every learning ecology can incorporate, amidst the chaotic abundance that characterizes the digital society.
shortDOI: 10/gf5f7h KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12795 10/gf5f7h 2339240:B3XDZLNT 2405685:64NV5INX
Keywords: Reviewed

Generation Unlimited: Investing for and with Young People - Sarkar, Urmila (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:6R8V7X9Q 2405685:YB8WZC3W

The Issues and Challenges of Using Multimedia at a District Level, Specialized Girls’ College in Bangladesh - Sarowardy, Muhammad Hasan; Halder, Deb Proshad (Creative Education, 2019)
The use of multimedia in imparting education has inevitably been trendy owing to its multifold benefits which have been established and reinvestigated as inseparable teaching aid and tool in teaching-learning process. But This technological assisting component cannot be accorded in many of the institutions of Bangladesh due to several internal as well as external factors. This paper aims to highlight the emerging factors that beset in the institution of Bangladesh. This institutional study on the issues and challenges of using of multimedia in a district (urban area) level girls’ college projects a thorough realization of the difficulties what this types of attributive colleges face in Bangladesh. The resource constraint, the lack of motivation of the teachers, the lack of expert human resource, the insufficient digital tools and lack of multimedia-enabled class environment are found to be barriers and some guiding directives are also imposed in this paper that emerges through the interviews of the teachers and the Vice principal. Thus, the paper, in a miniature effort, tries to lay out the challenges the college of Bangladesh faces and highlight some remedial ways to cope up the challenges.
KerkoCite.ItemAlsoKnownAs: 10/gj37jg 2339240:M5B3GAH9 2405685:LDBLDTX5

Nigeria : A Short Update on Poverty and Shared Prosperity - Sattar, Sarosh; Kalam Azad, Abul (World Bank, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:XHKAC398

The Future Is Ours: Strategic Foresight toolkit – making better decisions - Save the Children UK; School of International Futures (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:WVZ8GDKD

Topic modeling as a strategy of inquiry in organizational research: A tutorial with an application example on organizational culture - Schmiedel, T.; Müller, O; Brocke, J. (Organizational Research Methods, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1177/1094428118773858 2405685:E5FNF8J8 2486141:L8RC8FY4
Keywords: _Added-ailr-2024

Final Evaluation Report: Evaluation of Africa Educational Trust’s Speak Up II in South Sudan - Schulze, Charles (African Education Trust, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:5AX82WHH 2405685:FWQJFXQN

The Global Competitiveness Report 2019 - Schwab, Klaus (World Economic Forum, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:3ITY5U7T 2405685:B95E4PHC 2405685:CU6VHKQI
Keywords: auto_merged; ⛔ No DOI found

Teacher CPD: International trends, opportunities and challenges - Scutt, Cat; Baeyer, Sarah (Chartered College of Teaching, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:36UKQ92L
Keywords: C:International

The impact of learning first in mother tongue: Evidence from a natural experiment in Ethiopia - Seid, Yared (Applied Economics, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1080/00036846.2018.1497852 2405685:CYI57FGE 4042040:Z62RLKMM

Introduction to Systematic Reviews - Serbic, Danijela (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QZ275HD2 2405685:NQ9IFWKD QZ275HD2

The role of online education for the advancement of women - Shahzadi, Dr Jacqueline (Graduate women International (GWI), 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:YEXGZ552 2405685:HI4ZM6MB
Keywords: ⛔ No DOI found

Highlights/Breakdown of the 2020 Approved Budget - Shamsuna Ahmed, Zainab (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:PWJ5P7HV

Digital Kids Asia-Pacific: Insights into Children’s Digital Citizenship - Shin, Tao Seob; Hwang, Hyeyoung; Park, Jonghwi; Teng, Jian Xi; Dang, Toan (UNESCO, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:4XC4UKI8 2405685:QZLYGHH3

How to Do a Systematic Review: A Best Practice Guide for Conducting and Reporting Narrative Reviews, Meta-Analyses, and Meta-Syntheses - Siddaway, Andy P.; Wood, Alex M.; Hedges, Larry V. (Annual Review of Psychology, 2019)
Systematic reviews are characterized by a methodical and replicable methodology and presentation. They involve a comprehensive search to locate all relevant published and unpublished work on a subject; a systematic integration of search results; and a critique of the extent, nature, and quality of evidence in relation to a particular research question. The best reviews synthesize studies to draw broad theoretical conclusions about what a literature means, linking theory to evidence and evidence to theory. This guide describes how to plan, conduct, organize, and present a systematic review of quantitative (meta-analysis) or qualitative (narrative review, meta-synthesis) information. We outline core standards and principles and describe commonly encountered problems. Although this guide targets psychological scientists, its high level of abstraction makes it potentially relevant to any subject area or discipline. We argue that systematic reviews are a key methodology for clarifying whether and how research findings replicate and for explaining possible inconsistencies, and we call for researchers to conduct systematic reviews to help elucidate whether there is a replication crisis.
shortDOI: 10/gftjxg KerkoCite.ItemAlsoKnownAs: 10.1146/annurev-psych-010418-102803 10/gftjxg 2339240:XIMFRKVQ 2405685:QWKJ9FR4
Keywords: Guidelines as Topic; Humans; Meta-Analysis as Topic; Publication Bias; Reviewed; Systematic Reviews as Topic; evidence; guide; meta-analysis; meta-synthesis; narrative; systematic review; theory

Using secondary data in education research - Siddiqui, Nadia (Social Research Update, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:EILE8N78 2405685:EZTM6SAR
Keywords: ⚠️ Invalid DOI

Sierra Leone invests $1.5 million to bring education innovation to schools for better learning outcomes - Sierra Leone Education Innovation Challenge (2019)
A national education dashboard released last month by Sierra Leone’s agency for technology and innovation and the Ministry of Basic and Senior Secondary Education (MBSSE) showed that schools and studentsRead More
Library Catalog: www.dsti.gov.sl EdTechHub.ItemAlsoKnownAs: 2405685:XUALMEQ5

Informed consent and nudging - Simkulet, William (Bioethics, 2019)
In order to avoid patient abuse, under normal situations before performing a medical intervention on a patient, a physician must obtain informed consent from that patient, where to give genuine informed consent a patient must be competent, understand her condition, her options and their expected risks and benefits, and must expressly consent to one of those options. However, many patients refrain from the option that their physician believes to be best, and many physicians worry that their patients make irrational healthcare decisions, hindering their ability to provide efficient healthcare for their patients. Some philosophers have proposed a solution to this problem: they advocate that physicians nudge their patients to steer them towards their physician's preferred option. A nudge is any influence designed to predictably alter a person's behavior without limiting their options or giving them reasons to act. Proponents of nudging contend that nudges are consistent with obtaining informed consent. Here I argue that nudging is incompatible with genuine informed consent, as it violates a physician's obligation to tell their patients the truth, the whole truth, and nothing but the truth during adequate disclosure.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bioe.12449 KerkoCite.ItemAlsoKnownAs: 10.1111/bioe.12449 2339240:QV33NIH3 2405685:4GJDPR2X
Keywords: bullshit; decision-making; informed consent; libertarian paternalism; lying; nudging; professional ethics; truth-telling

Behavioural Innovation: embracing behavioural science for lasting impact - Simpson, Lea (Brink, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:PCJXFRIC 2405685:ILLVHDH4

Education and Disability in the Global South: new perspectives from Africa and Asia. London: Bloomsbury Publishing. - Singal, Nidhi; Lynch, P; Johansson, S. T (British Journal of Special Education, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1111/1467-8578.12292 2339240:EVTHNM88 2405685:3M6AJUNM

SITA Group CSR Report 2019 - SITA (2019)
Towards a Sustainable Future
EdTechHub.ItemAlsoKnownAs: 2405685:GWT7IX55

GPE 2020 Country-level Prospective Evaluations. Malawi - Smith, Prepared Matthew; Fenning, Christine (Global Partnership for Education (GPE), 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:9ABNU7B8 2405685:DQGKVE9A
Keywords: ⛔ No DOI found

Expensive Classrooms, Poor Learning: The Imperatives of Reforming School Construction in Egypt - Sobhy (Alternative Policy Solutions, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:TDXJZ3NX 2405685:RTUVJKMS 4656463:RJ4BGGQV

What do Tanzanian parents want from primary schools—and what can be done about it? - Solomon, Samuel; Zeitlin, Andrew (Research on Improving Systems of Education (RISE), 2019)
KerkoCite.ItemAlsoKnownAs: 10.35489/BSG-RISE-RI_2019/009 2129771:WRWFX4LH 2339240:MKH7QA3N 2405685:3Y9DDX62 2405685:89L48PRQ

Fen Bilimleri Öğretmenlerinin Akıllı Tahta Kullanım Durumlarının Belirlenmesi: Tokat İli Örneği* - Soylu, Ümit İlay and Bozdoğan, Aykut Emre (Uluslararası Türk Eğitim Bilimleri Dergisi, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QCLAGHXV 2405685:FQ9VXLTU

Early Years Preschool Program Impact Evaluation 2018, Midline Survey - Spier, Elizabeth (World Bank, Development Data Group, 2019)
KerkoCite.ItemAlsoKnownAs: 10.48529/ASWC-7R84 2405685:4Q6ZLDXY 2486141:PHAA4RZ7

Developing a competency-based of language skills and literary abilities in the primary school - Suryanto, E.; Akhadiah, S. (Journal of Physics: Conference Series, 2019)
0 citations (Crossref) [2024-04-29] Issue: 1 KerkoCite.ItemAlsoKnownAs: 10.1088/1742-6596/1339/1/012066 2339240:9M4FKZWM 2405685:Z32RMRLK
Keywords: ⛔ No INSPIRE recid found

Annual Survey of Progress and Achievement - T-TEL (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:8MWHYQCT 2405685:PSLM9PT6

Pre-primary teachers’ preparedness in integrating information and communication technology in teaching and learning in Tanzania - Tandika, Pambas Basil; Ndijuye, Laurent Gabriel (Information and learning science, 2019)
Purpose Integration and use of technology in teaching and learning in the education sector from pre-primary education (PPE) to the higher levels of education, is a policy issue. In developed countries, including Tanzania, information and communication technology (ICT), especially in PPE, is inadequately researched for laying evidence on its applicability in instruction and learning. Therefore, this paper aims to determine pre-primary teachers’ preparedness in integrating ICT in classroom instruction and challenges teachers face in integrating it for child’s meaningful learning. Design/methodology/approach Methods and instruments: a qualitative transcendental phenomenological approach was used in determining teachers’ preparedness in integrating ICT in PPE in Tanzania. It was further used to collect data that describe the teaching and learning through the integration of ICT in every session as their lived experience for pre-primary teachers. Its selection was appropriate as it allowed researchers to systematically analyse for description the commonalities and differences existing among the involved teachers in integrating ICT in teaching and learning as their lived experiences (Moerer-Urdahl and Creswell, 2004). To appropriately analyse teachers’ understanding and experiences regarding ICT and its integration in teaching and learning in pre-primary classes, semi-structured interviews and open-ended questionnaires were used for in-depth understanding of the study problem. Semi-structured interviews were used to collect data through open-ended questions where researchers took an average of 40 min per session with participants’ (teachers) using notebooks to take note of their thoughts, feelings and beliefs about ICT integration in PPE. Use of the semi-structured interview was based on the reality that it provides in-depth information pertaining to participants’ experiences and viewpoints of a particular topic (Turner, 2010). Once the interview session was complete, each teacher was given a questionnaire to fill in for triangulating their experiences. Description of participants: a total of 14 schools constituting 28 teachers were purposively sampled and engaged in this study. Analysis of participants’ demographic characteristics indicates that all of the involved teachers had certificate in teacher education that qualified them as primary school teachers. Meanwhile, 18 (66.7 per cent) of the pre-primary school teachers who were involved in this study were female with only 10 (33.3 per cent) had working experience at and above five years of teaching in early grade classes. Study participants (teachers) from Itilima and Meatu Districts were purposively involved in the study as their experiences in young children’s learning and contextual influences (educational and training policy of 2014, the ICT policy of 2007, and foreign studies) are potential in improving the quality of learning. Study area: the current study was conducted in two districts (Itilima and Meatu) all found in Simiyu region. The two districts were selected and considered appropriate by the study as they constituted the 17 most disadvantaged rural areas in Tanzania (Mosha et al., 2015). Authors describe the two districts as having poor educational outcomes mainly relatively low pass rates in the primary school leaving examination results. In Itilima, one ward out of 22 was studied in which its six schools [with a total of 12 teachers] among 87 schools in the district were involved. While in Meatu district, eight of 121 schools [with a total of 16 teachers] in one ward of 29 wards were studied. This implies that a total of 14 schools and 28 teachers were involved in this study. Data analysis: the data collected through the interviews and open-ended questionnaires were subjected to content analysis procedures (reading and re-reading notes and transcripts followed by a three-steps-coding process consisting of open, axial and selective coding procedures). The analysis process was informed by the Vagle’s (2014) six steps for phenomenological research data analysis procedure (holistic reading of the entire text, first line-by-line reading, follow up questions, second line-by-line reading, third line-by-line reading, and subsequent readings). Practically, the researchers read and re-read the texts and transcribed data from the language used during data collection that is Kiswahili, into the reporting language that is English. Following transcription, data were coded for developing categories of data through axial and elective coding processes. Findings The data analysis was conducted and results and its discussion are presented in three sub-sections: preparedness of teachers in using ICT in teaching and learning; teachers’ views about the integration of ICT in teaching and learning; and challenges faced by teachers in integrating ICT in teaching and learning. Teacher’s preparedness in the use of ICT in teaching: exploration of teachers’ preparedness in integrating ICT in teaching and learning was preceded by exploration of teachers’ understanding of ICT in teaching and learning. Analysis revealed that majority of teachers were aware about ICT in teaching and learning and they understood it as the implementation of curriculum at school level that involves use of ICT-based facilities such as television, mobile phones, computer and radio. Teacher elaborated that appropriate use of ICT-based facilities that would later develop children to potentially improve their understanding and practical application in daily life. Other teachers understood ICT in teaching and learning as use of printed materials [newspapers and magazines] in facilitating pupil’s learning of planned lessons. While other teachers were aware of what ICT means the second category of teachers as noted in their responses, had limited understanding, as to them, ICT in education meant use of printed materials. Difference in teachers’ understanding of the ICT in teaching and learning also indicate some teachers viewing it as use of ICT facilities in developing children’s competencies in the specific subject. In the teachers’ views, ICT is considered as subject content and they delimited their understanding into that perspective ignoring it as technological use for facilitating meaningful learning in all subjects. Their views are based on the development of children with competencies useful in facilitating further learning in the subject known as Teknolojia ya Habari na Mawasiliano. Following the question based on exploring teachers’ understanding of ICT in teaching and learning, researchers explored teachers’ preparedness in using ICT in teaching and learning. Table 1.0 illustrates teachers’ multiple responses regarding their preparation. Table I: teacher’s preparedness in using ICT in teaching and learning. S/N; preparedness; freq; and per cent. Enhancing child’s understanding on the use of ICT-based facilities-20, 71.4; using remedial sessions teaching ICT-12, 42.8; using ICT-based facilities for teaching other classes-8, 28.5. Table 1.0 illustrates that teachers are prepared to enable children use ICT to access information and more knowledge related to their school subjects and general life. They were of the view that ICT could serve well in areas where text and supplementary books are scares or torn-out by pupils because were poorly bound or due to poor quality of papers used. Therefore, availability of ICT facilities in schools would become important resource-materials for pupils, as well as teachers. For instance, a teacher said that; Availability of ICT facilities, such as computers in schools will help us in preparing notes or content for supplementing their learning. Different from the paper-based notes, computers will keep our notes properly compared to the papers that get easily displaced and hard to retrieve notes when lost (Interview, 20 April 2016). In addition to the use of ICT facilities in serving as resource material, their use in schools would aid pupils and teachers to use them beyond teaching and learning. Teachers narrated that children may find games and puzzles that all help in stimulating their thinking, hence interest in schooling and further learning. Teachers also said they are prepared to use even extra hours that are beyond school timetable to ensure children learn well to meet the uncovered periods once facilities are placed in school. Use of extra hours beyond the normal school timetable comm. Research limitations/implications The study was limited to the accessed and involved schools as some schools were found to have no specific teachers teaching a pre-primary class on reasons the responsible teacher for the class had retired. As a result, researchers spend extended time to travel and reach schools that were located far from one school to the other. Again, some teachers were reluctant in participation on reasons that researchers are evaluating their competency for reporting to the higher authorities. Practical implications Differences in teachers’ understanding of the ICT in teaching and learning also indicate some teachers viewing it as the use of ICT facilities in developing pupils’ competencies in the specific subject. In the teachers’ views, ICT is considered as subject content and they delimited their understanding into that perspective ignoring it as technological use for facilitating meaningful learning in all subjects. Effective integration of ICT for efficiency in instruction depends on the teacher’s preparedness especially competency in using the equipments and infrastructures especially electric power. Social implications Integration of Information and Communication Technology in teaching and learning in PPE is socially important in the view that all children regardless of their background (urban or rural, affluent or poor) benefits in learning through use of technology. The children’s access to education integrating ICT would ensure equal opportunities
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/ILS-01-2019-0009 2339240:T4KLPYB6 2405685:TZWTRL92
Keywords: Information and communication technology; Learning and quality instruction; Pre-primary education; Preparedness; Teaching

Teacher Development Programme End of Programme Report - Teacher Development Programme (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:YREGV4VF 2405685:AIWDTWHX

Let’s Read - The Asia Foundation (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:HM8MTIIC 2405685:Y4NFIS88

Statistics - The Global E-Waste Statistics Partnership (E-Waste in Africa, 2019)
Continent / Region / Country statistics
KerkoCite.ItemAlsoKnownAs: 2339240:D3C55V34 2405685:GNE5FSXL

The Personal Data Protection Bill 2019 - The Personal Data Protection Bill (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:Q2TCIVX4 2405685:WLGITJRI

Supporting Adolescent Girls Education in Zimbabwe - Thukral, H; Conrad, L; Laesecke, A; Reeves, A; Sibal, M; Zasoski, L (School-to-School International, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RS9XM7XC 2405685:PVRJTG4H

Teacher Training Delivery Mode Research - Tiguryera, Scholastica (USAID, RTI, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:WI5IJ7ZS 2405685:S546AYYY
Keywords: ⛔ No DOI found

Research on Children with Disabilities Influences Education Policy in Pakistan - Tofaris, Elizabeth; Bari, Faisal; Malik, Rabea (REAL Centre, University of Cambridge and The Impact Initiative, 2019)
KerkoCite.ItemAlsoKnownAs: 10.35648/20.500.12413/11781/ii333 2339240:5PXUHZI5 2405685:UZRF9Y2H

Technology is transforming governance in Pakistan - Touqeer, Irum; Rontoyanni, Clelia (World Bank Group, 2019)
Punjab Excise and Taxation Service Center. Photo: World Bank Technology is changing our world faster than ever before. And Pakistan, home to more than 64 million internet users and 62 million people connected to mobile data, is no exception. As they’ve become more digital-savvy, Pakistanis are now expecting better digital ...
KerkoCite.ItemAlsoKnownAs: 2339240:EELM2PKK 2405685:FM2QXUDY

Making great strides yet a learning crisis remains in Tanzania: Results of the SDI and SABER service delivery surveys - Trako, Iva; Molina, Ezequiel; Asim, Salman (The World Bank, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:SNZ3GBER 2405685:V4XEV62U

Slum children: barrier faced by children in accessing primary education - Tripathi, Alpica (United International Journal for Research & Technology, 2019)
Children are mostly recognised by the society as diamond gift from the God, as jewellers cleaves the diamond from other unwanted and rough pieces. In the same way, parents of the children cleave off unwanted thoughts, societal behaviour and environment from the life of the society so that brilliancy of children luminous in the world. The responsibility of parents as well as government of country is to make availability of healthy and friendly environment for the learning of the children. The slum children’s faces lots of barriers and hurdles in accessing and attaining the education. The education is the eminent phase of socialising the child. Education is a power to accelerate skills and talents among children. Education helps to transform the living conditions and thinking ability of children. The right to education is not only the right to access education but also the right to receive an education of good quality. Education must be available and accessible but also acceptable and adaptable. The most of the slum children are indulging their precious time in doing labour, earning a coin, fighting daily from the challenges of life and wandering here a there for having a meal. The children are no doubt a tribute from Almighty but they should be preserve and nurture very sensitively in span of life. Urban children face a particularly complex set of challenges affecting their development and the fulfilment of their rights. The worst consequences of urbanisation, industrialisation and modernisation give birth to diverse group of children in urban areas like slum children, runaway children, working children, street children, orphan child. These children spend their precious time as rag picker, construction workers, factory workers, child beggars, migrant labourer, sex worker and domestic workers in swanky lifestyle of cities. These un-notified and homeless children are far from the reach of the policies of the government and even not noticed by the policy maker of the government. These children are deprived from their rights of survival, rights of protection, rights of development and rights of participation. These children even fight for their basic necessities of life.
KerkoCite.ItemAlsoKnownAs: 2339240:QFXBURV4 2405685:WPJAASED
Keywords: ⛔ No DOI found

Are our children learning? Uwezo Tanzania learning assessment report 2019 | Unesco IIEP Learning Portal - Twaweza East Africa (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:AL7LX9CJ 2405685:7KQIECHH

Research on children with disabilities influences education policy in Pakistan - UKFIET; Education, 2019 |; Disabilities | 0 (UKFIET: The Education and Development Forum, 2019)
This impact story was written and produced by the Impact Initiative for International Development Research – a collaboration between the REAL Centre, University of Cambridge and the Institute of Development Studies, University of Sussex. You can download and read the full impact story here. According to new research generated by the Research for Equitable Access […]
KerkoCite.ItemAlsoKnownAs: 2339240:HLAR6CJT 2405685:PEJWTXNK

Sustainable Development Knowledge Platform - UN (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:XX8K6IWH 2405685:8JT6YXRS 8JT6YXRS

Inequalities in Human Development in the 21st Century - UNDP (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:V6TNP72D 2405685:9TDAZW6S

Inequalities in Human Development in the 21st Century, Ghana - UNDP (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:HDRIMSCU

Inequalities in Human Development in the 21st Century, Kenya - UNDP (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:392IVFST

Inequality in Human Development in the 21st Century, Jordan - UNDP (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:3EEM6V4S

Access to information: A New Promise for Sustainable Development - UNESCO (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:TIQ7G37D 2405685:XQQP38SL

ICT Transforming Education in Africa UNESCO-KFIT project update, January-March 2019 - UNESCO (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:5ZL38WL2 2486141:VBBHJJDJ

ICT Transforming Education in Africa UNESCO-KFIT project update, January-March 2019 - UNESCO Digital Library - UNESCO (UNESCO, 2019)
EdTechHub.ItemAlsoKnownAs: 2405685:E6JTI753

New Methodology Shows that 258 Million Children, Adolescents and Youth Are Out of School - UNESCO (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:DFK8M42B 4042040:6Q4K3URI

Right to education handbook - UNESCO (UNESCO, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:6YQ6VKH6 2405685:PFS3CXZ3

The world is off track in achieving the global education goal, SDG4 - UNESCO (UNESCO, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:MY93PCGX 2405685:UVVIK4X9

Training Trainers on Gender Responsive Pedagogy | UNESCO-IICBA - UNESCO (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:89V62T8K 2405685:6D3Y4NWN

Education sector analysis methodological guidelines. Vol. 2: Sub-sector specific analysis - UNESCO-IIEP; World Bank; UNICEF; Global Partnership for Education (2019)
The purpose of these guidelines is to provide methods for comprehensive education sector analyses to support the preparation and monitoring of education sector plans. They are an update of a 1999 document that has been used to support the preparation of approximately 70 Education Country Status Reports (CSR) in more than 40 countries. The goal of the guidelines is to strengthen national capacities in order that Government teams can conduct education sector analyses with progressively less external support.
KerkoCite.ItemAlsoKnownAs: 2405685:BRN5TXIS

New methodology shows that 258 million children, adolescents and youth are out of school - UNESCO Institute for Statistics (UNESCO Institute for Statistics, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:8NSWCYW9 2405685:G6XBUYV2

Sustainable Development Goal 4 : 4.c.1 Proportion of teachers who have received at least the minimum organized teacher training - UNESCO Institute for Statistics (Sustainable Development Goal 4, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:NHPAFI8E 2405685:3FRX2EUN

New methodology shows that 258 million Children, Adolescents and Youth are out of school - UNESCO-UIS (United Nations Educational, Scientific and Cultural Organisation, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:VXZWG9VF 2405685:3NXMC26R

Education 2030: A strategy for refugee education - UNHCR (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:C8RXY86T

Digital literacy for children — 10 things to know - UNICEF (2019)
Digital literacy goes beyond technical know-how. It refers to the knowledge, skills and attitudes that allow children to be both safe and empowered in an increasingly digital world. This encompasses their play, participation, socializing, searching and learning through digital technologies. What constitutes digital literacy will vary according to children’s age, local culture and context. Children need to be digitally literate even when they are not online. Facial scanning and artificial intelligence-based profiling increasingly affect children’s lives. Children’s schooling, social welfare and future job opportunities may depend on how well they understand the digital world around them. Digital literacy is a growing part of any approach to skills development. It features in UNICEF’s framework which seeks to prepare children and adolescents for school, work and life. In addition to digital literacy, other interconnected skills for UNICEF are: foundational skills (literacy and numeracy); transferable skills (also known as life skills, 21st-century skills or soft skills); and job-specific skills (technical and vocational skills). Tools to develop and assess digital literacy are proliferating. A number of digital competence frameworks have been developed by both international agencies and companies. Frameworks are a necessary starting point as they define the boundaries of what constitutes digital literacy and inform curricula and assessments. Despite using a range of labels (e.g. digital literacy, skills, citizenship), they broadly converge around the idea of a set of competencies that include technical as well as transferable skills, such as communication and problem solving. Yet most existing tools place little emphasis on children. Digital literacy definitions usually focus on citizens of all ages and not on children specifically. UNICEF believes there is a need to focus more on digital literacy for children, who have unique needs. In this area, there is a slow change from a risk and safety paradigm towards rights-based approaches that favour expression, play and development. Few programmes operate at scale or have been evaluated for impact. One contributing factor is the lack of global consensus and standards that makes it difficult for governments and other stakeholders to design and implement comparative and cost-effective initiatives, especially within developing countries. Similarly, UNICEF programmes would benefit from greater coordination. While UNICEF has delivered a range of digital literacy programmes at the request of governments, a survey of 40 initiatives carried out by 37 Country Offices shows they are not well coordinated with each other, and knowledge is not systematically generated or shared about efficacy and impact. Implementing digital literacy is not easy. According to the Country Offices surveyed, key barriers to digital literacy programming are: lack of teachers’ and trainers’ capacity; lack of ICT infrastructure; low connectivity (especially for remote areas); and a lack of understanding from decision-makers. The Country Offices are asking for policy development support, digital literacy frameworks, curriculum guidelines and practical tools, such as training manuals and toolkits. Some existing digital literacy frameworks or tools suit UNICEF well. These include the DigComp framework of the European Commission and the Digital Kids Asia-Pacific framework developed by the UNESCO Asia and Pacific Regional Office in Bangkok. If using existing digital literacy frameworks, UNICEF can add value by focusing on children. Digital literacy programmes should be context-driven. Implementing digital literacy programmes effectively requires more than simply importing a good programme from elsewhere. Beyond choosing a framework, an integrated approach to digital literacy involves undertaking a preliminary diagnostic review of the local context, developing operationalization guidelines and conducting impact assessments.
KerkoCite.ItemAlsoKnownAs: 2339240:DAVC5T72 2405685:LGV5JGFE

Early Literacy and Multilingual Education in South Asia - UNICEF (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:YPILCB6K 2405685:BIML6DRG

Every child learns: UNICEF education strategy 2019–2030 - UNICEF (2019)
UNICEF education strategy 2019–2030
KerkoCite.ItemAlsoKnownAs: 2339240:9ZGVZ22B 2405685:LTZFWSMN

Every child learns: UNICEF education strategy 2019-2030 - UNICEF (United Nations Children's Fund, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:3EKFXYT2 2405685:4FYKRPLC

Including Everyone Strengthening the Collection and Use of Data About Persons with Disabilities in Humanitarian Situations - UNICEF (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:4ACZGLC4 2405685:LPKBXGZH

Multiple Indicator Cluster Survey Findings Report: Zimbabwe - UNICEF (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:XBYY45NG

Regulatory Policies and ICT Trends: Insights from Timor-Leste - United Nations Economic and Social Commission for Asia and the Pacific (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:9MINAGWZ 2405685:4TFDFF8G

Results of the Population and Housing Census 01/4/2019 - United Nations Vietnam (United Nations Vietnam Press Centre, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:G6XE8D4J

Universal Basic Education 2018 Indicator Profile for Basic Education Institutions in Nigeria: Public Schools Commission - Universal Basic Education Commission (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:V8XHE9D4 2405685:DE29EEVB

Final Report - SENEGAL - Universalia (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:QHLV2XP3

2018 Civil Society Organization Sustainability Index - for Asia 5th Edition – December 2019 - USAID (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:SA6U2LEK 2405685:3ILYUE9N

Early Grade Reading Study II (EGRS II) - USAID (2019)
The activity team works in partnership with the Department of Basic Education to evaluate the efficacy and cost-effectiveness of interventions focused on improving the performance of grade 1 and 2 learners in the subject English First Additional Language.
Library Catalog: www.edu-links.org KerkoCite.ItemAlsoKnownAs: 2405685:FPWA6KU3

Improving Education Opportunities USAID Senegal Fact Sheet - USAID (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:BVBHJWJC

Software Global Goods Valuation Framework - USAID (2019)
Software global goods are digital tools, often “free and open-source”, that can be adapted and reused for the global health sector to meet the needs of various countries and contexts.
KerkoCite.ItemAlsoKnownAs: 2339240:JIC88SW3 2405685:CQ89L8A8

How ed-tech can help leapfrog progress in education - Vegas, Emiliana; Ziegler, Lauren; Zerbino, Nicolas (Brookings, 2019)
This brief analyzes the use of ed-tech innovations around the world.
KerkoCite.ItemAlsoKnownAs: 2339240:LH87HU6C 2405685:D9VNFXR8

Evaluation of Inclusive Basic Education in the UNICEF Country Programmes 2012-2016 and 2017-2021 - Venäläinen, Raisa; Chultemsuren, Tamir; Tsendendamba, Batsugar (UNICEF, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:PMGRMUMI 2405685:S2JMNIPP

Using examination and learning assessment data to uncover foundational skill gaps in Sierra Leone’s secondary schools - Waistell, Daniel; De, Sourovi; Ofori Owusu, Diana; Allen, Reg; Sanni, Kayode; Dupigny, Albert (Education technology and data science for inclusive systems, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:J8IWHLVQ
Keywords: ⛔ No DOI found

Assessment of accelerated education to catch up with missed school programme in post crisis settings: Case study of selected IDP camps in Maiduguri metropolitan council - Wali, Yagana S; Muhammad Ali, Mustapha (British Journal of Educational Studies, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:GV95QIPL 2405685:VQUVNDCL
Keywords: ⛔ No DOI found

Redesigning the design: a review of education technology interventions in Pakistan - Waqar, Yasira; Bokhari, Tahira Batool (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:QCA97BYT 2405685:GTK8US66
Keywords: ⛔ No DOI found

Can’t Wait to Learn Lebanon - War Child (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:2DC7K49J 2405685:WGG5SRLK

I'd blush if I could: closing gender divides in digital skills through education - West, Mark; Kraut, Rebecca; Ei Chew, Han (UNESCO, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:GZ2PGRST 2405685:ZQPSPXQG

Liberia: Farewell 2019 - A Review of ICT Initiatives in Liberia - Wilkins, Darren (All Africa, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:PKSW9KQS

Examining sustained impacts of two teacher professional development programs on professional well-being and classroom practices - Wolf, Sharon; Peele, Morgan E. (Teaching and Teacher Education, 2019)
We examine second-year impacts of a 1-year pre-primary teacher training and coaching program, delivered with and without parental-awareness meetings, evaluated with a school-level randomized trial. Outcomes included teachers’ professional well-being and classroom practices. Most gains observed during the program year faded out. However, there were small sustained impacts on the implementation of training activities. Counteracting effects of the parental-awareness meetings were evident, with suggestive evidence that teachers in this treatment group displayed lower scores on one dimension of classroom qualitydSupporting Student Expressiondcompared to controls. Implications for professional development and educational quality are discussed.
shortDOI: 10/ggjk6c KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2019.07.003 10/ggjk6c 2339240:GB3MPNJU 2405685:M8ZR3GRF
Keywords: _proposed-for: Scoping review

Cambodia Learning Poverty Brief - World Bank (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:PX7JEYZP 2405685:YDZI4I58

Country Diagnostic of Senegal - World Bank (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:HPZVAMCI

El Salvador | Data - World Bank (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:R3QZYUMR 2405685:ETUARZB7

Ending Learning Poverty: What will it take? - World Bank (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:3VBYYMMW 2405685:IN2IKH2L

Ghana Accountability for Learning Outcomes Project - World Bank (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:VXTPKKNF 2405685:RYNVN7QJ

Kenya Overview - World Bank (2019)
The World Bank’s work in Kenya supports the government’s Vision 2030 development strategy, which aims to accelerate sustainable growth, reduce inequality, and manage resource scarcity.
Library Catalog: www.worldbank.org KerkoCite.ItemAlsoKnownAs: 2405685:3KINEYR6

Learning poverty - World Bank (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:HBB55RC3 2339240:MKW7W6F6 2405685:JL3T5B44 2405685:LM9S4WTM

Learning Poverty Brief - World Bank (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:GBKAU9Q5 2405685:NGEPLHDI 2405685:YBW7KR4Z

Liberia - Improving Results in Secondary Education Project - World Bank (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:B759A5Q3

Nigeria | Population - World Bank (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:GA3Y3TKV

Pakistan - Learning Poverty Brief - World Bank (World Bank Group, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:6NDFBFR9 2405685:9GTWUCR4

Population growth (annual %) - Pakistan - World Bank (World Bank Group, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:U4A7B3YM 2405685:FR9ZYXYR

Population, total - Pakistan | Data - World Bank (World Bank Group, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:AEP6WKXX 2405685:B2N4JR6B

Project Information Document: Sierra Leone Free Education Project - World Bank (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:GIC5MV46

Secondary Education Quality Improvemen Project (SEQUIP) - World Bank (World Bank Group, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:38JKD79X 2405685:SWHXQAFJ

Secondary Education Quality Improvement Project (SEQUIP) - World Bank (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:PX9AA76T 2405685:TGPWHJQ8

The Future of Work in Africa: The Roles of Skills, Informality, and Social Protection in Unleashing the Promise of Digital Technologies for All - World Bank (World Bank, 2019)
A new World Bank report says Sub-Saharan African countries could benefit from well-harnessed technological adoption.
KerkoCite.ItemAlsoKnownAs: 2339240:WY5ZPXR9 2405685:W8VE6V9D

The Third Punjab Education Sector Project (PESP III) - World Bank (World Bank Group, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:SLADUHSN 2405685:6K54KZ57

The World Bank In Zimbabwe - World Bank (2019)
The World Bank's lending program in Zimbabwe is inactive due to arrears, and the role is now limited to technical assistance and analytical work.
Library Catalog: www.worldbank.org EdTechHub.ItemAlsoKnownAs: 2405685:GGXFDY2S

Urban population - Pakistan | Data - World Bank (World Bank Group, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:46DZPS2B 2405685:5DQAJU7Q

Bangladesh - Additional Financing to the Second Reaching Out-of-School Children Project : Learning Opportunities for Displaced Rohingya Children - World Bank Group (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:XP8M9YUK 2405685:Z37EUUD9

Assistive technology - World Health Organization (2019)
WHO fact sheet on assistive technology. Assistive technology enables people to live healthy, productive, independent, and dignified lives, and to participate in education, the labour market and civic life.
KerkoCite.ItemAlsoKnownAs: 2339240:3GM7SDTZ 2405685:AAEKD76U

Guidelines on Physical Activity, Sedentary Behaviour and Sleep for Children Under 5 Years of Age - World Health Organization (World Health Organization, 2019)
33 p.
Accepted: 2019-04-03T14:35:28Z KerkoCite.ItemAlsoKnownAs: 2339240:HXRJ26E9 2405685:R8MFHINW

Global learning XPRIZE: Executive summary - XPRIZE (XPRIZE, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:LMHWGYMG 2405685:RF9I68JG

Securing learning for children in conflict and crisis - Yarrow, Noah; Capek, Maja (World Bank, 2019)
Publisher: World Bank Publications KerkoCite.ItemAlsoKnownAs: 2339240:CLJU3BUW 2405685:R8XFHX2K

Towards equitable access to information and opportunity for all: mapping schools with high-resolution Satellite Imagery and Machine Learning - Yi, Zhuangfang; Zurutuza, Naroa; Bollinger, Drew; Garcia-Herranz, Manuel; Kim, Dohyung (2019)
KerkoCite.ItemAlsoKnownAs: 2405685:DHZ6C2T4 4042040:ATJ89RKU

A support programme for caregivers of children with disabilities in Ghana: Understanding the impact on the wellbeing of caregivers - Zuurmond, Maria; Nyante, Gifty; Baltussen, Marjolein; Seeley, Janet; Abanga, Jedidia; Shakespeare, Tom; Collumbien, Martine; Bernays, Sarah (Child: Care, Health and Development, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1111/cch.12618 2405685:NPVKZCTP